FGFR2 mediates the progression of colorectal cancer by promoting the expression of HIF-1α via the PI3K/AKT/mTOR pathway - Yiyang Hu; Liuxu Yao; Yuhong Li; HongFa Wang; Huang Huang; Junbiao Fang; Foquan Luo (Tissue and Cell, 2027)

A data-driven spatial equilibrium framework for strategic reallocation in urban underground space planning - Wei-Xi Wang; Fang-Le Peng; Yun-Hao Dong; Hu Li (Tunnelling and Underground Space Technology, 2027)

Promiscuous activity of ornithine decarboxylase from Enterobacter hormaechei: An alternative pathway for histamine formation in fermented sausages - Wei He; Binbin Li; Kaidi Hu; Xumei Zhong; Yulin Zhang; Jiamei Yu; Jiaxin Xie; Chengtao Li; Fengqin Li; Lanlan Wu; Shuhong Li; Jianlong Li; et al. (Food Microbiology, 2027)

Higher mitochondrial DNA methylation is associated with increased risk of stroke: a nested case-control study - Xueru Fu; Yuewan Fang; Yujie Zhao; Bin Yang; Yaqin Su; Li Yang; Weifeng Huo; Liuding Wen; Yuying Wu; Yang Zhao; Fulan Hu; Ming Zhang; et al. (Human Genetics, 2026)

Integration of clinical and cellular lipidomics identifies a serum metabolite signature predictive of oxaliplatin resistance in colorectal cancer - Xue-fei Wu; Li-ye Xie; Fu-wei Lian; Hao-tang Wei; Shu-fang Ning; Bang-li Hu (Functional & Integrative Genomics, 2026)

Molecular epidemiology and antimicrobial resistance of Vibrio parahaemolyticus isolates from aquatic products in the Southern Fujian coast, China - Qiao-Hua Zheng; Yang Chen; Yu-Fang Tian; Turmidzi Fath; Jun-Chao Zheng; Dan-Feng Zhang; Yi-Hong Wang; Qing-Sen Chen; Feng-Xia Li; Xiu-Min Chen; Yuan-Qing Hu (Brazilian Journal of Microbiology, 2026)

Long-term cattle manure application rebuilds topsoil buffering capacity and mitigates fertilizer-induced acidification in Mollisols - Yafei Su; Wenbin Bao; Zhenhua Yu; Xiaojing Hu; Changkai Liu; Rui Fang; Junjie Liu; Jian Jin; Guanghua Wang; Xingyi Zhang; Yuriy Kravchenko; Xiaobing Liu; et al. (Agriculture, Ecosystems & Environment, 2026)

Role of residual carbon in the fusion temperature regulation of ash-iron mixtures under entrained-flow gasification conditions - Hao Cheng; Guoqiang Cao; Zhongren Ba; Donghai Hu; Yongbin Wang; Chunyu Li; Jiantao Zhao; Yitian Fang (Fuel, 2026)

The study on laccase-mediated covalent cross-linking driving subunit rearrangement of rye secalins - Peng Zhou; Yue Hu; Nurbiya Abdujilil; Yan Zhang; Ying Li; Juanjuan Liu; Guilan Zhu; Wei Wang; Jinwu Chen; Lulu Zhou; Jingjing Wang; Zemin Fang (Food Hydrocolloids, 2026)

Differential effects of pristine and aged polystyrene nanoplastics on the first molting process in Tachypleus tridentatus - Ranran Ding; Youji Wang; Nisha Singh; Shuang Shen; Miao Xu; Hexu Li; Yanxin Wang; Ruoling Sun; James Kar-Hei Fang; Khor Waiho; Hanafiah Fazhan; Menghong Hu (Environmental Pollution, 2026)

Tire wear particle leachate-induced hepatotoxicity in Carassius auratus: Associations with gut microbiota dysbiosis and lipid metabolism disorder - Peng Fang; Yongyu Hu; Maolin Zhang; Yuanyuan Tan; Siwen Li; Fang Xiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

AI-enhanced superior bionic skin with dual-layer nanofiber membranes for sweat-based multiple biomarker detection - Xinshuo Liang; Kaisong Huang; Shuo Meng; Wenjie Fang; Shuai Zhang; Leqi Lei; Xin Li; Xi Yao; Jinlian Hu (Chemical Engineering Journal, 2026)

Vacancy engineering triggers Cu-O-Ti superexchange: Spatial charge separation and synchronous utilization for enhanced Fenton-like performance - Zhimo Fang; Zhou Zhou; Xiaomeng Li; Dongyang Li; Bin Hu; Haoyu Wang; Lin Zhang; Qin Dai; Kai Li; Yao Kong; Shiguan Yang; Qiang Lu (Chemical Engineering Journal, 2026)

Gravel cover regulates vegetation growth and bank-slope erosion resistance in the Three Gorges Reservoir Area - Yuanyuan He; Xusheng Xia; Chenyu Zhang; Li Wang; Shimei Wang; Xianwei Zhang; Wenzhuo Hu; Keying Zhang; Xingfeng Zhang; Kun Fang; Huafeng Deng (CATENA, 2026)

Boosting low-temperature catalytic performance over VOx/TiO2 via tuning vanadium sites and oxygen species for chlorobenzene oxidation abatement - Xuan Wang; Danrui Zhu; Wei Hu; Shilong Li; Xue Fang; Mingzhi Wang; Jianjun Chen; Zhengmao Cao; Qiulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Effect of food components on arsenic metabolism by the gut microbiota using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME) - Yue Wu; Shimao Xiong; Xiyan Jiang; Peng Xiao; Fang Zhao; Rui Li; Syed Ali Hassan; Xiaolin Cai; Zhengyi Hu; Dennis Sandris Nielsen; Naiyi Yin; Yanshan Cui (Food Research International, 2026)

Combined effects of Trametes hirsuta AH28–2-derived laccase and Bacillus-derived α-amylase on the rheology and quality of modified Rye bread - Jingjing Wang; Yue Hu; Mengyuan Li; Guilan Zhu; Lulu Zhou; Yan Zhang; Ying Li; Peng Zhou; Zemin Fang (Food Chemistry, 2026)

Integration of nontargeted screening with in vitro bioassays to evaluate and identify estrogenic compounds in food contact materials - Hongyan Li; Linhao Ying; Ya Chen; Wendi Fang; Yuxia Hu; Chao Deng; Lei Zhao; Jiangdong Zhang (Food Chemistry, 2026)

Formation and application of soybean protein amyloid fibril-dextran-epigallocatechin gallate nanoparticles for interfacial engineering of lycopene-loaded Pickering emulsions - Changling Wu; Jie Hou; David Julian McClements; Li Li; Zhaogui Chen; Chengjun Liao; Kaixi Chen; Guangbiao Yan; Hao Hu; Guanyu Fang; Zhiping He; Xingquan Liu; et al. (Food Chemistry, 2026)

Unlocking the potential of defatted Antarctic krill meal for producing xanthine oxidase inhibitory peptides through high hydrostatic pressure-assisted enzymatic hydrolysis - Kai Chen; Gang Wang; Zeyu He; Gangliang Hu; Zhiyue Wu; Xiaoli Li; Ruosi Fang; Gongnian Xiao (Food Bioscience, 2026)

Lipidomic and physicochemical insights into thermal processing-induced changes in dried whole egg-dofu - Yunxiao Xie; Jiayao Peng; Yanyin Li; Yan Chen; Guo Chen; Renyi Qin; Jinqiu Wang; Gan Hu; Fang Geng (Food Bioscience, 2026)

Canned seafood as a potential source of microplastics exposure with taxon-specific partitioning and packaging-derived contamination - Xinyi Li; Shihan Xu; Jin Qian; Binhan Li; Li'ang Li; Chengming Zhang; Fangzheng Zhang; Menghong Hu; Moslem Sharifinia; Nisha Singh; Jae-Seong Lee; James Kar-Hei Fang; et al. (Environmental Pollution, 2026)

Super-lithostatic fluid overpressure–tectonic coupling in horizontal opening-mode fracturing and blocky cementation in the crust - Miao Wang; XinXin Gao; Yelei Wang; Yong Chen; Daniel Moncada; Fang Hao; Tao Hu; Fulai Li; Yifan Song; Ziye Lu; Xin Zeng; Zhiming Zhang; et al. (Earth-Science Reviews, 2026)

Thermodynamic and kinetic regulation of small-molecule acceptor via chlorinated thiophene side-chain engineering for as-cast toluene-processed organic solar cells - Jianlong Hu; Jianan Sheng; Hang Yang; Kewei Hu; Jiahao Qian; Xuncheng Zhu; Xiangyu Zheng; Tingting Fang; Yue Wu; Youkuo Wang; Chaohua Cui; Yongfang Li (Chemical Engineering Journal, 2026)

Defect-engineered Cu2O/g-C3N4 for enhanced catalytic ozonation via surface hydroxyl enrichment and nitrogen-vacancy-guided interfacial construction - Mingyue Li; Zhuang Guo; Zhixiong Hu; Dan Li; Fang Chang; Jian Wei; Maosheng Zheng (Chemical Engineering Journal, 2026)

Natural polysaccharides modulate the microbiota-gut-brain axis through multiple targets: A new perspective on the pathogenesis and treatment of depression - Zhizhong Luo; Yang Fang; Hu Qi; Xi Peng; Xiongwei Zang; Lan Yi; Jiuseng Zeng; Li He; Nan Zeng (Carbohydrate Polymers, 2026)

Performance of current atmospheric observation networks on quantifying sub-continental emissions of halogenated gases - Xiaoyi Hu; Zifa Wang; Bowei Li; Xuekun Fang (Atmospheric Environment, 2026)

Mechanistic insights into glufosinate ammonium‑induced hepatotoxicity in grass carp: Integrating network toxicology, transcriptomics, experimental validation and intervention strategies - Wenying Sun; Peng Fang; Yongyu Hu; Maolin Zhang; Wentao Ma; Siwen Li (Aquatic Toxicology, 2026)

Highly sensitive and precise SERS quantification of P. gingivalis in complex saliva matrices via AgNPs@4-MPBA substrates coupled with the NiPLS-AMLP algorithm - Lina Bai; Kai Hu; Jie Li; Guoqiang Fang; Wuliji Hasi; Siqingaowa Han (Analytica Chimica Acta, 2026)

A sunscreen UV filter disrupts energy homeostasis and impairs growth in the endangered living fossil Tachypleus tridentatus - Guangjin Li; Yiting Li; Xingda Lin; Shiyong Wang; Meijiao Yan; Yaoyao Chu; Chuihong Fang; Zhi Chen; Fengxiao Hu (Journal of Hazardous Materials, 2026)

Isolation and functional characterization of goose-derived lactic acid bacteria with growth-promoting and gut health benefits in Sanhua geese - Changsheng Jiang; Wenli Shi; Ji Chen; Weitao Wang; Dandan Fang; Wanji Zhan; Wei Zuo; Chuanyan Che; Ahmed H. Ghonaim; Mengmeng Jin; Qianqian Hu; Keli Yang; et al. (Food Chemistry, 2026)

Analysis of the damage mechanism of resveratrol to Acetobacter sp. based on proteomics and its combined inactivation effect with pulsed electric field - Yifan Dong; Siyu Chen; Er-Fang Ren; Lili Gai; Zhong Han; Jun-Hu Cheng; Xin-An Zeng; Weizheng Zhou; Li Zheng; Debao Niu (Food Microbiology, 2026)

Integrated ATAC-seq and RNA-seq analysis reveals dynamic changes in chromatin accessibility and gene expression in Acrossocheilus fasciatus after Streptococcus agalactiae infection - Wenbin Fang; Renxuan Huang; Zihang Wu; Wanqing Tong; Minghao Hu; Yanhong Li; Shanjian Zheng (Fish & Shellfish Immunology, 2026)

Compound-specific effects of phthalate esters on nitrogen cycling and N2O emissions in paddy soils under contrasting moisture regimes - Yuna Li; Yunzhe Hu; Shulan Cheng; Huajun Fang; Yifan Guo (Environmental Pollution, 2026)

Operationally stable biphasic absorbent for low-energy CO2 capture: from laboratory development to pilot-scale validation - Zhipeng Chen; Mengxiang Fang; Zhixiang Xia; Ximing Hu; Ying Wang; Yutao Xia; Tao Wang; Qinghui Wang; Shuifei Li; Yali Yang (Chemical Engineering Journal, 2026)

Charge-programmable carbon dots tailored by amino acid pKa spectrum for spatiotemporally controlled siRNA delivery and antiviral protection in plants - Fang Wang; Xueyang Ji; Yan Zhao; Jingyan Hu; Ziqi Zhang; Jinxuan Wang; Kailin Su; Jingyan Jia; Ao Zhou; Ning Li; Ying Song; Changjun Zhang; et al. (Chemical Engineering Journal, 2026)

A tetrahedral framework nucleic acid-based co-delivery platform enhances the antibacterial activity of nisin and quercetin against MRSA - Jiuyan Zhang; Ruiyuan Shi; Jiajian Liang; Yingqing Liu; Zhao Tu; Xiaonan Wang; Likai Hu; Chengbao Huang; Lingyan Cheng; Jie Wang; Xiang Fang; Li Wang (Critical Reviews in Food Science and Nutrition, 2026)

Earthworm burrows enhanced rice root growth under a no-tillage rice-rapeseed rotation system - Lingling Liu; Chao Li; Huan Fang; Weida Gao; Craig J. Sturrock; Paul D. Hallett; Hu Zhou (Soil and Tillage Research, 2026)

Chemical constituents from Litsea pungens and their anti-inflammatory and cytotoxic activities - Kexin Chen; Fang Yang; Si-Yu Hu; Yu Zhang; Chuanrun Li; Yongxu Zhao; Chuan-Rui Zhang (Phytochemistry Letters, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Abiotic stress sensing in plants: Biochemical and biophysical basis - Qingya Lv; Jiawei Li; Changyun Liu; Kenz R. Samraoui; Stephanie Hutin; Xu Li; Faming Dong; Haiyan Xiong; Yidan Ouyang; Honghong Hu; Yibo Li; Jo Hepworth; et al. (Molecular Plant, 2026)

Divergent effects of plastic mulching on the soil micro-food web across planting patterns and soil depths: Evidence from a field experiment - Yumiao Sun; Jiaqi Sun; Sijia Wang; Cuicui Qu; Yiwen Hu; Fang Li; Dongmei Geng; Li Xu (Journal of Environmental Management, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Comparison of laccases from Streptomyces coelicolor and Coprinopsis cinerea on rye dough secalins reconstruction - Yue Hu; Peng Zhou; Guilan Zhu; Yan Zhang; Xiao Gao; Juanjuan Liu; Chengshuo Tang; Ying Li; Zemin Fang; Jingjing Wang (Journal of Cereal Science, 2026)

Rubidium isotopes reveal no sub-arc melting of altered oceanic crusts in a cold subduction zone - Zi-Qiang Zhong; Ding-Sheng Jiang; Saskia Erdmann; Yi-Xiang Chen; Xia Hu; Zheng Xu; Wei Zhang; Jia-Ru Sheng; Wang-Ye Li; Fang Huang (Geochimica et Cosmochimica Acta, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Vibration isolation for mechatronic metamaterial rings with piezoelectric shunting circuits - Long Zhao; Ze-Qi Lu; Li-Fang Lin; Hu Ding; Li-Qun Chen (Engineering Structures, 2026)

Improved photovoltaic performance via synergistically combining electric poling and flexoelectricity on lead-free ferroelectric (KNbO3)0.9(BaNi1/2Nb1/2O3-δ)0.1 films - Chuanqing Li; Yu Cai; Feifan Hu; Zhihua Duan; Tao Wang; Xiaomei Qin; Yanxue Tang; Xiangyong Zhao; Aiyun Liu; Feifei Wang; Zhongchen Gao; Fang Wang; et al. (Chemical Engineering Journal, 2026)

Inflammatory response involved in cartilage degeneration induced by T-2 toxin: systematic review - Qian Li; Yikai Hu; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Miao Wang; Huanxia Zhang; Yanjie Dou; Shuiyuan Yu; Fang-fang Yu (Mycotoxin Research, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Agent-specific bleeding signatures in non-hypertensive versus hypertensive patients exposed to oral anticoagulants: a real-world pharmacovigilance study - Ying Feng; Hua-Hua Liu; Liu-Cheng Li; Kai-Li Mao; Xiao-Fang Niu; Jie Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrating network pharmacology, molecular docking, machine learning, and experimental validation: puerarin improves sepsis-induced acute kidney injury via the Sirt1-Nrf2-HO-1 pathway - Shangping Fang; Jiameng Liu; Wanning Li; Zhaorong Chang; Yuesong Han; Cuifeng Zhang; Xianwen Hu; Yongquan Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multi-phase PAH transport across the land-sea continuum: Mechanistic drivers of source-sink dynamics and socioeconomic modulation - Yang Ye; Huijun Liu; Jiajie Hu; Minggang Cai; Lixiao Chen; Mengyang Liu; Zhiheng Li; Zhiguo Fang; Wenlu Zhao (Marine Pollution Bulletin, 2026)

Non-nitrogen-fixing halophytes alleviate nitrogen limitation and decrease soil salinity through nitrogen transfer from nitrogen-fixing plants - Zehao Zhang; Tian Li; Yao Zhang; Rui Hu; Jiabao Li; Hongxiang Jin; Ying Fang; Zhaohua Lu; Jingkuan Sun (Plant and Soil, 2026)

The Hippo–Yki pathway governs growth and cell fate in the posterior silk gland of the silkworm - Yan Ma; Zhiyong Zhang; Wenhui Zeng; Zhou Fang; Xin Yu; Lin Cheng; Zehui Ma; Qipeng Zeng; Dena Jiang; Yiyun Tang; Jie Hu; Chen Zhao; et al. (Insect Biochemistry and Molecular Biology, 2026)

Gelator-dependent crystalline network tolerance governs probiotic dispersion stability in oleogels through mechanisms involving rheology and crystallization kinetics - Shuai Chen; Zengliu Song; Ran Qiu; Suqiong Fang; Zhe Li; Ronghai Hu; Yong Cao; Jie Xiao (Food Research International, 2026)

Phyllanthus emblica L. polyphenols mitigate high-fat diet-induced cognitive impairment via modulating gut microbiota and calcium/cAMP signaling pathways - Xinyi Deng; Ziyuan Li; Jiamin Tian; Fang Chen; Zeyuan Deng; Qirui Hu; Xiaoya Wang; Le Kang; Zhihong Zhang; Yao Pan (Food Bioscience, 2026)

Ultrathin COF membranes with polyethyleneimine synergy for efficient dye separation - Qiongan Meng; Xin Fang; Zhongwei Pang; Jundie Hu; Jiafu Qu; Jianzhang Li; Yahui Cai (Chemical Engineering Journal, 2026)

Benefits for non-Article 5 countries under the Montreal Protocol from supporting the phase-out of ozone-depleting substances in Article 5 countries - Mingrui Ji; Xiaoyi Hu; Mengyue Ma; Bowei Li; Ruoqian Wang; Xuekun Fang (Atmospheric Pollution Research, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Time-Series Transcriptomics of a Gill Cell Line (BTG) from Chinese Bahaba (Bahaba taipingensis) During ISKNV Infection (3–24 hpi) - Chenfei Guo; Zhihong Gong; Fei Fang; Xihong Li; Lei Wang; Na Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Fishes, 2026)
The Chinese bahaba (Bahaba taipingensis), an endangered marine fish, is highly vulnerable to infectious spleen and kidney necrosis virus (ISKNV). In this work, we developed a gill filament-derived cell line, designated BTG, to investigate how these cells respond to ISKNV over time, specifically from 3 to 24 h post-infection (hpi). BTG cells grew steadily, displayed a diploid chromosome number of 2n = 48, demonstrated high transfection efficiency, and were highly susceptible to viral infection. Characteristic cytopathic effects (CPEs) became noticeable as early as 6 hpi at 27 °C. RNA-seq profiling showed that the number of differentially expressed genes (DEGs) steadily increased with time. Standard enrichment analysis at individual time points (3, 6, 12, and 24 hpi) highlighted pathways mainly involved in DNA replication, cell cycle control, ribosome assembly, transcription and translation, mismatch repair, and cell adhesion. Temporal clustering analysis, however, revealed hidden patterns in immune gene expression. Genes that were consistently downregulated were enriched in immune-related pathways, including ECM–receptor interaction, cytokine–receptor signaling, PI3K–AKT, and Wnt signaling, indicating prolonged suppression of host defense mechanisms. In contrast, clusters of genes transiently upregulated during the first 6 h post-infection were associated with antiviral and innate immune pathways, such as NF-κB, JNK, IRF3, IRF7, caspases, JAK, MHC I, and lysosome-related functions, suggesting a rapid but short-lived antiviral response. Genes that were continuously upregulated were primarily involved in nucleic acid replication and protein synthesis, reflecting a gradual host cell reprogramming to support viral replication. Taken together, these findings reveal a temporal shift in BTG cells from an initial burst of immune activity to immune suppression, accompanied by enhanced viral replication. The BTG cell line thus represents a valuable in vitro model for dissecting ISKNV–host interactions and offers new perspectives on the molecular strategies employed by megalocytiviruses in B. taipingensis.

Optimization of neo-female induction by 17β-estradiol administration and subsequent production of YY males in yellow drum (Nibea albiflora) - Bingbing Fang; Qihui Zhu; Weihua Hu; Ruiyi Chen; Shengping Li; Wanchang Zhang; Dongdong Xu (Aquaculture International, 2026)

Prediction of stability and deformation for seawalls using RSM-SVR method - Xingye Sun; Shenming Zhu; Zhichao Hu; Wenjiang Chen; Haiyun Wei; Dongzi Pan; Yujie Li; Minhui Fang; Zhen Guo (Marine Georesources & Geotechnology, 2026)

Per- and polyfluoroalkyl substances in food contact materials: Migration, health risks and sustainable alternatives - Run Li; Shensheng Xiao; Jiayong Hu; Qiao Wang; Jingguang Li; Min Fang; Nannan Qiu; Xin Liu; Yongning Wu (Trends in Food Science & Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel method for spatial localization of dam leakage channels based on total magnetic field gradient - Diquan Li; Xuefeng Chen; Yanfang Hu; Yongbing Wang; Zhe Wang; Yiming Wu; Rui Fang (Journal of Applied Geophysics, 2026)

Amelioration of NAFLD by herbal-dairy meal replacement (HD-MR) potentially via the gut microbiota–short-chain fatty acid axis - Yuqing Xie; Qirui Hu; Zhiqing Gong; Chuxian Li; Jinrong Yang; Pinnan Zhang; Fengxin Wang; Yao Pan; Zeyuan Deng; Fang Chen (Food Bioscience, 2026)

Whole-genome sequencing and probiotic characterization of Lacticaseibacillus paracasei SMN-LBK isolated from koumiss produced in Xinjiang, Northwest China - Yu Gao; Zhexin Fan; Shengwei Hu; Zhifeng Fang; Xiaoqian Chen; Baokun Li; Yuhui Li (Food Bioscience, 2026)

Uncovering the synergistical roles of interfacial catalysis and wettability of Janus membranes for anti-wetting and anti-fouling of membrane distillation - Xinyu Ye; Mengmeng Lou; Xiangming Xu; Lijun Meng; Baowei Hu; Fang Li (Chemical Engineering Journal, 2026)

Substrate specificity and in vivo efficacy of engineered cocaine esterases toward cocaine and its toxic metabolites - Zhenzhen Li; Qi Hu; Xingyu Deng; Cong Chen; Ziying Ren; Nan Mo; Zheer Huang; Binjie Wang; Lei Fang; Jiye Wang; Shurong Hou; Xiabin Chen (Chemico-Biological Interactions, 2026)

A comprehensive review on the main alkamides in Piper nigrum and anti-inflammatory properties of piperine - Rui Guo; Yiming Fang; Junyao Li; Haoyang Gao; Zhiqiang Niu; Yadong Lv; Long You; Ji Zhang; Xu Wang; Guiping Wu; Taoyun Wang; Weicheng Hu; et al. (Phytochemistry Reviews, 2026)

Lithium enrichment in pegmatites driven by magmatic fluids: evidence from Rb stable isotopes - Xia Hu; Guangwei Li; Zhiqin Xu; Fang Huang (Mineralium Deposita, 2026)

Artesunate overcomes oxaliplatin resistance in colorectal cancer by inducing ferroptosis through inhibition of the CDK5/Nrf2/GPX4 pathway - Feng Lv; Xiao-huan Li; Si-qi Li; Hao-wei Deng; Hao-tang Wei; Ke-zhi Li; Ming-zhi Xie; Li-ye Xie; Shu-fang Ning; Bang-li Hu (Apoptosis, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Cuproptosis: a novel mechanism and 3PM-oriented therapeutic strategy for cancer - Ding Yang; Wei-Ting Hu; Miao Li; Fang-Qing Shen; Hao-Yu Wang; Jin-Ying Ye; Fu-Lu Ren; Yun Wang (EPMA Journal, 2026)

A molecular switch: antitoxin HigA integrates transcriptional activation by XreR and proteolytic clearance by Lon to balance virulence and stress adaptation in the fish pathogen Edwardsiella piscicida - Yin Gou; Jingjing Sui; Jinggang Dong; Jun Li; Baocun Zhang; Qingjian Fang; Guoqing Wang; Hanjie Gu; Yonghua Hu (Marine Life Science & Technology, 2026)

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

Nutrient input of coastal aquaculture may affect growth of mangrove following intermediate disturbance hypothesis: critical thresholds and spatial relationship coupling - Haonan Li; Haitao Chen; Longtian Huang; Chunxiang Liu; Jin Luo; Haoyu Wang; Mengji Zhang; Xiuqiong Liang; Yongze Xing; Wenlu Lan; Xiaoyan Peng; Sheng Fang; et al. (Marine Pollution Bulletin, 2026)

Genomic insights into adaptation and microevolution of two novel non-AOA Nitrososphaeria, Acidarchaeum fankouense and Thermosulfuris yongpingense, in acid mine drainage ecosystems - Licao Chang; Xikai Su; Wenzhe Hu; Yun Fang; Jun Liu; Jintian Li; Linan Huang; Wensheng Shu (Systematic and Applied Microbiology, 2026)

Brain gray matter atrophy in adult population with cognitive impairment due to chronic cadmium exposure - Zhentao Gao; Longtao Yang; Rong Ma; Xiaoying Li; Fang Pei; Wei Hu; Yixuan Wu; Xiaojiang Tang; Jun Liu (NeuroToxicology, 2026)

Temperature-dependent demethylation of methylarsenic by methanogens: Linking carbon metabolism to arsenic speciation in landfills - Yuzhou Yang; Yuqian Wang; Jinye Li; Yuyang Long; Xiaocui Xiao; Chengran Fang; Lifang Hu (Journal of Hazardous Materials, 2026)

Arsenic recovery by UV/sulfite/iodide system: Dual roles of carbonate/bicarbonate - Xilong Zhou; Haoxiang Zhong; Jianing Han; Qiaozhi Li; Ziqi Zheng; Meifang Li; Hui Wang; Ying Fang; Jiaqin Deng; Xinjiang Hu (Journal of Cleaner Production, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Stand development drives the reassembly of soil fungal communities and soil multifunctionality in poplar plantations of northern China - Hongling Yang; Haifu Fang; Ya Hu; Hailing Li; Xiangwen Gong; Yulin Li; Xiaoan Zuo (Plant and Soil, 2026)

First report of apple geminivirus infecting apple in Liaoning and Hebei provinces, northern China - Kai-jie Li; Xu-dong Fan; Fang Ren; Yu-xin Hao; Guo-jun Hu; Ya-feng Dong (Journal of Plant Pathology, 2026)

On-site, intelligent, and integrated monitoring of cereal safety: A review of advances in pathogens and toxins detection (2015-2025) - Ruiyuan Shi; Jiajian Liang; Chengbao Huang; Likai Hu; Lingyan Cheng; Zhao Tu; Xiaonan Wang; Jie Wang; Xiang Fang; Li Wang (Trends in Food Science & Technology, 2026)

Enhanced Fenton-like catalysis and antimicrobial activity of bimetallic nanocomposite functionalized hierarchical nanofibrous membranes - Xinru Chen; Yulu Shi; Junfeng Hu; Xiaofeng Fang; Fang Li; Guomin Wang; Zheyi Meng (Journal of Water Process Engineering, 2026)

Redox coupling induced by nitrite in the UV/sulfite system: Mechanisms and pathways of metformin degradation - Wenyao Liang; Ziqi Zheng; Jiazhen Zheng; Xinjiang Hu; Haoxiang Zhong; Chao Zhang; Changlan Hou; Ying Fang; Hui Wang; Meifang Li; Xi Hu; Jiaqin Deng; et al. (Journal of Environmental Chemical Engineering, 2026)

Fourier transform ion cyclotron resonance mass spectrometry revealed molecular diversity and complexity of dissolved organic matter in the influent and effluent of 49 wastewater treatment plants - Xuexin Gong; En Hu; Zhineng Hao; Fang Yang; Baozhu Pan; Ming Li (Journal of Environmental Chemical Engineering, 2026)

Mechanisms, influencing factors, removal effectiveness and electrochemically enhanced technologies of tidal flow constructed wetlands - Chunyao Zhao; Yuqing Yang; Xiaoheng Wang; Peiyang Zhang; Bohan Fang; Yuting Zhong; Ke Zhao; Zhen Hu; Erping Cui; Jianan Li (Journal of Environmental Chemical Engineering, 2026)

Crystallize and protonate: A dual-boosting strategy for photocatalytic NO abatement over carbon nitride - Haonan Hu; Bin Liu; Xianli Hu; Hao Ma; Ting Zhang; Jinwu Bai; Wei Xu; Ruimei Fang; Yuhan Li; Fan Dong (Journal of Environmental Sciences, 2026)

Effect of atmosphere on the ash fusion temperature and precipitation kinetic of metallic iron of iron-containing coal ash - Hao Cheng; Guoqiang Cao; Zhongren Ba; Donghai Hu; Yongbin Wang; Chunyu Li; Jiantao Zhao; Yitian Fang (Fuel, 2026)

INU/AOS attenuates DEX-induced osteoporosis via interacting with gut microbiota and reversing inflammation in mice - Li Yang; Ran Liao; Xinjie Hu; Liang Hu; Shanshan Li; Yuntao Liu; Zhen Zeng; Ran Li; Zhengfeng Fang; Hong Chen (Food Bioscience, 2026)

Aroma in ‘Munage’ Grape Spirits response to different inoculation strategies of H. uvarum/P. fermentans in mixed fermentation with S. cerevisiae - Jia-Qi Wang; Jia-Liang Hu; Qian-Qian Feng; Yang Zhang; Hong-Yan Zhang; Su-Fang Zhang; Yun-Kui Li; Hua-Feng Yang; Guo-Jie Jin (Food Bioscience, 2026)

X-ray investigation into the effects of stress paths on the meso-structure evolution of coral sand - Fenghui Hu; Xiangwei Fang; Xin Liu; Hong Li; Zhenhan Chen; Zhichao Dong (Engineering Geology, 2026)

Sulfur-modified electrolytic manganese residue catalysts promote surface oxidative complex formation for the degradation of nitroimidazole organic pollutants with high half-wave potentials - Xin Xu; Linling Fang; Xiang Lu; Yang Hu; Xueli Yang; Mengke Li; Yun Liu; Yuehui Chen; Zhimin You; Zhiguo He (Chemical Engineering Journal, 2026)

Unraveling -Ni2+/-Mn2+ doped Ti3CNTx MXene nanowebs for high-performance asymmetric supercapacitors - Sabeen Fatima; Yu Sun; Lei Han; Nan Han; Muyang Li; Safia Khan; Klaus Leifer; Xiaoqing Jiang; Jie Li; Qingsong Wan; Hongji Fang; Yafei Ning; et al. (Chemical Engineering Journal, 2026)

LDL receptor affects the skeletal muscle and bone microstructure of female mouse through the Wnt/β-catenin signaling pathway - Yue Hu; Huiling Liu; Chaoyue Zhao; Peizhao Shi; Meiqing Lu; Yanli Chen; Xiaoyan Fang; Lingling Huang; Zhikun Bai; Jinhua Wang; Hai Li (Journal of Molecular Histology, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Global Potential and Trade‐Offs of Conservation Tillage for Crop Productivity and Ecosystem Services - Wanyang Zhang; Linchuan Fang; Wenju Zhang; Chaoqun Wang; Tianyi Qiu; Xiaokun Li; Min Huang; Bolin Li; Ling Xia; Lai Peng; Yifeng Xu; Xiaoyong Wu; et al. (Global Change Biology, 2026)
Conservation Agriculture (CA) is pivotal to achieve sustainable intensification, yet the global efficacy of its core practice, conservation tillage (CT), remains debated regarding the trade‐offs between crop productivity and ecosystem services across diverse environmental contexts. Here, we conducted a second‐order meta‐analysis, synthesizing 69 published meta‐analyses, to elucidate the context‐dependent drivers regulating the “win‐win” outcomes of CT. Globally, CT reduced greenhouse gas (GHG) emissions by 5%, increased soil organic carbon sequestration by 21%, increased soil fertility by 11%, and reduced soil erosion by 12%, all while maintaining crop yields comparable to conventional tillage. However, CT can also emerge as a partial trade‐off between crop yields and ecosystem services, notably between crop yield and GHG mitigation. These trade‐offs were strongly regulated by climatic and edaphic conditions as well as management intensity. For instance, strong synergies between crop productivity and multiple ecosystem services were more pronounced in (semi‐)arid regions characterized by low temperatures and low precipitation, as well as in coarse‐textured alkaline soils. Furthermore, integrating CT with residue retention and crop rotations maximized these synergies, mitigating potential yield penalties. Collectively, our synthesis demonstrates that context‐specific refinement of CT implementation is essential to reconcile agricultural productivity with ecosystem services, thereby advancing climate‐resilient agricultural systems globally.

Genomic and polyphasic characterization of Halomonas salsilacus sp. nov., moderately halophilic bacterium isolated from saline lake sediment - Xia Luo; Yumo Li; Mingzhu Zhang; Rongfei Hu; Fang Liu; Feina Li; Li Tuo (Systematic and Applied Microbiology, 2026)

Quantifying the nonlinear interactions of 2D/3D building and green space morphology on land surface temperature across different urban functional zones - Haiyan Luo; Rui Zhou; Chunlin Li; Qun Ma; Xuening Fang; Yina Hu; Xinlin Lv; Zining Dong; Yujing Tian; Shubo Fang (Sustainable Cities and Society, 2026)

Reconfiguring China’s interprovincial rice distribution to support low-carbon goals under climate change - Jintao Yang; Fang-He Zhao; Manchun Li; Penghui Jiang; Zhepeng Hu (Resources, Conservation and Recycling, 2026)

The overlooked role of nitrate in mediating electron transfer and enhancing reactive species generation in TiO2 photocatalytic water remediation - Zheng Hu; Jin Wu; Lingzhi Shen; Zili Lin; Zihong Xu; Zhenjun Xiao; Zheng Fang; Daguang Li; Ping Chen; Wenying Lv; Guoguang Liu (Process Safety and Environmental Protection, 2026)

An integrated flotation-cyclic leaching process for reduced acid consumption in vanadium shale extraction - Yibo Hu; Chenkun Lin; Zhiwen Xia; Jianxing Fang; Cong Yin; Qingliang Wang; Huijuan Li; Pengfei Hu (Minerals Engineering, 2026)

Synergistic oxygen vacancy and multivalence in Co/Cu-ZIF/V₂O₅ nanozyme enable ultrasensitive colorimetric detection of ascorbic acid and epigallocatechin gallate - Mingxuan Liu; Yuanjuan Bai; Jianming Tan; Zetong Mei; Kun Du; Gonggang Liu; Li Liu; Shanshan Chang; Ling Fang; Jinbo Hu (Food Chemistry, 2026)

Effects of enzymatic hydrolysis and Maillard reaction on the flavor and antioxidant activity of Agaricus blazei Murill - Hongyu Li; Lijia Zhang; Zhengfeng Fang; Hong Chen; Bin Hu; Wenjuan Wu; Yuntao Liu; Zhen Zeng (Food Chemistry, 2026)

A multifunctional role of sodium decanoate: Preventing thermal aggregation and enhancing foaming properties of enzymatically hydrolyzed egg white protein - Xingyu Li; Yuting Du; Zahra Batool; Guofeng Jin; Rana Muhammad Aadil; Fang Geng; Jinqiu Wang; Gan Hu (Food Hydrocolloids, 2026)

Calcium and high pressure regulation of 7S/11S pea globulin gel structure for simulating egg pudding texture - Jiajia Zhao; Xueyan Wang; Xin Yuan; Minjie Liao; Jiahao Li; Lingjun Ma; Fang Chen; Xiaosong Hu; Junfu Ji (Food Hydrocolloids, 2026)

A strength criterion for sand considering the anisotropy of the spatial distribution of particles and voids - Fenghui Hu; Xiangwei Fang; Chunni Shen; Zhenghan Chen; Chengsheng Wang; Haibin Li (Computers and Geotechnics, 2026)

Enhanced uranium (VI) removal in aqueous solutions via synergistic adsorption-reduction by phytic acid-modified MXene supported nZVI - Huaichang Yu; Mengqi Ma; Sisi Chu; Juanjuan Jiang; Linshan Fang; Tingting Sheng; Xiaoyu Li; Chuhan Qiu; Baowei Hu; Sen Yang (Chemical Engineering Journal, 2026)

Interface passivation with 1,3-propyldiammonium diiodide enables production-line compatible perovskite/silicon tandem solar cells - Dongyong Fan; Longhao Jisi; Wenfeng Zhang; Xin Hu; Fang Wen; Wei Long; Yuchao Hu; Yifeng Zhang; Guoqiang Xing; Liping Su; Haijin Li; Wenhua Zhang; et al. (Chemical Engineering Journal, 2026)

Species identity outweighs richness in shaping soil microbial resource limitation in subtropical mixed Pinus massoniana-broadleaved plantations - Yi Li; Xi Fang; Wenhua Xiang; Pifeng Lei; Liang Chen; Shuai Ouyang; Xiangwen Deng; Yanting Hu; Huili Wu (CATENA, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Identification of a novel stripe rust resistance locus in a Chinese wheat landrace by bulked segregant analysis of recombinant inbred lines combined with the 660 K SNP array - Liuyang Shang; Suyu Li; Yuqin Li; Fang Wang; Shutao Chen; Kanghui Zeng; Yanling Hu; Yinghui Li; Zhenzhen Wei; Lianquan Zhang; Guoyue Chen; Bihua Wu; et al. (Euphytica, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The human-AI empathy loop: a path toward stronger human-AI relationships - Ruolei Gu; Yuqing Zhou; Suchen Yao; Yuan Zhou; Fang Cui; Frank Krueger; Grit Hein; Li Hu (Science Bulletin, 2026)

Dynamic optimization method of production scheme for subsea production system integrated changing factors - Tongming Liu; Guijie Liu; Gongbo Li; Bo Hu; Xin Fang; Guanghao Li (Ocean Engineering, 2026)

Metagenomics insights into functional adaption of the carbon-cycling microbial profiles to long-term fertilization regimes - Hairui FANG; Junjie LIU; Yu JIANG; Xueli CHEN; Zhuxiu LIU; Haidong GU; Xiaojing HU; Zhenhua YU; Yansheng LI; Jian JIN; Xiaobing LIU; Guanghua WANG (Pedosphere, 2026)

Rapid prediction of cellulose, hemicellulose, and lignin content in biomass using FTIR based on transfer learning - Junmeng Li; Dezhi Chen; Zhou Fang; Xing Hu; Xiaochuan Chen; Jun Xu; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Journal of Cleaner Production, 2026)

Different polyphenols improve the gel properties by altering the crystal density of short- and long-chain acyl triacylglycerols oleogels - Fang Hu; Yingying Zhang; Jialing Long; Dayang Zhu; Zhenyu Yu; Mingming Zheng; Yibin Zhou; Shiyi Li (Food Chemistry, 2026)

Integrated analysis of DNA methylome and transcriptome reveals key regulatory genes and immune pathways in Opsariichthys bidens against Aeromonas veronii infection - Wenbin Fang; Jiazheng Ye; Zilong Wu; Yanhong Li; Wanqing Tong; Minghao Hu; Qianhui Li; Zihang Wu; Shanjian Zheng (Fish & Shellfish Immunology, 2026)

Associations between residential greenness, depressive symptoms, and sleep quality among college students in China - Chunliang Wang; Chunhui Yang; Kun Yuan; Ruitong Zhang; Qing Li; Linmin Hu; Xinjie Dai; Xixian Fang; Runhua Zhou; Yuyan Zhou; Ningrui Liu; Jianbang Xiang (Environmental Research, 2026)

A generic monomer confined strategy for defective UiO-66 synthesis towards enhanced aqueous phosphate removal - Chengcheng Ji; Shaogang Hu; Yifan Bu; Kexin Yi; Chao Li; Shaodong Xie; Shuyan Yu; Fang Zhang; Wulin Yang (Chemical Engineering Journal, 2026)

The intrinsic mechanism of anaerobic degradation of leachate and control of antibiotic resistance gene migration in a microbial electrolysis cell with intermittent power supply enhanced by magnetic biochar - Qiaona Xie; Zijie Yu; Zhenxiang Li; Di Wu; Hongyuan Liu; Yuyang Long; Lifang Hu; Chengran Fang (Chemical Engineering Journal, 2026)

Porous microsphere-based one-stop repair platform mobilizes endogenous mesenchymal stem cells and recapitulates hypoxic metabolism for cartilage regeneration - Yingkun Hu; Shuhao Yang; Yan Fang; Zhenghao Xu; Jianye Yang; Qinyang Zhang; Chengqiang Zhou; Xulin Hu; Ning Hu; Li Chen (Chemical Engineering Journal, 2026)

Advance in the characteristics, bioactivities, and drug delivery application of chitosan and its derivatives for osteoarthritis: A review - Ruiyuan Zhang; Li Yang; Lin Li; Haiyan Huang; Yao Song; Yicheng Lei; Yuan Hu; Shiyin Chen; Fang Liu (Carbohydrate Polymers, 2026)

Multifaceted Role of RIMBP2 in Promoting Hearing in Murine Cochlear Hair Cells - Menghui Liao; Xin Chen; Ling Lu; Qing Liu; Rongrong Guo; Yuyang Qiu; Yangnan Hu; Yuhua Zhang; Qiaojun Fang; Panpan Zhang; Yige Li; Shuijin He; et al. (Neuroscience Bulletin, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Extraction of camptothecin and 10-hydroxycamptothecin from Camptotheca acuminata fruits by natural deep eutectic solvent - Beibei Fang; Qing Liu; Chengli Yang; Kaixuan Liu; Guanya He; Xuchun Zhai; Kaishun Hu; Zulekha; Dali Li (Natural Product Research, 2026)

From parasitic to productive: Leveraging ORR-generated alkalinity for electrochemical lithium recovery via Ti3C2Tx/Li4Ti5O12 microenvironment design - Dezhi Fang; Xueli Zhang; Feng Liu; Sile Hu; Peng Lin; Bowen Li; Peng Zhang; Kexun Li (Water Research, 2026)

Central-eastern China's chloroform emissions during 2021–2024 inferred from high-frequency in-situ atmospheric measurements and industrial sampling - Bowei Li; Runze Zhu; Jiahuan Huang; Xiaoyi Hu; Qianna Du; Ruoqian Wang; Xuekun Fang (Science of The Total Environment, 2026)

Bio-inspired cracked metal-phenolic networks with durable confinement capillarity and photocatalysis for highly efficient evaporation and water remediation - Min Hu; Yuting Li; Kuiyan Zhan; Cunyu Song; Fang He; Yuexiang Li; Zhenxing Wang (Science Bulletin, 2026)

AhNHL24 enhances peanut resistance to bacterial wilt and stem rot via glutathione and phenylpropanoid pathways - Mengtian Hou; Hao Li; Zenghui Cao; Fang Wang; Sasa Hu; Yanzhe Li; Qian Ma; Yaoyao Li; Yi Fan; Kai Zhao; Kunkun Zhao; Ding Qiu; et al. (Plant Science, 2026)

Quantitative prediction of fracture distribution in deep conglomerate reservoirs of the Bozhong 19-6 South structure, offshore Bohai Bay Basin, East China: Insights from numerical simulation of multiphase strike-slip regimes - Liang Zhou; Chao Deng; Li-ya Da; Yu Xia; He-wei Hu; Kai Ji; Chang-yu Fan; Yong Cheng; Yu-jie Ning; Xiao-fang Yang (Marine and Petroleum Geology, 2026)

Emissions of fully fluorinated greenhouse gases in central-eastern China inferred from atmospheric observations - Qianna Du; Xiaoyi Hu; Runze Zhu; Zifa Wang; Bowei Li; Liting Hu; Zhouxiang Cai; Mingrui Ji; Jingtao Xu; Haibo Yu; Yunxing Hu; Bo Yao; et al. (Journal of Environmental Management, 2026)

Zinc-chlorogenic acid network-induced tomato seed protein gels: Fabrication, characterization, and application in a plant-based food - Jiahao Li; Wenjia Wang; Xin Yuan; Fang Chen; Xiaosong Hu; Lingjun Ma; Junfu Ji (Food Research International, 2026)

Establishment of a new intestinal cell line of the grouper (Cephalopholis sonnerati) and immune response to Vibrio harveyi infection - Chaowei Li; Chongwei Wang; Shuang Liu; Fei Fang; Bo Zhou; Qiaomu Hu; Caiyun Sun; Yong Zhang; Songlin Chen (Fish & Shellfish Immunology, 2026)

Associations of outdoor artificial light at night exposure with telomere length and mitochondrial DNA copy number in children and adolescents: Examining sex-specific associations - Gaojie Fan; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; Liqin Hu; Xiaoning Lei; Youjie Wang; Mingyang Wu; et al. (Environmental Research, 2026)

Accurate prediction and screening of Ni-based bimetallic catalysts for hydrogen production from biogas reforming: An interpretable machine learning study - Wen-ming Zhang; Bin Hu; Bo-yuan Zheng; Ji Liu; Qi Niu; Kai Li; Zhi-mo Fang; Bing Zhang; Qiang Lu (Chemical Engineering Journal, 2026)

Cigarette smoke exposure diminishes ovarian reserve in mice by regulating granulosa cells redox homeostasis imbalance through Wnt10b-ERβ feedback loop - Fang Li; Mengting Xu; Yanhui Zhao; Ying Wang; Nengyin Hu; Sailing Ji; Jianing Miao; Li Wang; Lili Wang (Chemico-Biological Interactions, 2026)

Production and Functional Evaluation of Recombinant Active Peptide RH in Pichia Pastoris: Protection Against Escherichia Coli Induced Cell Death - Lu Zhao; Mingyang Hu; Yuwen Li; Jiaoyu Xin; Yuxin Fang; Chenyu Xue; Na Dong (Probiotics and Antimicrobial Proteins, 2026)

Polysaccharides, saponins and flavonoids in Astragali Radix: a review of phytochemistry and pharmacology for future therapeutic applications - Xiaolin Huang; Ziyuan Guo; Zihan Wang; Chen Ma; Li Dong; Xiaosong Hu; Fang Chen; Yinghua Luo; Daotong Li (Phytochemistry Reviews, 2026)

Upregulation of the Mitophagy-Related Gene EXOSC4 Is Associated with Immune Dysregulation in Spinal Cord Injury - Xiaoqin Liu; MengFan Li; Jiating Hu; PanFeng Fang; Yuxin Ma; Ziyu Guo; Hongqiang Wang; Chao Xu (Molecular Neurobiology, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

SIRT3/AMPK-Driven Mitophagy Failure Underlies Methylmercury-Induced Neurotoxicity: Evidence from Humans to Cells - Jiahuan Hu; Li Zhang; Fang Chen; Changsong Tian; Aihua Zhang; Wenjuan Wang (Molecular Neurobiology, 2026)

Target Fibroblast-B cell crosstalk via MIF signaling drives pathogenic B cell differentiation and joint damage in knee osteoarthritis - Bizhi Tu; Zheng Zhu; Yan Li; Zhengming Zhu; Shijie Wang; Peizhi Lu; Ya Li; Shuo Yang; Dingtao Hu; Run Fang; Rende Ning (Inflammation Research, 2025)

Feeding behavior recognition of group-housed pigs based on pose estimation and keypoint features discrimination - Yuhang Hu; Xin Dai; Baisheng Dai; Ran Li; Junlong Fang; Yanling Yin; Honggui Liu; Weizheng Shen (Computers and Electronics in Agriculture, 2025)

The combined effects of aging polylactic acid microplastics and TCPP on the byssus genes of the mussel Mytilus coruscus - Li’ang Li; Dan Hu; Zhen Zhong; James Kar-Hei Fang; Menghong Hu; Yueyong Shang; Youji Wang (Marine Pollution Bulletin, 2025)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Biomass electrooxidation-involved carbon radicals boost electrochemiluminescence - Qie Fang; Lin Xu; Lijin Wang; Jingshuai Li; Yan Zhou; Yifei Chen; Wenxuan Jiang; Liuyong Hu; Wenling Gu; Chengzhou Zhu (Science Bulletin, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Adipokinetic hormone receptor is required for larval food intake and development of Plutella xylostella - Qiu-Li Hou; Mei Fang; Jia-Ni Zhu; Donal M. O’Sullivan; Er-Hu Chen (Journal of Insect Physiology, 2025)

Detecting soluble solids content of individual berries using image depth correction in hyperspectral imaging of grape clusters - Haoling Liu; Kekun Zhang; Miao Lu; Yihang Li; Shijie Tian; Jin Hu; Yulin Fang (Food Control, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Design of Ni-MOF@biochar heterostructures via ligand-induced distortion for highly selective N2H4 sensing - Bo Ran; Ping Hu; Jun Sun; Jialu Fang; Yan Li; Qihua Sun; Zhizhong Zhang; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Buried interface engineering for efficient and stable inverted perovskite solar cells - Li Pan; Runze Yu; Zhu Fang; Bin Chen; Liya Zheng; Runxin Hu; Gang Chen (Chemical Engineering Journal, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Electrostatic and functional group-mediated biosorption of microalgae and lead using biosafe Aspergillus oryzae 3.042 fungal pellets - Feili Li; Shiyu Chen; Yijie Lin; Jingjing Fang; Wen Shi; Junjie Qian; Gaoxiang Zhang; Jun Hu (Bioresource Technology, 2025)

Emission estimates of ozone-depleting hydrochlorofluorocarbons for China inferred from new observations and inverse modeling - Ye Chen; Xiaoyi Hu; Kuang Xiao; Xiao Zhang; Mingzhu Li; Tong Ye; Bowei Li; Mingrui Ji; Bo Yao; Haibo Yu; Xuekun Fang; Li Tan; et al. (Atmospheric Environment, 2025)

Cell-supporting cytoskeletons and phagocytic acquisition of compatible solutes emerge as common strategies for high-salt adaptation in different ciliates - Fengchao Li; Wenying Zhang; Shuai Luo; Ning Ma; Jing Zhang; Weiwei Qin; Che Hu; Xinxin Gao; Yuan Xiao; Chuanqi Jiang; Xiaocui Chai; Qiukun Wang; et al. (Science China Life Sciences, 2025)

The nutritional value, application status and challenges of Houttuynia cordata Thunb (H. cordata) - Xiaolin Huang; Peng Yu; Yinghua Luo; Ziyuan Guo; Zihan Wang; Chen Ma; Li Dong; Peng Luo; Guoze Wang; Xiaosong Hu; Fang Chen; Hao Guo; et al. (Phytochemistry Reviews, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

MOF promotes cisplatin resistance in lung cancer cells by enhancing WSTF acetylation - Qian Sui; Dongsheng Lin; Fang Huang; Haijian Hu; Xiaohui Liu; Zheng Li; Jiheng Liu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Comparative analysis of the WRKY gene family between Chimonanthus praecox and C. salicifolius - Wei Zou; Gui-Ting Hu; Fang-Fang Gui; Xin-Chen He; Priyanka Borah; Li Zhu; Hui-Juan Ning; Li-Yuan Yang (Genetica, 2025)

Unveiling the symbiotic effect of trade-embodied carbon: An examination of China’s interactions with Pacific Rim countries - Wei Hu; Xiangyun Fang; Jinfu Fang; Jianzhen Zhang; Feng Yang; Cansong Li; Ziran Jiang; Kun Hou; Yanming Zhang (Journal of Geographical Sciences, 2025)

CPT1A facilitated ferroptosis by forming feedback loop with Nrf2 via PI3K/AKT pathway in colorectal cancer - Xiao-huan Li; Feng Lv; Si-qi Li; Hao-wei Deng; Li-ping Tang; Ke-zhi Li; Li-ye Xie; Bang-li Hu; Shu-fang Ning (Apoptosis, 2025)

Synergistic effects of elevation loss and environmental extremes trigger salt marsh die-off in the Yangtze Estuary - Yang Hu; Lv Gong; Yuanhao Song; Tianyou Li; Wenzhen Zhao; Xianye Wang; Shubo Fang; Xiuzhen Li (Ocean & Coastal Management, 2025)

Constitutive androstane receptor activation modulates YAP expression and activity through ubiquitination and sumoylation - Fengting Liang; Shuaishuai Zhang; Wenhong Zhou; Guofang Bi; Xiao Yang; Peng Wang; Shicheng Fan; Shuang Hu; Chenghua Wu; Xiaowen Jiang; Dan Li; Hui Ouyang; et al. (Toxicology Letters, 2025)

Deep-sea ventilation shifts and glacial climate evolution: redox history of the central Philippine Sea over 6.7 Myr - Liang Yi; Yibing Li; Sheng Xu; Bangqi Hu; Martín Medina-Elizalde; Xue Ding; Yeqiang Shu; Pavel Mikhailik; Panfeng Li; Congxi Fang; Yonghang Xu; Haifeng Wang; et al. (Quaternary Science Reviews, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

The influence of different antioxidants on the properties of diacylglycerol based oleogels - Fang Hu; Liwen Zhang; Daoyu Ding; Suyuan Zhao; Jialing Long; Mingming Zheng; Shiyi Li (Food Research International, 2025)

A review on the chemical composition, biological activity, and potential health benefits applications of Longan (Dimocarpus longan Lour.) - Yan Hu; Xiaoying Zhang; Daotong Li; Chen Ma; Li Dong; Yinghua Luo; Xiaosong Hu; Fang Chen (Food Chemistry, 2025)

Simultaneous quantitative point-of-care detection of nucleic acid and protein biomarkers for acute myocardial infarction using bright aggregation-induced emission nanoparticles - Yue Cao; Peng Li; Zhiwei Guo; Yuhang Yang; Kuangrou Jia; Zihao Xu; Banglao Xu; Guanfeng Lin; Fang Hu; Zhenhua Chen; YingSong Wu (Chemical Engineering Journal, 2025)

Stable and efficient n-type perylene diimides radical as cathode interlayer with wide thickness tolerance for organic solar cells - Lin Hu; Senmei Lan; Guobin Shen; Fang Wang; Yingzhi Jin; Zhen Su; Jia Yao; Mengzhen Du; Zheng Yan; Wei Li; Dan Zhou; Erjun Zhou; et al. (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Ternary synergistic organic hole transport materials for inverted perovskite solar cells - Zijun Ma; Yue Gao; Qiaoyun Chen; Xinyu Yu; Junjie Zhou; Xiwei Liao; Chenyang Li; Xuemei Lai; Tingxing Hu; Xiang Fang; Jun Jiang; Mingfu Ye; et al. (Chemical Engineering Journal, 2025)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Fatigue Behavior of Rock Salt under Primary Creep Effect at Various Temperatures with Acoustic Emission Monitoring - Hang Li; Hongling Ma; Zhiwen Hu; Zhen Zeng; Jiangyu Fang; Rui Liang; Chunhe Yang (Rock Mechanics and Rock Engineering, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Efficient separation of impurities from pyrolusite and the enhancement of its products for improving the performance of lithium-ion batteries - Riran Zang; Houyang Chen; Shuxian Shi; Man mo; Dawei Lan; Guangliang Zhang; Yangxian Huang; Kunsong Hu; Xinghua Liang; Lingxiao Lan; Yong Yang; Junji Li; et al. (Chemosphere, 2025)

Unraveling the biofilm armor: How ROS drives biofilm formation in aquatic pathogen Edwardsiella piscicida - Qingjian Fang; Yin Gou; Hanjie Gu; Qingjuan Wu; Jiaojiao He; Chenghua Li; Bin Sun; Yonghua Hu (Aquaculture, 2025)

Multivariate explainable machine learning assists in redefining high-performance phosphate removal by layered double hydroxides - Peng Zhang; Yafei Li; Silu Huo; Peng Lin; Dezhi Fang; Sile Hu; Bowen Li; Zikang Xu; Xinyuan Qiu; Kexun Li; Hao Wang (Water Research, 2025)

Fusaritricins E–G, three new polyketides, isolated from the endophytic fungus Fusarium sp. HC20 and their antifungal activities - Xu-Ri Wan; Chang Li; Ling-Yan Liu; Fang Yue; Xuan Lu; Yue-Hu Pei; Yi-Hui Yang (Phytochemistry Letters, 2025)

Human flood adaptation characteristics: A comparative study of three global river deltas - Shupu Wu; Yang Hu; Wenzhen Zhao; Lv Gong; Yuanhao Song; Chenghong Li; Xiuzhen Li; Md.Jaker Hossain; Xinmeng Shan; Jiayi Fang; Jie Yin; Weiguo Zhang; et al. (Journal of Hydrology, 2025)

Antibiotic-induced perturbations in C–N metabolic networks, and associated gene pathways in soybean (Glycine max) seedlings - Jie Feng; Zhiheng Li; Qianqian Liu; Yuye Hu; Zikang Ye; Jinyi He; Zhiguo Fang; Lidan Wu; Kaiming Cheng; Huijun Liu (Journal of Hazardous Materials, 2025)

Cooperative effects of Mn4+–Olattice and Cu+–Ovacancy–Mn3+ sites during low-temperature oxidation of CO over LaMn1-yCuyO3-δ perovskite - Xu Duan; Jian Yang; Hongbin Li; Jiaqing Zhu; Runxue Liu; Yujie Fang; Huan Li; Guang Hu; Jiangling Li; Qingcai Liu (Journal of Environmental Chemical Engineering, 2025)

Comparative advantages of biogenic sulfur over chemical elemental sulfur as electron donors in sulfur-driven autotrophic denitrification: Denitrification performance, sludge characteristics and microbial responses - Jiali Fang; Yan Wang; Bingzheng Wang; Haoxing Hu; Ziheng Feng; Huiyun Zhong; Ji Li (Journal of Environmental Chemical Engineering, 2025)

Chalcophile elements in post-subduction magmas and implications for metal recycling in oceanic and continental subduction - Xiang Wang; Zaicong Wang; Li-Qun Dai; Wen Zhang; Xiaodong Deng; Xi Zhang; Stephen Foley; Charles H. Langmuir; Wei Fang; Lang Wang; Tao He; Aiqing Ren; et al. (Geochimica et Cosmochimica Acta, 2025)

Coal gasification-combustion system − Part I: Principle and nitrogen migration characteristics - Shaobo Yang; Qiangqiang Ren; Shaobo Han; Ruifang Cui; Yujie Hu; Yuqian Heng; Shilong Dong; Linxuan Li; Mengyin Gong; Chen Liang; Shuai Guo; Neng Fang; et al. (Fuel, 2025)

Aroma characteristics and adaptability of Goji (Lycium barbarum L.) leaf tea prepared from 25 different Goji lines - Mengcong Zhang; Li Lu; Xiaowen Hu; Chengzhe Zhou; Cheng Zhang; Jiaxin Fang; Linyuan Duan; Bo Zhang; Yuqiong Guo (Food Chemistry, 2025)

The effect of uracil on the freeze-drying survival rate of Lactiplantibacillus plantarum YR07 based on transcriptome analysis - Sha-sha Zheng; Wen-di Zhang; Li-jun Tan; Li-fang Zou; Ying-ying Hu; Liu Yang; Bao-cai Xu (Food Microbiology, 2025)

Atmosphere-based estimations of CO2 emissions at city and county scales and comparative analysis: a case study in Yangtze River Delta Urban Agglomerations (YRDUA) - Zhouxiang Cai; Liting Hu; Di Chen; Mengyue Ma; Qingquan Hu; Haibo Zhou; Hanwei Chen; Dan Yang; Yun Li; Xuekun Fang (Environmental Research, 2025)

Self-healing and thickness-insensitive perylene diimide-based cathode interfacial layers for organic solar cells - Wei Chen; Dan Zhou; Lin Hu; Jiangang Ma; Guobin Shen; Wentian Wan; Shuhua Wang; Fang Wang; Ruizhi Lv; Bin Hu; Haitao Xu; Zaifang Li; et al. (Chemical Engineering Journal, 2025)

Structural stabilization via strontium doping in LiMn2O4 enables selective lithium capture from high-mg brines by rocking-chair capacitive deionization - Dezhi Fang; Xueli Zhang; Feng Liu; Sile Hu; Peng Zhang; Kexun Li (Chemical Engineering Journal, 2025)

Targeted membrane permeability alterations in Enterobacter hormaechei ZS01 for high-level production of 3-succinyl-pyridine from the tobacco waste - Sheng Lei; Xia Fang; Wenwei Li; Lingchao Zhu; Xianyi Li; Cenming Zhu; Li Gao; Ruilin Hu; Dan Wang; Yanqing Duan (World Journal of Microbiology and Biotechnology, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

Antifungal cytochalasans from the co-culture of two endophytic fungi Aspergillus spelaeus and Xylaria sp - Xian-Hua He; Ye-Fang Hu; Hua-Chun Feng; Li-Qi Liang; Lan-Fang Zou; Qian Wu; Min Liang; Jun Li; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2025)

Combined effects of polyamide microplastics and the pathogenic bacterium Vibrio parahaemolyticus on the immune parameters of Mytilus coruscus - Yiting Pan; Zhiyuan Yang; Wenxin Zhao; James Kar-Hei Fang; Jianhang Shi; Daoji Li; Menghong Hu; Youji Wang (Marine Pollution Bulletin, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Combined toxicity of polyethylene microplastics and soil salinization to earthworms is generally antagonistic or additive - Zheng Fang; Mark E Hodson; Chao-Jian Hu; Wen-Jun Li; Jun Li; Alejandra Bouzas Monroy; Lei Tong; Xiao Xiao (Journal of Hazardous Materials, 2025)

Functional oleogels constructed by short- and long-chain acyl triacylglycerols: Characterization and in vitro simulated digestion - Fang Hu; Liwen Zhang; Yan Zhu; Suyuan Zhao; Wei Xu; Zhenyu Yu; Mingming Zheng; Yibin Zhou; Shiyi Li (Food Chemistry, 2025)

Multifunction hydrogen-bonded organic framework aerogel platform for detection and removal of heavy metal ions in pear juice - Chunhua Li; Xieyang Zhang; Deshui Li; Guanqun Luan; Xiaoyu Hu; Zhilei Zhao; Lide Fang (Food Chemistry, 2025)

Piceatannol, a catechol analog of resveratrol, is more effective in improving glucose metabolism disorders - Ruilu Sun; Wei Li; Minjie Liao; Yiran Yu; Yao Mou; Junfu Ji; Fang Chen; Xiaosong Hu; Lingjun Ma (Food Bioscience, 2025)

Quantitative assessment of heat tolerance in new rice varieties through field survey during natural extreme heat events - Ting Sun; Tianhui Miao; Jianan Hu; Haoyang Zhou; Minglu Li; Jiayi Zhang; Yuanyuan Pan; Ran Bi; Shenghao Ye; Menglei Wei; Zeyu Wu; Guoqiang Li; et al. (European Journal of Agronomy, 2025)

Efficient zinc extraction from industrial wastewater with novel phenyl phosphate for saline wastewater net-zero emission - Shuai Li; Jianguang Yang; Hong Liu; Jia Ning; Bo Han; Shenghai Yang; Hai Yu; Fang Hu; Hongliang Zhang; Yongming Chen (Desalination, 2025)

Two-pathways photocatalytic production of H2 over ZnIn2S4 coupled NH2-MIL-101 (Fe) loaded with polyoxometalate - Junhao Wu; Xu Yang; Bonan Li; Xiao Fang; Weize Sun; Tao Su; Pengfei Feng; Khalid Umer; Yingying Hu; Yong Ding (Chemical Engineering Journal, 2025)

CO2 absorption kinetics and species analysis of DMEDA water-lean absorbents - Zhilv Chen; Chaoming Jian; Chao Li; Tao Wang; Qinhui Wang; Mengxiang Fang; Fanpeng Meng; Wei Chen; Yongsheng An; Ximing Hu (Chemical Engineering Journal, 2025)

Screening of Antibiotic-Sensitive Lactic Acid Bacteria (LAB) Associated with the Gut of Penaeus Vannamei and its Application in Shrimp Farming - Yiwen Gu; Xiu Lin; Yanxu Lu; Shuguang Fang; Kun Hu; Xin Ju; Liangzhi Li; Zhi Chen (Current Microbiology, 2025)

“Excavation-freezing-thawing” failure and crack characteristics of open-pit slope in cold regions: a case study in Baorixile mine, Hulunbeir, China - Guanghe Li; Zihuan Hu; Yanting Wang; Dong Wang; Laigui Wang; Zhigang Tao; Xiaoxu Yang; Yongzhi Du; Zhiwei Zhou; Chunjian Ding; Kun Fang (Bulletin of Engineering Geology and the Environment, 2025)

Shewanella mytili sp. nov., a novel bacterial species isolated from the intestinal tract of Mytilus edulis in the South China Sea - Suyun Fang; Jun Min; Haikun Zhang; Yan Li; Xingyue Lin; Xiaoke Hu (Antonie van Leeuwenhoek, 2025)

Cognitive reserve mitigates cognitive impairment in cerebral small vessel disease by protecting white matter fibers: an automated fiber quantification study - Mingyu Li; Yachen Shi; Lin Ma; Haixia Mao; Min Xu; Qianqian Gao; Jiayi Yang; Feng Wang; Xiangming Fang; Xiaoyun Hu (Brain Imaging and Behavior, 2025)

Pharmacokinetic study of Vibrio parahaemolyticus phage Фvp140 in Litopenaeus vannamei following oral administration - Di Fang; Laizhuang Jin; Qianhui Song; Xiong Zou; Lei Feng; Letian Li; Hui Zhang; Kun Hu; Mao Lin; Wenhong Fang (Aquaculture, 2025)

Unveiling the prevalence of metal resistance genes and their associations with antibiotic resistance genes in heavy metal-contaminated rivers - Fang-Zhou Gao; Li-Xin Hu; You-Sheng Liu; Hai-Yan Yang; Liang-Ying He; Hong Bai; Feng Liu; Xiao-Wei Jin; Guang-Guo Ying (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Viral insights into the acidification of sulfidic mine tailings - Xikai Su; Jun Liu; Licao Chang; Wenzhe Hu; Yun Fang; Jintian Li; Linan Huang; Wensheng Shu; Hailiang Dong (Journal of Hazardous Materials, 2025)

Prenatal exposure to PM2.5 constituents and newborn leukocyte telomere length in a prospective study: Windows of susceptibility and modification by maternal folic acid supplementation - Gaojie Fan; Qing Liu; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; Liqin Hu; Chao Xiong; Zhongqiang Cao; et al. (Journal of Hazardous Materials, 2025)

Hexavalent chromium and cellular senescence: A comprehensive analysis from chromate-exposed occupational population and chromate-inhaled mouse model - Zhiqiang Ji; Yali Zhang; Guiping Hu; Shiyi Hong; Zekang Su; Qiaojian Zhang; Li Wang; Tiancheng Wang; Shanfa Yu; Qian Bu; Fang Yuan; Xiaojun Zhu; et al. (Journal of Hazardous Materials, 2025)

Zircon U Pb geochronology and geochemistry of ore-bearing rhyolites in the Fuxingtun Ag–Pb–Zn deposit, Great Xing'an Range, NE China: Constraints on petrogenesis and tectonic setting - Shanming Zhang; Xiangguo Guo; Haijun Li; Genhou Wang; Lixin Fan; Erhong Hu; Fukang Fang; Junyi Zi; Minghao Wang (Journal of Geochemical Exploration, 2025)

Efficient prediction of gaseous n-hexane removal in two-phase partitioning bioreactors with silicone oil based on the mechanism and kinetic models - Lichao Lu; Tuo Ju; Yangdan Fang; Jingtao Hu; Zhuqiu Sun; Zhuowei Cheng; Qian Li; Jianmeng Chen; Dong-zhi Chen (Journal of Environmental Sciences, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Wet oxidation of NO with NaClO2 in alkaline conditions: effects of acidic components in flue gas - Huasheng Wang; Shuang Deng; Hongyun Hu; Can Fang; Guangqian Luo; Ze Wang; Songgeng Li (Environmental Research, 2025)

Isolation and Application of Manganese-Oxidizing Bacteria in Mining Areas: Bioremediation of Manganese and Other Heavy Metals in Acidic Wastewater from Uranium Mines - Boyuan Zheng; Hongyang Xia; Xu Zhao; Yi Guo; Jianming Li; Haotong Guo; Wenjie Hu; Jinming Hu; Hongqiang Wang; Fang Hu; Zhiwu Lei; Qingliang Wang (Water, Air, & Soil Pollution, 2025)

Olfactory GnRH3 crypt sensory neurons transduce sex pheromone signals to induce male courtship behavior in zebrafish - Xuefan Cui; Lu Chen; Binbin Tao; Xiya Zhang; Yanlong Song; Ji Chen; Ming Duan; Weiwei Li; Kuangxin Chen; Yang Pei; Xuerui Hu; Ke Feng; et al. (Science China Life Sciences, 2025)

A theory of multi-spheric interaction-driven hydrocarbon formation and enrichment - Rixiang Zhu; Wang Zhang; Huajian Wang; Jilei Li; Qingyang Hu; Liang Zhao; Xiaomei Wang; Shuichang Zhang; Fang Hao; Zhijun Jin (Science China Earth Sciences, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Microbial mediation of soil organic carbon fractions and its feedback to long-term climate change - Xinqi SiMa; Rui Fang; Zhenhua Yu; Yansheng Li; Xiaojing Hu; Haidong Gu; Caixian Tang; Judong Liu; Junjie Liu; Xiaobing Liu; Guanghua Wang; Ashley Franks; et al. (Plant and Soil, 2025)

Identification and validation of oxidative stress-related diagnostic markers for recurrent pregnancy loss: insights from machine learning and molecular analysis - Hui Hu; Li Yu; Yating Cheng; Yao Xiong; Daoxi Qi; Boyu Li; Xiaokang Zhang; Fang Zheng (Molecular Diversity, 2025)

Insight into unloading and geostress characteristics of high slopes based on valley evolution: a case study in Luding county, China - Hongfu Zhou; Shuwu Li; Fan Yang; Tian Fang; Rui Li; Jingyi Xue; Jinpeng Hu; Jiang Xing (Bulletin of Engineering Geology and the Environment, 2025)

Seasonal variations in feeding ecology and mercury contamination of golden cuttlefish (Sepia esculenta) in the coastal waters of China - Zhenfang Zhao; Haoran Li; Xiaoting Jiang; Zhou Fang; Guanyu Hu (Marine Pollution Bulletin, 2025)

A specific energy and penetration interaction-based method for optimizing TBM operational parameters in hard rock - Lei She; Cheng-cheng Hu; Yan-long Li; Dong-feng Li; Zhao-Yu Li; Tao Fang; Ji-guang Zheng (Tunnelling and Underground Space Technology, 2025)

Intrinsic ion migration-induced susceptible two-dimensional phase-transition memristor with ultralow power consumption - Lanhao Qin; Yimeng Yu; Cheng Fang; Yujie Liu; Kaichen Zhu; Decai Ouyang; Shenghong Liu; Bailing Song; Ruochen Zhou; Mario Lanza; Wenhua Hu; Jinsong Wu; et al. (Science Bulletin, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Arsenic mobilization by Bathyarchaeia in subsurface sediments at the Jianghan Plain, China - Zhou Jiang; Wenjie Fang; Yongguang Jiang; Yidan Hu; Yiran Dong; Ping Li; Liang Shi (Journal of Hazardous Materials, 2025)

Pea isolate protein/β-cyclodextrin/CQDs microcapsules improve stability and in vitro sustained release of fish oil - Wenyuchu Chen; Fang Tian; Yongjing Xu; Yujin Li; Weiliang Guan; Chenyang Lu; Sheng Hu; Luyun Cai (Food Bioscience, 2025)

Identification of key feature variables and prediction of harmful algal blooms in a water diversion lake based on interpretable machine learning - Yundong Wu; Bo Xian; Xiaowei Xiang; Fang Fang; Fuhao Chu; Xingkang Deng; Qing Hu; Xiuqiong Sun; Wei Tang; Shaopan Bao; Genbao Li; Tao Fang (Environmental Research, 2025)

Performance of photovoltaic thermal–ground source heat pump with a phase change water tank - Fang Wang; Mengwei Liu; Songtao Hu; Wenliang Guo; Xianfei Liu; Ye Tian; Jun Zhang; Chaowen Deng; Jicheng Li (Energy and Buildings, 2025)

Indoor use of consumer chemical products and its link to depression and anxiety among college students in 297 chinese cities - Kai Su; Chunliang Wang; Linmin Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Qing Li; Runhua Zhou; Zan Lu; Dingwen Li; Yating Xie; et al. (Building and Environment, 2025)

Formation and evolution of overpressure and its control on hydrocarbon accumulation in the Yinggehai Basin - Lu Yang; Lin Hu; Gaowei Hu; Yazhen Zhang; Jinqiang Tian; Fang Hao; Zonglin He; Yue Xue; Xuezhe Li; Ziqi Feng; Chunlei Li; Baibing Yang (Science China Earth Sciences, 2025)

TREM2 Modulates Postoperative Cognitive Function in Aged Mice by Inhibiting the NLRP3/caspase-1 Pathway and Apoptosis via PLCγ2 Activation - Xinyue Zhang; Renyi Wang; Xue Pan; Zitong Chen; Yilong Li; Yue Hu; Fang Liu; Xuezhao Cao (Molecular Neurobiology, 2025)

Application of sourdough in gluten-free bakery products - Hangyan Dan; Hongyu Li; Cheng Li; Zhengfeng Fang; Bin Hu; Hong Chen; Caixia Wang; Saiyan Chen; Teng Hui; Wenjuan Wu; Zhen Zeng; Yuntao Liu (Critical Reviews in Food Science and Nutrition, 2025)

Effects of inescapable waste composition on microplastic release and sulfate reduction in landfill - Ying Hu; Xianghang Li; Dongsheng Shen; Lifang Hu; Chengran Fang; Yuyang Long (Waste Management, 2025)

Bimetallic MOFs@PAN ordered nanofibrous membranes with antibacterial activity for air filtration and personal protective equipment - Xiao Cheng; Enyuan Hu; Haiyun Li; Qiang Liu; Lei Zhao; Cheng Deng; Yanhua Fang; Mengfu Zhu (Journal of Environmental Chemical Engineering, 2025)

Coupled effects between the present-day segment movement rate of the Anninghe active fault zone in Southwest China and fault-induced landslides - Hongfu Zhou; Wenqing Tang; Shuwu Li; Wanlin Liu; Tian Fang; Jingyi Xue; Jinpeng Hu; Jiang Xing (Geomorphology, 2025)

In-situ hydrogen-mediated catalytic transfer hydrogenolysis of Kraft lignin for highly selective production of monomeric phenols - Han-Bing Gao; Bing-Hu Xie; Yue-Lun Wang; Le-Le Qiu; Yun-Peng Zhao; Jian Xiao; Mei Zhong; Jing Liang; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Exposure to green space and leukocyte mitochondrial DNA copy number in children and adolescents - Gaojie Fan; Xiaoning Lei; Qing Liu; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; Liqin Hu; Jing Wei; et al. (Environmental Research, 2025)

Spatial retention, absorption, transport, and enrichment of microplastics in mangrove sediment complex system - Xiuqiong Liang; Chunxiang Liu; Haoyu Wang; Haonan Li; Jin Luo; Gang Luo; Wei Hu; Wenlu Lan; Leishi Wu; Sheng Fang; Yan Tian; Xiang Sun (Environmental Pollution, 2025)

Customized interfacial electronic interactions in protonated g-C3N4/ZnIn2S4 S-scheme 2D/2D edge-to-face heterostructures for boosted CO2 photoconversion - Lei Li; Xinyan Dai; Kangjie Gao; Hangjing Yu; Fang Chen; Wentao Wang; Jiqiang Ning; Yong Hu (Chemical Engineering Journal, 2025)

Stabilizing lithium metal batteries by anion modulated Quasi-Solid polymer electrolytes - Yifeng An; Renyi Li; Chi Fang; Wenchao Hu; Yang Yang; Aijun Li; Dubin Huang; Hsingkai Chu; Song Gao; Yonggang Wang; Jiaxin Zheng; Yatao Liu; et al. (Chemical Engineering Journal, 2025)

Optimizing boron oxide-support interactions for enhanced catalytic stability in propane oxidative dehydrogenation - Jinshu Tian; Kerou Hu; Ling Fang; Chi Wang; Ru Kong; Mingwu Tan; Lili Zhang; Zhongting Hu; Xiaonian Li; Yihan Zhu (Chemical Engineering Journal, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Transcriptomic analysis of wrinkled leaf development of Tai-cai (Brassica rapa var. tai-tsai) and its synthetic allotetraploid via RNA and miRNA sequencing - Xinli Zhang; Wen Zheng; Zhiyu Zhu; Xiaocan Guo; Jinbao Hu; Li’ai Xu; Huihui Fang; Yunshuai Huang; Zhengyan Ling; Zhujun Zhu; Yunxiang Zang; Jianguo Wu (Plant Molecular Biology, 2025)

Propofol Promotes Anesthesia Through the Activation of Centrally-Projecting Edinger–Westphal Nucleus Urocortin 1-Positive Neurons - Jing Huang; Yiwen Hu; Sheng Jing; Fuhai Bai; Zonghong Long; Zhuoxi Wu; Liang Fang; Lei Cao; Youliang Deng; Xiaohang Bao; Hong Li (Neuroscience Bulletin, 2025)

Removal of tetrabromobisphenol A from water by four activated carbons: adsorption performance and implications for engineering practice - M. Wu; J. F. Li; Y. X. Bao; J. M. Hu; Z. G. Cao; J. Fang; P. Li (International Journal of Environmental Science and Technology, 2025)

Effect of Blade Number on Tip Vortex Cavitation of Propeller - Yanan Wang; Yang Xiao; Bin Fang; Wen Li; Chuanzhi Duan; Weipeng Zhang; Jian Hu (Journal of Marine Science and Engineering, 2025)
Tip vortex cavitation not only impacts the hydrodynamic performance of a propeller but also results in vibrations, noise, and erosion. In this study, the effect of blade number on propeller tip vortex cavitation is investigated using computational fluid dynamics (CFD) methods. Numerical simulation is performed regarding four model propellers with blade numbers varying from one to four. These propellers have the same blade geometry as the E779A propeller. Large eddy simulation (LES) and the Schnerr–Sauer cavitation model are used to solve tip vortex cavitation with local mesh refinement according to the spiral tip vortex trajectory. The hydrodynamic performance and tip cavitation of the propellers are solved and analyzed to reveal the fluid mechanism of tip vortex formation. The effect of blade number on wake velocity and wake vorticity is discussed. Numerical analysis showed that the increase in blade number leads to a reduction in the thrust and torque of a single blade, although the total thrust and torque of all blades increased. The present study takes new insights to the suppression of tip vortex cavitation, which benefits propeller design.

The important role of TLR2/MyD88/JNK in regulating the pathogenesis and inflammation induced by pseudorabies virus in mice - Jingyi Niu; Gang Li; Yiyu Liu; Chao Wan; Yixuan Li; Yu Dai; Haixia Hu; Lianci Peng; Rendong Fang; Chao Ye (Veterinary Microbiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Deriving leaf-scale chlorophyll index (CIleaf) from canopy reflectance by correcting for the canopy multiple scattering based on spectral invariant theory - Chenpeng Gu; Jing Li; Qinhuo Liu; Hu Zhang; Alfredo Huete; Hongliang Fang; Liangyun Liu; Faisal Mumtaz; Shangrong Lin; Xiaohan Wang; Yadong Dong; Jing Zhao; et al. (Remote Sensing of Environment, 2025)

Selective activation of dioxygen to singlet oxygen over La-Si co-doped TiO2 microspheres for photocatalytic degradation of formaldehyde - Shuaitao Li; Haodi Liu; Xun Hu; Yanfen Fang; Xiaofeng Cao; Qifeng Chen (Journal of Environmental Sciences, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Recent advances in electrode materials for typical halogen removal via capacitive deionization - Sile Hu; Dezhi Fang; Fukuan Li; Zikang Xu; Kexun Li; Peng Zhang; Weidong Feng (Desalination, 2025)

Two-photon polymerization 3D printing of biomimetic microstructures for functionalizing surfaces to inhibit bacterial growth - Wentao Zhu; Fang-Yi Huo; Lei-Ming Cao; Zi-Zhan Li; Qian Zhu; Rongxiang He; Bolei Chen; Yong Liang; Bo Cai; Hong He; Lin-Lin Bu; Ligang Hu (Chemical Engineering Journal, 2025)

Monitoring the level of hydrogen sulfide in arthritis and its treatment with a novel near-infrared fluorescent probe - Jing-Jing Chao; Ling Hu; Jing-Fang Mi; Guo-Jiang Mao; Fen Xu; Liufang Hu; Juan Ouyang; Chun-Yan Li (Analytica Chimica Acta, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Effect of food addiction of lysine on feeding habit in fish - Hong-Liang Lu; Yun-Liang Miao; Jia-Ming Zou; Zi-Jun Hu; Ying-Cen Li; Xu-Fang Liang; Shan He (Aquaculture, 2025)

Geostationary ocean color satellite observations reveal the fine structure of mesoscale eddy dynamics - Xiaosong Ding; Xianqiang He; Yan Bai; Wentao Ma; Jiajia Li; Feng Ye; Shujie Yu; Qiwei Hu; Fang Gong; Difeng Wang; Teng Li (Remote Sensing of Environment, 2025)

Steel slag enhanced simultaneous nitrogen and phosphorus removal from low C/N wastewater by sulfur-driven autotrophic denitrification - Haoxing Hu; Bingzheng Wang; Jiali Fang; Ziheng Feng; Huiyun Zhong; Ji Li (Journal of Water Process Engineering, 2025)

Innovative synergistic deep dewatering of municipal sludge using coupled piezoelectric materials and mechanical filtration - Binqi Rao; Yulin Li; Yan Zhang; Weilun Ren; Hongbai Jia; Wenbo Huang; Xilong Lu; Peng Xu; Lijiang Hu; Jiadi Lian; Kewei Chen; Fang Zhou (Journal of Environmental Chemical Engineering, 2025)

Experimental and computational study on xylan pyrolysis: The effect of branch structures - Bin Hu; Wen-ming Zhang; Xue-Wen Guo; Ji-hong Li; Xiao Yang; Zhi-mo Fang; Ji Liu; Qiang Lu (Fuel, 2025)

Influence of whey protein types on the bioaccessibility of β-carotene in different formulations: Emulsions vs microcapsules - Shanshan Hu; Fang Tian; Shiqi Yi; Qihang Liu; Shilin Liu; Yanrong Zhao; Xuguang Zhang; Yan Li (Food Bioscience, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Horizontally oriented 2D skin structures on fiber interface for long-life flexible energy storage devices - Guangyu Fang; Xiaorui Ma; Rong Hu; Jiao Dai; Haoran Tian; Lin Li; Weilin Xu; Yonggang Yao; Jun Wan (Chemical Engineering Journal, 2025)

Developing the sensing mechanism of high-performance N2H4 sensors derived from waste cotton stalk using a one-step process - Ping Hu; Jun Sun; Bo Ran; Jialin Li; Jialu Fang; Qihua Sun; Ning Tian; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

Research of two dust transport pollution in northern China in 2023: Perspectives from LiDAR and multi source data - Hao Yang; Xiaomeng Zhu; Duoyang Qiu; Zhiyuan Fang; Yalin Hu; Xianyang Li (Atmospheric Pollution Research, 2025)

PpBOR1 is critical for the excess borate tolerance of Physcomitrium patens - Ishfaq Ahmad; Xuejia Sun; Yangyang Yu; Fangni Jia; Yizuo Li; Qiang Lv; Yong Hu; Fang Bao; Yikun He (Plant Cell Reports, 2025)

Cooling and Exhumation of the Late Cretaceous Laojunshan Granites in Southeast Yunnan Province, China: Constraints from Fission-Track Thermochronology and Tectonic Implications - Fang Li; Hao Bai; Ye Fang; Da Zhang; Ganguo Wu; Wei Xue; Chaoyang Que; Xinming Zhang; Xiaolong He; Bojie Hu (Journal of Earth Science, 2025)

A strategy for electrochemical biosensing based on dendritic HCR amplification for detection of RNA m5C and m6A methylation - Mimi Li; Lina Wang; Yue Hu; Yi Liu; Shuang Xu; Kexing Peng; Chenghong Li; Hui Huang; Lichao Fang; Lulu Li; Huamin Liu; Xiaolong Wang; et al. (Analytica Chimica Acta, 2025)

Multiple effects of zinc materials on fish, parasites, and the bacterial community in aquatic ecosystems - Xianliang Li; Danyi Wei; Ling Wang; Hao Wang; Jundi Shuli; Wei Hu; Hongyi Chen; Shiqian Fang; Weiliang Guo; Hengwei Deng; Dongdong Zhang; Jianlong Li; et al. (Aquaculture, 2025)

Navigating the gut-liver axis: The potential of tea to alleviate inflammatory bowel disease and associated metabolic syndromes - Qi Fang; Chunyin Qin; Ying Peng; Liang Zhang; Daxiang Li; Shanshan Hu (Trends in Food Science & Technology, 2025)

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

Chemosensory protein 8 confers thiamethoxam resistance in Diaphorina citri - Qian Li; Wan-Wei Hu; Ao Fang; Zhuo-Bing Wang; Xiao-Fang Yuan; Yue Sun; Zheng-Hui Zou; Nuo Chen; Tian-Xing Jing; Ying-Xue Liu; Wei Chen; Hai-Zhong Yu; et al. (Pesticide Biochemistry and Physiology, 2025)

Impact of eight extruded starchy whole grains on glycemic regulation and fecal microbiota modulation - Fang Fang; Yu-Xin He; Hao-Qiang Wang; Yan-Li Zhang; Ya-dong Zhong; Xiao-Tian Hu; Shao-Ping Nie; Ming-Yong Xie; Jie-Lun Hu (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Separator-SEI interactions: Unlocking new pathways for lithium metal battery stability - Shuyang Li; Wei Zhou; Junyu Hou; Fei Yan; Renzong Hu; Jie Zhao; Fang Fang; Jiafeng Ruan; Yun Song (Chemical Engineering Journal, 2025)

Synergy of Ni single atoms and NiO nanoclusters in carbon nitride to create local charge polarization for enhanced CO2 photoreduction - Lei Li; Xinyan Dai; Chao Cheng; Fang Chen; Saikh Mohammad Wabaidur; Wentao Wang; Yong Hu (Chemical Engineering Journal, 2025)

Evaluation of Antibiotic-Sensitive Bacillus Strain as a Potential Probiotic for Enhanced Growth in Penaeus vannamei - Yiwen Gu; Ke Xu; Zhuoran Chen; Yanxu Lu; Shuguang Fang; Kun Hu; Xin Ju; Liangzhi Li; Zhi Chen (Current Microbiology, 2025)

Linking microbial nutrient limitation and community composition to nitrogen mineralization in bamboo forest soil with phosphorus addition - Tong-Tao Hu; Dong Bu; Yang Zhang; Fang-Chao Wang; Jian-Jun Li; Kui-Ling Zu; Ming-Hui Meng; Chao Liang; Xiang-Min Fang (Soil Ecology Letters, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Long-term warming offsets the beneficial effect of elevated CO2 on mineral associated organic carbon in Mollisols - Xinqi SiMa; Yansheng Li; Zhenhua Yu; Haidong Gu; Junjie Liu; Judong Liu; Rui Fang; Xiaojing Hu; Xiaobing Liu; Guanghua Wang; Caixian Tang; Ashley Franks; et al. (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Antimicrobial perylenequinones isolated from the endophytic fungus Alternaria alstroemeriae - Yong-Fu Li; Fang Yue; Xu-Ri Wan; Chang Li; Yi Sun; Yue-Hu Pei (Phytochemistry Letters, 2025)

Electroactivation of peroxymonosulfate (PMS)-coupled electrocoagulation for degradation of iodinated contrast media and reduction of I-DBPs formation: Dual control and QSAR modeling - Shuai Fang; Zhaoyang Wang; Wenyi Hu; Jin Bian; Xin Li (Journal of Hazardous Materials, 2025)

Marine productivity controlled by oceanic circulation in the Northwest Pacific over the last glacial cycle - Limin Hu; Hao Fang; Xuefa Shi; Yuying Zhang; Zhifei Duan; Chao Li; Jörg Lippold; Minoru Ikehara; Yiming Luo (Global and Planetary Change, 2025)

Insight into the effect of support properties on DBD plasma-catalytic NH3 synthesis over Ru-Co bimetallic catalysts - Bianbian Gao; Guoqiang Cao; Donghai Hu; Liang Guo; Zhongren Ba; Chunyu Li; Jiantao Zhao; Yitian Fang (Fuel, 2025)

American ginseng fruit: Antioxidant capacity, bioactive components, and biosynthesis mechanism during development - Yujuan Zhang; Lijuan Hou; Jing Hu; Xianchang Wang; Shujing Guo; Hongqing Xie; Yun Zhou; Wen Ai; Lin Li; Xin Wang; Li Ren; Fangzhou Zhao; et al. (Food Research International, 2025)

Dispersed organic matter from pre-Devonian marine shales: A review on its composition, origin, evolution, and potential for hydrocarbon prospecting - Qingyong Luo; Fariborz Goodarzi; Ningning Zhong; Nansheng Qiu; Xiaomei Wang; Václav Suchý; Imran Khan; Xiaowei Zheng; Bei Liu; Omid H. Ardakani; Ye Zhang; Dahua Li; et al. (Earth-Science Reviews, 2025)

Oxygen vacancies induced intrinsic electric field attenuation for superior molecular oxygen activation and NO oxidation - Hao Ma; Wenting Li; Bin Liu; Haonan Hu; Yuhan Li; Wei Xu; Ruimei Fang; Fan Dong (Chemical Engineering Journal, 2025)

Biochar addition affects the microfood web structure of soil animals: A meta-analysis - Fang Yuan; Xue Hu; Wang Shiping; Li Ma; Zhonghua Zhang; Lihong Song; Honglin Li; Buqing Yao; Huakun Zhou (CATENA, 2025)

Three new isoquinoline alkaloids from the fermentation of Aspergillus sp. 0338 and their anti-MRSA activities - Min Yang; Miao Dong; Qing-Yang Wu; Shui Yao; Gui Pu; Yue-Yu Ma; Rui-Feng Xiong; Qiu-Fen Hu; Fang Wang; Yin-Ke Li (Natural Product Research, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Acrylamide drives amidase-mediated gut dysbiosis to aggravate colitis - Daotong Li; Yinghua Luo; Huimin Fan; Li Dong; Xiaoying Zhang; Yu Feng; Meiling Tian; Shuqing Zhang; Wenjing Chen; Lujia Zhang; Jianwei Gao; Xiangning Ma; et al. (Science Bulletin, 2025)

Preparation and characterization of novel natural pigment-indicating film: Application in kiwifruit freshness monitoring - Si Xia; Xiangjun Fang; Weijie Wu; Guannan Wang; Huizhi Chen; Zhiwen Hu; Li-Shu Wang; Ruilin Liu; Haiyan Gao (Food Chemistry, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Exogenous C6-HSL enhanced the cometabolic removal of sulfadiazine by an enriched ammonia oxidizing bacteria culture - Bingzheng Wang; Yaqin Wang; Jiali Fang; Ziheng Feng; Haoxing Hu; Huiyun Zhong; Sisi Chen; Ji Li (Environmental Pollution, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

ZnO site-occupying effect assisted regulation of nanoporous carbon network to enhance capacitive deionization for copper ions removal - Yang Zhao; Fei Wang; Yufeng Yan; Shuangfeng Fang; Baihang Cai; Jin Huang; Xinru Gong; Jian Hu; Li Liu; Hengyuan Hu; Yudan Zhang; Ziqi Cai; et al. (Desalination, 2025)

Identification of xenobiotic response element family transcription regulator SadR from sulfonamides-degrading strain Microbacterium sp. HA-8 and construction of biosensor to detect sulfonamides - Qian Li; Mingliang Zhang; Changchang Wang; Kaihua Pan; Hongfei Liu; Weihao Zhu; Yanni Huang; Qian Zhu; Junqiang Hu; Mingli Jiang; Fang Wang; Qing Hong (Bioresource Technology, 2025)

Impacts of human behaviors involving sound and light exposure in sleep environments on sleep and mental disorders: A cross-sectional study - Linmin Hu; Xinjie Dai; Xixian Fang; Kai Su; Chunliang Wang; Chunhui Yang; Ruitong Zhang; Jie He; Minhui Li; Xinran Ye; Jiahong Xu; Xiyang Pan; et al. (Building and Environment, 2025)

Development and characterization of a complete set of monosomic alien addition lines from Raphanus sativus in Brassica oleracea - Shiting Fang; Jingwen Zhao; Fangping Lei; Jie Yu; Qi Hu; Tuo Zeng; Lei Gu; Hongcheng Wang; Xuye Du; Mengxian Cai; Zaiyun Li; Bin Zhu (Theoretical and Applied Genetics, 2025)

RO4929097 inhibits NICD3 to alleviate pulmonary hypertension via blocking Notch3/HIF-2α/FoxM1 signaling pathway - Hao Zhu; Cheng Li; Fang Hu; Lifu Wu; Ling Wu; Meihua Zhou; Wei Liu; Aiguo Dai (In Vitro Cellular & Developmental Biology - Animal, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Paroxetine promotes longevity via ser-7-dop-4-IIS axis in Caenorhabditis elegans - Yiming Zhou; Lijuan Chen; Meijing Wang; Yang Yang; Bin Hu; Guolin Li; Fang Wei (GeroScience, 2024)

Implications of inhalation bioaccessibility for the exposure assessment of drifting airborne pesticides caused by field spraying - Tingting Meng; Ke Fang; Tingting Li; Weizhang Qi; Li Zhang; Yingmei Hu; Yuying Liu; Yanhong Shi; Haiqun Cao; Jinjing Xiao (Science of The Total Environment, 2024)

Sequential oxidation procedures with KMnO4: Component characteristics of labile reducing capacity fractions in anaerobic sediments - Xuemei Chen; Zhijun Li; Songjie Fu; Lanwei Liang; Xiaohan Liu; Fang Hu; Wen Zhang; Yonghong Bi; Yang Jiao; Sen Gu; Qingman Li (Science of The Total Environment, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Lactobacillus reuteri or Lactobacillus rhamnosus GG intervention facilitates gut barrier function, decreases corticosterone and ameliorates social behavior in LPS-exposed offspring - Xinyuan Wang; Riqiang Hu; Fang Lin; Ting Yang; Yiwen Lu; Zhujun Sun; Tingyu Li; Jie Chen (Food Research International, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

The effect of enzymatic hydrolysis on the flavor improvement of chicken broth by characterizing key taste and odor-active compounds - Minjie Liao; Siyi Peng; Haibin Guo; Xin Yuan; Kaixin Li; Lingjun Ma; Fang Chen; Xiaosong Hu; Xiaojun Liao; Junfu Ji (Food Bioscience, 2024)

Characterization of core microbiota of barley seeds from different continents for origin tracing and quarantine pathogen assessment - Xin Zhou; Fang Liu; Chun-Chun Wang; Hui-Li Zhang; Peng Zhao; Fu-Hong Xie; Dian-Ming Hu; Wei-Jun Duan; Lei Cai (Food Microbiology, 2024)

Enhancement of PFAS stress tolerance and wastewater treatment efficiency by arbuscular mycorrhizal fungi in constructed wetlands - Yuchen Wang; Xue Li; Lexing You; Shanshan Hu; Jinfu Fang; Bo Hu; Zhongbing Chen (Environmental Research, 2024)

Understanding the synergistic catalysis of balanced Cu0-Cu+ sites and oxygen vacancies in Cu/ZrO2 catalysts for the efficient hydrogenation of furfural - Xinling Yang; Zhou Chen; Jingjing Tan; Yuanna Zhang; Jinglei Cui; Changzhen Wang; Li Fang; Yulei Zhu; Long Huang; Hu Shi; Yongzhao Wang (Chemical Engineering Journal, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

High-Precision Re-Os Geochronology of the newly Discovered Lihefu Deposit Reveals the ∼145 Ma Mo Mineralization in Daye District, Eastern China - Hao Hu; Longpeng Li; Heng Luo; Yi Huang; Fang Sun; Jinhua Liu; Xiaodong Deng (Journal of Earth Science, 2024)

PTGR1-mediated immune evasion mechanisms in late-stage triple-negative breast cancer: mechanisms of M2 macrophage infiltration and CD8+ T cell suppression - Fang Huang; Fuhe Wang; Qilu Hu; Ying Li; Da Jiang (Apoptosis, 2024)

Toward the bioactive potential of myricitrin in food production: state-of-the-art green extraction and trends in biosynthesis - Yaqian Geng; Yingfeng Xie; Wei Li; Yao Mou; Fang Chen; Jianbo Xiao; Xiaojun Liao; Xiaosong Hu; Junfu Ji; Lingjun Ma (Critical Reviews in Food Science and Nutrition, 2024)

Interactions between dissolved organic matter with different molecular weights and nonylphenol in surface water bodies - Demin Li; Zhaoyang Wang; Qianqian Ding; Hong Sun; Shuai Fang; Kangyi Zhang; Wenyi Hu; Jin Bian (Chemosphere, 2024)

Unveiling the overlooked small-sized microbiome in river ecosystems - Fang-Zhou Gao; Li-Xin Hu; You-Sheng Liu; Lu-Kai Qiao; Zi-Yin Chen; Jian-Qiang Su; Liang-Ying He; Hong Bai; Yong-Guan Zhu; Guang-Guo Ying (Water Research, 2024)

Asiatic acid induces lung cancer toxicity by triggering SRC-mediated ferroptosis - Huizhen Li; Guixuan Fang; Wen Tian; Yinglin Liao; Jing Xiang; Yingying Hu; Lianxiang Luo (Toxicology and Applied Pharmacology, 2024)

The effect of mixed microbial agents on tobacco black shank disease - Fang Liang; Chai Yunxia; Li Yuanyuan; Geng Shaowu; Bu Yunhong; Hu Yang; Ai Kebiao; Shi Jianfei; Duan Jiyou; Yang Maosong; Zhu Rong (Physiological and Molecular Plant Pathology, 2024)

Hydro-morphology and water quality jointly shape the structure and network stability of the plankton community in multi-tributary river basins - Chao Chang; En Hu; Xudong Xue; Juan Li; Dou Du; Fang Yang; Ming Li (Journal of Hydrology, 2024)

Construction and characterization of different hemolysin gene deletion strains in Vibrio parahaemolyticus (ΔhlyA, ΔhlyIII) and evaluation of their virulence - Jinyuan Che; Shaojie Hu; Qitong Fang; Binghong Liu; Zhuochen Liu; Cunjie Hu; Lei Wang; Lekang Li; Baolong Bao (Journal of Invertebrate Pathology, 2024)

Polyamide microplastics can mitigate the effects of pathogenic bacterium on the health of marine mussels - Yiting Pan; Wenxin Zhao; James Kar-Hei Fang; Jianhang Shi; Mohamed H. Aboraya; Daoji Li; Menghong Hu; Youji Wang (Journal of Hazardous Materials, 2024)

MAMCL: Multi-attributes Masking Contrastive Learning for explainable seismic facies analysis - Long Han; Xinming Wu; Zhanxuan Hu; Jintao Li; Huijing Fang (Computers & Geosciences, 2024)

Defective carbon-bridged Cu sites to boost oxygen reduction reaction in neutral zinc-air batteries - Tianjing Wu; Honghui Hu; Yufeng Wu; Mingjun Jing; Zhanpeng Chen; Fang Chen; Yansong Bai; Dan Li; Sheng Zhang; Lijie Liu; Wentao Deng; Hongshuai Hou; et al. (Chemical Engineering Journal, 2024)

Corrigendum to “Design of molecular scale inhibitors for high temperature industrial cooling water systems based on group synergistic effects” [Chem. Eng. J. 494 (2024) 153164] - Jing Fang; Zhiqiu Ye; Zhansi Dou; Yanhua Zhang; Wei Wu; Yuan Hu; Bibo Wang; Hao Li (Chemical Engineering Journal, 2024)

Surface patterned polyvinyl alcohol/CNT hydrogels for sustained solar powered high concentration brine desalination and salt harvesting - Changjun Li; Xiaoyang Fang; Chen Hu; Mang Zhao; Shumiao Li; Hao-Yu Zhao; Tingting Zhang; Zhong-Zhen Yu; Xiaofeng Li (Chemical Engineering Journal, 2024)

Investigation into pullout characteristics of root piles within coral sand foundations at varied relative compaction - Zhiqiang Wang; Xiangwei Fang; Yuhao Li; Chunni Shen; Fenghui Hu; Ganggang Zhou (Marine Georesources & Geotechnology, 2024)

Multi-behavior detection of group-housed pigs based on YOLOX and SCTS-SlowFast - Ran Li; Baisheng Dai; Yuhang Hu; Xin Dai; Junlong Fang; Yanling Yin; Honggui Liu; Weizheng Shen (Computers and Electronics in Agriculture, 2024)

Identification of key anthropogenic and land use factors and ecological risk assessment of dissolved polycyclic aromatic hydrocarbons (PAHs) and organochlorine pesticides (OCPs) in an urbanized estuary in China - Huijun Liu; Jiajie Hu; Yan Tan; Zhong Zheng; Mengyang Liu; Rainer Lohmann; Simon Vojta; Samuel Katz; Yong Liu; Zhiheng Li; Zhiguo Fang; Minggang Cai; et al. (Marine Pollution Bulletin, 2024)

Nano-enabled strategies to promote safe crop production in heavy metal(loid)-contaminated soil - Li Chen; Linchuan Fang; Wenfeng Tan; Haijian Bing; Yi Zeng; Xunfeng Chen; Zimin Li; Weifang Hu; Xing Yang; Sabry M. Shaheen; Jason C. White; Baoshan Xing (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

PSO-SLIC algorithm: A novel automated method for the generation of high-homogeneity slope units using DEM data - Yange Li; Bangjie Fu; Zheng Han; Zhenxiong Fang; Ningsheng Chen; Guisheng Hu; Weidong Wang; Guangqi Chen (Geomorphology, 2024)

Preparation and characterization of fennel (Foeniculum vulgare miller) essential oil/hydroxypropyl-β-cyclodextrin inclusion complex and its application for chilled pork preservation - Qianqian Song; Qian Lu; Shengyang Zhang; Zihan Zhang; Jialing Huang; Xin Li; Dan Song; Jiarui Pu; Zhibo Yang; Zhengfeng Fang; Yuntao Liu; Bin Hu (Food Chemistry, 2024)

Tomato juice regulates bile acid-TGR5 signaling and reverses cognitive deficit and neuroinflammation in high-fat high-cholesterol diet-induced mice - Xunyu Song; Lujia Zhang; Jun Sun; Xinbing Zhang; Daotong Li; Xiaosong Hu; Fang Chen (Food Bioscience, 2024)

Antibiotic resistance genes risks in relation to host pathogenicity and mobility in a typical hospital wastewater treatment process - Chenye Xu; Chun Hu; Fang Li; Weiping Liu; Yumin Xu; Dake Shi (Environmental Research, 2024)

Characteristics of China's coal mine methane emission sources at national and provincial levels - Di Chen; Mengyue Ma; Liting Hu; Qianna Du; Bowei Li; Yang Yang; Liya Guo; Zhouxiang Cai; Mingrui Ji; Runze Zhu; Xuekun Fang (Environmental Research, 2024)

Highly-sensitive ultrathin flexible pressure sensor based on quasi-2D conductive network for human physiological signal monitoring - Lixia Li; Yuhang Liu; Zhihong Wang; Dongqi Wang; Kai Yang; Haiqing Hu; Shuyan Qi; Li Fang; Lijing Han; Ruoyu Zhang (Chemical Engineering Journal, 2024)

Assessing bioavailability risks of heavy metals in polymetallic mining regions: a comprehensive analysis of soils with varied land uses - Shan Liu; Yanni Li; Changlin Zhan; Hongxia Liu; Jiaquan Zhang; Kuangxin Guo; Tianpeng Hu; Bhagawati Kunwar; Lihu Fang; Yanan Wang (Environmental Monitoring and Assessment, 2024)

Molecular insights into the enhanced growth of cyanobacteria by adaptive laboratory evolution in wastewater environments - Lang Hu; Xinyi Fang; Lelei Wen; Haixin Zhang; Baoyu Peng; Changchun Li (Algal Research, 2024)

The Association Between the Non-essential Metal Mixture and Handgrip Strength in Chinese Community-Dwelling Older Adults - Yan Zhang; Ziwei Tian; Xuqiu Cheng; Bohao Fang; Qiang Liu; Junzhe Li; Yuan Wang; Hongli Wang; Xianwei Guo; Guimei Chen; Huaibiao Li; Liang Sun; et al. (Biological Trace Element Research, 2024)

Unveiling influences of metal-based nanomaterials on wheat growth and physiology: From benefits to detriments - Fengyu Huang; Li Chen; Yi Zeng; Wei Dai; Fang Wu; Qing Hu; Ying Zhou; Shunmei Shi; Linchuan Fang (Chemosphere, 2024)

A citrullinated antigenic vaccine in treatment of autoimmune arthritis - Xu Jin; Tianya Dong; Qian Wang; Yang Xie; Xiangyu Fang; Chaonan Wei; Shuyan Liu; Xi Zheng; Ping Wang; Danxue Zhu; Lulu Cao; Suwei Dong; et al. (Science Bulletin, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Physiological responses of the microalga Isochrysis galbana exposed to polystyrene microplastics with different particle sizes - Xue'en Jin; Yuyang Fang; Li'ang Li; Menghong Hu; James Kar-Hei Fang; Fahim Ullah Khan; Wei Huang; Youji Wang (Marine Environmental Research, 2024)

Application of external voltage-applied enhances surface adhesion of Shewanella oneidensis MR-1 - Guowei Chen; Renhao Shen; Yifei Sun; Fazhu Wu; Chao Yuan; Zhen Hu; Xia Li; Xuefei Wu; Zhipeng Fang; Li Liu; Gang Wang (Journal of Water Process Engineering, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Exogenous selenium promotes cadmium reduction and selenium enrichment in rice: Evidence, mechanisms, and perspectives - Fengyu Huang; Li Chen; Ying Zhou; Jingqiu Huang; Fang Wu; Qing Hu; Nan Chang; Tianyi Qiu; Yi Zeng; Haoran He; Jason C. White; Wenchao Yang; et al. (Journal of Hazardous Materials, 2024)

Synergistic effects of superfine grinding and high hydrostatic pressure on the contents, distribution, digestive behaviors and antioxidant activities of polyphenols in barley leaves - Huijuan Zhu; Jiahao Li; Xin Yuan; Jiajia Zhao; Lingjun Ma; Fang Chen; Xiaosong Hu; Junfu Ji (Food Chemistry, 2024)

Metal-organic cages for efficient capture and convenient detection of iodine from vapor and aqueous solutions - Zhi-Yong Zeng; Zhen-Chen Lou; Lianrui Hu; Weitao Dou; Xiaoli Zhao; Xiaodong Li; Junfeng Fang; Xuhong Qian; Hai-Bo Yang; Lin Xu (Chemical Engineering Journal, 2024)

Phase separation behavior and CO2 absorption kinetic analysis of DETA/DEA/DMAC biphasic absorbent - Zhipeng Chen; Tao Wang; Chao Li; Mengxiang Fang; Wei Chen; Ximing Hu; Yan Shao; Zhihao Liu; Wei Zhang; Li Zhang; Wenyang Fan; Shaojuan Zeng (Chemical Engineering Journal, 2024)

Enhanced photodetection in organic semiconductor single crystal sensitized by a tailored synergistic absorption of capsule-shaped chlorophyll derived CQDs - Yangyang Xie; Jinkai Wei; Yongxu Hu; Jianzhou Ren; Hongling Guo; Hao Lv; Chong Geng; Zhongwu Wang; Shu Xu; Fang Wang; Lei Zheng; Kailiang Zhang; et al. (Chemical Engineering Journal, 2024)

Synthesis of NaAlSiO4 Hollow Microspheres as Absorbents for the Removal of Heavy Metal Ions from Wastewater - Zhiyuan Ouyang; Lihui Meng; Yanru Hu; Wenchao Li; Fang Zhu; Bin Xie; Zilin Zhou; Shuojie Cui; Meng Wang; Qingzhi Wu (Environmental Processes, 2024)

Community Composition and Functional Characterization of Microorganisms in Surface Sediment of the New Britain Trench - Lin Hu; Zhixuan Wang; Zixuan Wang; Li Wang; Jiasong Fang; Rulong Liu (Current Microbiology, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Fucoidan changes lipid accumulation in the liver of common carp (Cyprinus carpio) by modulating lipid and glucose metabolism - Fang Li; Hanchang Sun; Jianxi Mei; Yaxin Deng; Guangdi Hu; Chengke Zhu; Xiao Xiang (Frontiers in Marine Science, 2024)
An 8-week feeding trial was conducted to investigate the effects of dietary fucoidan levels (0 mg/kg, 500 mg/kg, 1,000 mg/kg, 1,500 mg/kg, and 2,000 mg/kg) on the hepatic ultrastructure and the transcriptomic landscape within the liver tissue of common carp. The results revealed that the addition of 1,000 mg/kg fucoidan to the diet significantly altered the ultrastructure of hepatocytes. Notably, the quantities of lipid droplets, autolysosomes, enlarged mitochondria, and endoplasmic reticulum were increased in the hepatocytes. The liver transcriptome analysis revealed that DEGs were notably abundant in the 1,000-mg/kg fucoidan group in glucolipid metabolism signaling pathways, including eukaryotes and nicotinate and nicotinamide metabolism, steroid biosynthesis, and PPAR signaling pathways. The quantitative real-time PCR (qPCR) results showed an excellent agreement on those of RNA-seq for both up- and down-regulated genes (a total of 13 genes selected for validation). Furthermore, fucoidan significantly influenced hepatic glucolipid metabolism of common carp at the mRNA level. Notably, the inclusion of lower concentrations of fucoidan in the diet, specifically at 500 mg/kg and 1,000 mg/kg, was found to significantly enhance the expression of mRNA for genes involved in glycolysis, including hk, gk, and pk, as well as genes linked to lipogenesis, such as srebf1, fasn, elovl5, acsl3a, scd, fads2, and cyp24a1. Conversely, higher concentrations of dietary fucoidan, at 1,500 mg/kg and 2,000 mg/kg, were observed to markedly upregulate the mRNA expression of genes associated with gluconeogenesis, including pck1, pck2, gs, gsk3a, gsk3b, and g6pca.1, along with genes related to lipolysis, such as hadhb, acadl, ecil, acacba, cpt1, fabp1, and fabp3. In summary, varying levels of fucoidan intake appear to exert differential influences on the hepatic glucolipid metabolism of common carp, suggesting a complex dose-dependent regulatory mechanism. For the first time, this research has established that fucoidan possesses a pronounced regulatory influence on the hepatic glucolipid metabolism in fish. This discovery not only underscores its potential as an immunostimulant but also opens new avenues for its application as a feed additive, with implications for modulating the nutritional metabolism of aquatic species.

Electroacupuncture Alleviates Streptozotocin-Induced Diabetic Neuropathic Pain via the TRPV1-Mediated CaMKII/CREB Pathway in Rats - Yinmu Zheng; Siyi Li; Yurong Kang; Qunqi Hu; Yu Zheng; Xiaoxiang Wang; Hengyu Chi; Keying Guo; Minjian Jiang; Zhouyuan Wei; Xiaomei Shao; Chi Xu; et al. (Journal of Molecular Neuroscience, 2024)

Optimising maize threshing by integrating DEM simulation and interpretive enhanced predictive modelling - Xuwen Fang; Jinsong Zhang; Xuelin Zhao; Li Zhang; Deyi Zhou; Chunsheng Yu; Wei Hu; Qiang Zhang (Biosystems Engineering, 2024)

Spatio-temporal patterns and population exposure risks of urban heat island in megacity Shanghai, China - Dan Liu; Rui Zhou; Qun Ma; Tianxing He; Xuening Fang; Lishan Xiao; Yina Hu; Jie Li; Lin Shao; Jun Gao (Sustainable Cities and Society, 2024)

Dynamic responses of the floatover system with nonstationary mating processes: An experimental study - Xukai Fang; Xinchao Li; Rongze Wang; Yu Chen; Changjun Hu; Xiaoxian Guo; Wenyue Lu; Xin Li; Xinliang Tian (Ocean Engineering, 2024)

The stress response of tetracycline resistance genes and bacterial communities under the existence of microplastics in typical leachate biological treatment system - Hong Li; Yiting Lian; Siyi Li; Mingdi Yang; Qiaona Xie; Libo Qiu; Hongyuan Liu; Yuyang Long; Lifang Hu; Chengran Fang (Journal of Environmental Management, 2024)

Iron biogeochemical redox cycling dominantly controls cadmium availability in acidic paddy soils - Yang Yang; Tongxu Liu; Thomas Borch; Liping Fang; Shiwen Hu; Wenting Chi; Guojun Chen; Kuan Cheng; Qi Wang; Xiaomin Li; Xiu Yuan; Fangbai Li (Geochimica et Cosmochimica Acta, 2024)

The effects and cell phenotype changes in Escherichia coli O157:H7 induced into VBNC state by l-malic acid at low temperature - Zequn Zhang; Yicong Shi; Tianlin Cui; Kangyi Mu; Fang Chen; Xiaojun Liao; Li Dong; Xiaosong Hu (Food Bioscience, 2024)

Covalent conjugate of pea protein induced by cyanidin-3-O-glucoside quinone: The structural formation and functional properties - Kaixin Li; Xin Yuan; Jiajia Zhao; Jinbo Ren; Lingjun Ma; Xiaojun Liao; Xiaosong Hu; Fang Chen; Junfu Ji (Food Hydrocolloids, 2024)

Design of molecular scale inhibitors for high temperature industrial cooling water systems based on group synergistic effects - Jing Fang; Zhiqiu Ye; Zhansi Dou; Yanhua Zhang; Wei Wu; Yuan Hu; Bibo Wang; Hao Li (Chemical Engineering Journal, 2024)

Pyrolysis-free coupling strategy to synthesize two-dimensional oxygen reaction electrocatalysts for rechargeable Zn-air batteries - Peng-Fei Xie; Hao Hu; Lingzhe Fang; Xiaohua Yu; Ju Rong; Xiaoyi Qiu; Feng Wu; Tao Li; Minhua Shao; Jin-Cheng Li (Chemical Engineering Journal, 2024)

Suspended sediment-discharge hysteresis characteristics and controlling factors in a small watershed of southern China - Yu Long; Ming Lei; Taoxi Li; Peiyao Xiao; Siyuan Liu; Jiaming Xu; Fang Tang; Xuexiang Hu; Xizhong Hu; Xiaodong Nie; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Alleviating Pentatrichomonas hominis-induced damage in IPEC-J2 cells: the beneficial influence of porcine-derived lactobacilli - Yibin Zhu; Haiming Cai; Zhuanqiang Yan; Hanqin Shen; Siyun Fang; Dingai Wang; Shenquan Liao; Nanshan Qi; Minna Lv; Xuhui Lin; Junjing Hu; Yongle Song; et al. (Veterinary Research Communications, 2024)

Associations between exposure to various air pollutants and risk of metabolic syndrome: a systematic review and meta-analysis - Changmao Dai; Xiaolan Sun; Liangqing Wu; Jiao Chen; Xiaohong Hu; Fang Ding; Wei Chen; Haiyan Lei; Xueping Li (International Archives of Occupational and Environmental Health, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

Glutathione-activated biotin-targeted dual-modal imaging probe with improved PDT/PTT synergistic therapy - Zhi-Chao Yang; Qing-Song Gu; Jing-Jing Chao; Fang-Yuan Tan; Guo-Jiang Mao; Liufang Hu; Juan Ouyang; Chun-Yan Li (Analytica Chimica Acta, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Systemic glucocorticoids link to long-term microvascular injury in COVID-19 - Qian Yang; Cai Yun Xia; Ying Cai; Yan Fang Zhang; Dao Ting Li; Shu Qi Wu; Peng Hu (Angiogenesis, 2024)

Exogenous indole modulates several CpxRA-mediated virulence-related parameters of Edwardsiella piscicida in vitro - Yin Gou; Qingjian Fang; Hanjie Gu; Aijun Tian; Jun Li; Yan Wang; Yonghua Hu (Marine Life Science & Technology, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Corrosion performance of A3 carbon steel in 30wt.% MEA and AMP-MEA blends for post-combustion carbon capture: Effect and mechanism of corrosion inhibitors - Yuwei Wang; Mengxiang Fang; Jun Gao; Chao Li; Yan Huang; Lin Yang; Shuifei Li; Ximing Hu; Tao Wang (International Journal of Greenhouse Gas Control, 2024)

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

Fishbone and nettle fiber inspired stretchable strain sensor with high sensitivity and wide sensing range for wearable electronics - Weiqiang Hong; Xiaohui Guo; Xianghui Li; Tianxu Zhang; Xiaowen Zhu; Jianwei He; Renkai Zhang; Shishun Yang; Yupeng Shao; Yuanyuan Fang; Zhihao Yin; Xunxun Sun; et al. (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Maize kernel damage dynamic prediction in threshing through PSO-LSTM and discrete element modelling - Xuwen Fang; Jinsong Zhang; Xuelin Zhao; Qiang Zhang; Li Zhang; Deyi Zhou; Chunsheng Yu; Wei Hu; Hao Wang (Biosystems Engineering, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

Microbial-induced carbonate precipitation effectively prevents Pb2+ migration through the soil profile: Lab experiment and model simulation - He-Wei Song; Dong Li; Hao Qiu; Zhi-Guo Yu; Amit Kumar; Xiu-Xiu Yan; Fang-Yu Hu; Bao-Yu Wang; Jing An (Science of The Total Environment, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

Is cryoablation still suitable for advanced non-small cell lung cancer after failure of first-line chemotherapy? A multicenter, prospective, randomized-controlled trial of eighty-seven patients - Yu Chen; Xueni Fang; Dan Wang; Quanwang Li; Kerui Zhang; Yuan Li; Jinghua Li; Haoyue Pang; Zhiqiang Cheng; Chunyang Zhang; Caiyun Zhang; Wuwei Yang; et al. (Cryobiology, 2024)

Interfacial high-valence Ni(IV)-enabled C-H activation for photoelectrochemical C-C bond cleavage of lignin to exclusively produce aromatic carboxylic acids - Pei-dong Wu; Lanyun Li; Hu Li; Zhen Fang (Chemical Engineering Journal, 2024)

NIR-triggered self-healing SiO2/melanin coatings with enhanced corrosion-resistant and mechanical robustness - Zhiqiang Fang; Yangkai Xiong; Lei Huang; Jipeng Li; Daxiong Hu; Qitong Mao; Hao Jiang; Xuewei Tang; Panpan Tang; Zheng Li; Guoqing Wang (Chemical Engineering Journal, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

Fully automated measurement of femoral neck axis line in anatomical coordinate system using CT images - Li Li; Qiyao Ye; Tan Hu; Dongshen Fang; Runyu Wan; Yu Shi (Medical & Biological Engineering & Computing, 2024)

Integrating network pharmacology and experimental models to identify notoginsenoside R1 ameliorates atherosclerosis by inhibiting macrophage NLRP3 inflammasome activation - Jingyue Yu; Jinyu Hu; Margaret Baldini; Huan Lei; Lei Li; Shanshan Luo; Jielian Wu; Xupin Liu; Dan Shan; Yanfei Xie; Haihong Fang; Jun Yu (Journal of Natural Medicines, 2024)

Dissolved oxygen and ammonia affect ammonia production via GDH/AMPK signaling pathway and alter flesh quality in Chinese perch (Siniperca chuatsi) - Ru Yang; Xuange Liu; Yong Liu; Qingda Tian; Ziwei Wang; Dejie Zhu; Zhisong Qian; Yi Yi; Jiacheng Hu; Yan Li; Xu-Fang Liang; Liwei Liu; et al. (Fish Physiology and Biochemistry, 2024)

Formulation and Characterization of Ethosomes for Transdermal Delivery of Prinsepia Utilis Rogle Seed Oil with Ameliorative Effects against UVB-Induced Skin Damage - Qianqian Fang; You Li; Fei Xiong; Xiaolong Hu; Ying Song; Wenbing Shen; Haijuan Dong; Xinhong Shi; Hao Wang (AAPS PharmSciTech, 2024)

Effects of different cooking methods on proximate composition, digestion characteristics, and antioxidant activity of Lentinus edodes - Chunxue Zeng; Hongyu Li; Junqi Li; Cheng Li; Zhengfeng Fang; Bin Hu; Caixia Wang; Saiyan Chen; Xiaolin Li; Zhen Zeng; Yuntao Liu (Food Chemistry, 2024)

Distribution characteristics of reactive silicon in six water bodies in the Yangtze River Basin in China - Xuemei Chen; Lanwei Liang; Songjie Fu; Xu Bao; Sen Gu; Yang Jiao; Fang Hu; Abdur Rahman; Qingman Li (Environmental Research, 2024)

Geographic distribution of bacterial communities of inland waters in China - Binhao Wang; Kaiming Hu; Chuqiao Li; Yinan Zhang; Chao Hu; Zhiquan Liu; Jiafeng Ding; Lin Chen; Wei Zhang; Jing Fang; Hangjun Zhang (Environmental Research, 2024)

Cellular senescence mediates hexavalent chromium-associated lung function decline: Insights from a structural equation Model - Yali Zhang; Guiping Hu; Qiaojian Zhang; Shiyi Hong; Zekang Su; Li Wang; Tiancheng Wang; Shanfa Yu; Fang Yuan; Xiaojun Zhu; Guang Jia (Environmental Pollution, 2024)

From disinfection to pathogenicity: Occurrence, resistome risks and assembly mechanism of biocide and metal resistance genes in hospital wastewaters - Chenye Xu; Yibo Zhang; Chun Hu; Chensi Shen; Fang Li; Yumin Xu; Weiping Liu; Dake Shi (Environmental Pollution, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

A deep learning-based imputation method for missing gaps in satellite aerosol products by fusing numerical model data - Ning Liu; Yi Li; Zengliang Zang; Yiwen Hu; Xin Fang; Simone Lolli (Atmospheric Environment, 2024)

Genetic dissection of ten photosynthesis-related traits based on InDel- and SNP-GWAS in soybean - Dezhou Hu; Yajun Zhao; Lixun Zhu; Xiao Li; Jinyu Zhang; Xuan Cui; Wenlong Li; Derong Hao; Zhongyi Yang; Fei Wu; Shupeng Dong; Xiaoyue Su; et al. (Theoretical and Applied Genetics, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Achieving zero fouling in the ultrafiltration for secondary water supply systems in the absence of residual chlorine - Huizhi Hu; Fang Xu; Rui Wang; Chu Zhou; Na Li; Senlin Shao (Water Research, 2024)

The relationship between the microclimate and efflorescence of revealed mural paintings and the later protection strategy - Shiqiang Fang; Wenjing Hu; Qian Li; Bingjian Zhang; Xueqiang Chen; Lina Xie (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Probing the role of natural resources and urbanization towards ecological sustainability in BRICST economies - Yang Shi; Jinlong Li; Zhen Fang; Ye Li; Han Hu; Wei Nie; Fuyu Meng (Resources Policy, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Impacts of exogenous C6-HSL on the enhanced cometabolic removal of sulfadiazine by enriched nitrifying sludge - Yaqin Wang; Bingzheng Wang; Jiali Fang; Ziheng Feng; Haoxing Hu; Huiyun Zhong; Ji Li (Journal of Water Process Engineering, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Microcystin-LR and polystyrene microplastics jointly lead to hepatic histopathological damage and antioxidant dysfunction in male zebrafish - Wang Lin; Fen Hu; Fang Liu; Ling Liao; Ling Ling; Li Li; Jifeng Yang; Pinhong Yang (Environmental Pollution, 2024)

A green large-scale fabrication of cellulose-based multifunctional fluorescent fibers for versatile applications - Changjing Qiu; Fang Peng; Pingping Wu; Xijun Wang; Songnan Hu; Chuanlin Huang; Xingxing Li; Dingfeng Xu; Hui Li; Peng-Cheng Ma; Pan Chen; Haisong Qi (Chemical Engineering Journal, 2024)

Global warming determines future increase in compound dry and hot days within wheat growing seasons worldwide - Yan He; Yanxia Zhao; Shao Sun; Jiayi Fang; Yi Zhang; Qing Sun; Li Liu; Yihong Duan; Xiaokang Hu; Peijun Shi (Climatic Change, 2024)
Compound dry and hot extremes are proved to be the most damaging climatic stressor to wheat thereby with grave implications for food security, thus it is critical to systematically reveal their changes under unabated global warming. In this study, we comprehensively investigate the global change in compound dry and hot days (CDHD) within dynamic wheat growing seasons during 2015–2100 under 4 socio-economic scenarios (SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5) based on the latest downscaled Coupled Model Intercomparison Project Phase 6 (CMIP6) models. Our results demonstrate a notable increase in CDHD’s frequency ( $${CDHD}_{f}$$ CDHD f ) and severity ( $${CDHD}_{s}$$ CDHD s ) worldwide under all SSPs, such increase is sharper over southern Asia in winter wheat growing season, and southern Canada, northern America, Ukraine, Turkey and northern Kazakhstan in spring wheat growing season. As the top 10 wheat producer, India and America will suffer much more detrimental CDHD in their wheat growing season. Adopting a low forcing pathway will mitigate CDHD risks in up to 93.3% of wheat areas. Positive dependence between droughts and heats in wheat growing season is found over more than 74.2% of wheat areas, which will effectively promote the frequency and severity of CDHD. Global warming will dominate the increase of CDHD directly by increasing hot days and indirectly by enhancing potential evapotranspiration thereby aggravating droughts. This study helps to optimize adaptation strategies for mitigating CDHD risks on wheat production, and provides new insights and analysis paradigm for investigating future variations in compound extremes occurring within dynamic crops growing seasons.

Nitrogen deposition-induced stimulation of soil heterotrophic respiration is counteracted by biochar in a subtropical forest - Yongfu Li; Shaobo Zhang; Yunying Fang; Dafeng Hui; Caixian Tang; Lukas Van Zwieten; Jiashu Zhou; Zhenhui Jiang; Yanjiang Cai; Bing Yu; Junguo Hu; Guomo Zhou; et al. (Agricultural and Forest Meteorology, 2024)

Porous durian shell biochar modified by KMnO4 (Mn-DSB) as a highly selective adsorbent for Be(II) - Yucheng Su; Xu Zhao; Yige Sun; Yuexiang Dong; Weiliang Wang; Haoshuai Li; Fang Hu; Qingliang Wang (Environmental Science and Pollution Research, 2024)

Temporal and spatial variations in the sub-daily precipitation structure over the Qinghai–Tibet Plateau (QTP) - Hou-Liang Lu; Jun Qiu; Meng-Jia Li; Hui-Min Zuo; Jin-Li Li; Bill X. Hu; Fang-Fang Li (Science of The Total Environment, 2024)

The effect of the endogenous protein on the rheological and digestive properties of rice starch - Hao Hu; Genyuan Li; Tingting Zhang; Sixing Lai; Kefan Ouyang; Fang Huang; Songyu Wang; Hua Xiong; Qiang Zhao (Journal of Cereal Science, 2024)

Estimation on strength parameters of sediments with hydrate layered distribution based on triaxial shearing tests - Lin Dong; Nengyou Wu; Fang Liu; Zhiwen Sun; Minhui Qi; Gaowei Hu; Yanlong Li (Gas Science and Engineering, 2024)

Molecular layer deposited mechanically and chemically robust niobicone interface empowering silicon nanowire anodes with competent cyclabilities - Jiabin Fang; Jianguo Li; Wangle Zhang; Lijun Qin; Kang Wu; Longfei Hui; Ting Gong; Dan Li; Yiyun Hu; Aidong Li; Hao Feng (Chemical Engineering Journal, 2024)

Defect-promoted nanoparticles−nanorod Ni−NiMoO4 heterogeneous nanostructures as efficient electrocatalysts to overall water/urea splitting in fresh/sea water - Caihong Fang; Ran Li; Xin Wang; Fei Duan; Junfeng Lin; Yunqin Hu; Zhiqing Cui (Chemical Engineering Journal, 2024)

Mimosa inspired intelligent anti-corrosive composite coating by incorporating lignin and pyridine derivatives grafted graphene oxide - Chang-An Xu; Xingchi Li; Zhengbang Tong; Zhuangzhuang Chu; Heng Fang; Yang Hu; Xudong Chen; Zhuohong Yang (Chemical Engineering Journal, 2024)

Environmental fluctuation influences the ontogenetic dispersal and distribution of two ommastrephid squids in the Pacific Ocean - Zhou Fang; Peiwu Han; Yan Wang; Jianhua Li; Guanyu Hu; Bilin Liu; Xinjun Chen (Reviews in Fish Biology and Fisheries, 2024)

Comparison of microbial communities in unleached and leached ionic rare earth mines - Lingyan Li; Haitao Wang; Jingang Hu; Yun Fang; Fang Zhou; Junxia Yu; Ruan Chi; Chunqiao Xiao (Environmental Science and Pollution Research, 2024)

Chemical features and biological functions of water-insoluble dietary fiber in plant-based foods - Meiling Tian; SolJu Pak; Chen Ma; Lingjun Ma; Kannan R. R. Rengasamy; Jianbo Xiao; Xiaosong Hu; Daotong Li; Fang Chen (Critical Reviews in Food Science and Nutrition, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Exploring the adverse effects of 1,3,6,8-tetrabromo-9H-carbazole in atherosclerotic model mice by metabolomic profiling integrated with mechanism studies in vitro - Tong Xu; Yu Jiang; Hualing Fu; Guanglei Yang; Xiaoxu Hu; Yangsheng Chen; Qian Zhang; Yuxi Wang; Yilan Wang; Heidi Qunhui Xie; Fang Han; Li Xu; et al. (Chemosphere, 2024)

Effects of elevated temperature and different crystal structures of TiO2 nanoparticles on the gut microbiota of mussel Mytilus coruscus - Zhuoqing Li; Li’ang Li; Inna Sokolova; Yueyong Shang; Wei Huang; Waiho Khor; James K.H. Fang; Youji Wang; Menghong Hu (Marine Pollution Bulletin, 2024)

The role and mechanism of NLRP3 in wasp venom-induced acute kidney injury - Haoran Li; Jianhua Gong; Fang Bian; Fanglin Yu; Hai Yuan; Fengqi Hu (Toxicon, 2024)

Do mould inhibitors alter the microbial community structure and antibiotic resistance gene profiles on textiles? - Ningyuan Yao; Wei Li; Lanfang Hu; Nan Fang (Science of The Total Environment, 2024)

Mitigating growth-stress tradeoffs via elevated TOR signaling in rice - Wei Li; Jiaqi Liu; Zeqi Li; Ruiqiang Ye; Wenzhen Chen; Yuqing Huang; Yue Yuan; Yi Zhang; Huayi Hu; Peng Zheng; Zhongming Fang; Zeng Tao; et al. (Molecular Plant, 2024)

Multi-scenario validation of the robust inversion method with biased plume range and values - Xinwen Dong; Shuhan Zhuang; Yuhan Xu; Hao Hu; Xinpeng Li; Sheng Fang (Journal of Environmental Radioactivity, 2024)

Water-ultrastable perovskite CsPbBr3 nanocrystals tailored by surface-confined strategy for amaranth sensing in food samples - Lei Hu; Kai-Qi Liu; Feng Li; Heng-Ye Li; Wei Wang; Hai-Lin Fang; Hang Gao; Zhong-Xia Wang (Food Chemistry, 2024)

Effects of ferulic acid on the polymerization behavior of gluten protein and its components - Wen Li; Xinyang Sun; Alfred Mugambi Mariga; Qin Yang; Yong Fang; Qiuhui Hu; Fei Pei (Food Hydrocolloids, 2024)

Catalytic hydroformylation of alkenes to branched aldehydes promoted by water on Rh nanoclusters-anchored porous triphenylphosphine frameworks - Dongrun Wang; Gong Zeng; Jian Fang; Hu Li; Hangning Chen; Jiantai Ma; Zhengping Dong (Chemical Engineering Journal, 2024)

Controlling carbon dioxide-to-hydrogen ratio to improve hydrogen utilization and denitrification rates of hydrogenotrophic autotrophic denitrification through homoacetogenesis-heterotrophic denitrification pathway - Yongcun Li; Yuwei Wang; Fang Dong; Shoujun Yuan; Zhenhu Hu; Wei Wang (Bioresource Technology, 2024)

Navigation path recognition between rows of fruit trees based on semantic segmentation - Liang Zhang; Ming Li; Xinghui Zhu; Yedong Chen; Jinqi Huang; Zhiwei Wang; Tian Hu; Ziru Wang; Kui Fang (Computers and Electronics in Agriculture, 2024)

Oropharyngeal aspirated Ag/TiO2 nanohybrids: Transformation, distribution and toxicity - Xiaoquan Huang; Congcong Li; Tingting Wei; Na Liu; Yongshuai Yao; Zhihui Wang; Yuanyuan Hu; Qing Fang; Shujing Guan; Yuying Xue; Tianshu Wu; Ting Zhang; et al. (Science of The Total Environment, 2024)

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Lake plastisphere as a new biotope in the Anthropocene: Potential pathogen colonization and distinct microbial functionality - Chenye Xu; Chun Hu; Jiawei Lu; Tong Yang; Chensi Shen; Fang Li; Jie Wang (Journal of Hazardous Materials, 2024)

Aspartic acid/arginine enhance the stability of gelatin emulsions - Hui-min Yan; Yu Song; Man-man Yu; Xiu-ning Yao; Wen-wen Zhang; Ying Xu; Xue-qing Li; Yu-qin Xu; Shun Fang; Jun Qi; Guo-yuan Xiong; Chao Li; et al. (Journal of Food Engineering, 2024)

Release of anthocyanins encapsulated by high hydrostatic pressure-treated micellar casein: Effect of serum Ca2+ level during in vitro digestion - Jinbo Ren; Yinning Qian; Lu Peng; Minjie Liao; Kaixin Li; Fang Chen; Xiaosong Hu; Xiaojun Liao; Lingjun Ma; Junfu Ji (Innovative Food Science & Emerging Technologies, 2024)

Efficient hydrogen production from formic acid over Ag@AgPd nanotriangulars at room temperature - Qian Lei; Ruoyan Miao; Xueqian Li; Xiaoyu Liu; Yuanyuan Li; Zhangwei He; Huidong Xie; Fang Song; Xiang Liu; Hu Liu (Fuel, 2024)

Gas chromatography ion mobility spectroscopy: A rapid and effective tool for monitoring oil oxidation - Fang Cui; Min Liu; Xue Li; Du Wang; Fei Ma; Li Yu; Chundi Hu; Peiwu Li; Liangxiao Zhang (Food Research International, 2024)

Changes in flavor and biological activities of Lentinula edodes hydrolysates after Maillard reaction - Jianguo Qiu; Hongyu Li; Yang Liu; Cheng Li; Zhengfeng Fang; Bin Hu; Xiaolin Li; Zhen Zeng; Yuntao Liu (Food Chemistry, 2024)

Landscapes of the main components, metabolic and microbial signatures, and their correlations during pile-fermentation of Tibetan tea - Ziqi Wang; Hongyu Li; Weimin Huang; Songqi Duan; Yue Yan; Zhen Zeng; Zhengfeng Fang; Cheng Li; Bin Hu; Wenjuan Wu; Xiguo Lan; Yuntao Liu (Food Chemistry, 2024)

Efficient piezo-photocatalysis of Bi2O2(OH)NO3/BiOI heterojunction: Collaboration of piezoelectric polarization and interface electric field - Yuanrui Li; Xiaolei Zhang; Rui Sha; Tong Li; Cheng Hu; Shuchen Tu; Fang Chen; Hongwei Huang (Chemical Engineering Journal, 2024)

Synergistic effect between Ni single atoms and Ni nanoparticles for effectively boosting sustainable co-electrolysis of CO2 and hydrazine - Min Li; Ye Hu; Wenhui Fang; Shixian Xin; Ying Wu; Yutao Cao; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

Introducing back-surface field for efficient inverted CsPbI3 perovskite solar cells - Chunyan Lu; Xiaodong Li; Haobo Yuan; Wenxiao Zhang; Xuemin Guo; Acan Liu; Hui Yang; Wen Li; Zhengbo Cui; YuYang Hu; Junfeng Fang (Chemical Engineering Journal, 2024)

Angiotensin-(1–9) attenuates adriamycin-induced cardiomyopathy in rats via the angiotensin type 2 receptor - Hui Ma; Chenggang Mao; Yang Hu; Liqin Wang; Xingqing Guo; Lei Li; Fang Wang; Renzheng Guan (Molecular and Cellular Biochemistry, 2024)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

Effects of antibiotic exposure on bioreactor treatment efficiency and dynamic migration of resistance genes in landfill leachate - Hongyuan Liu; Qiaona Xie; Libo Qiu; Hong Li; Yuyang Long; Lifang Hu; Chengran Fang (Journal of Water Process Engineering, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Ultrasonic assisted activation of persulfate for the treatment of spent porous biochar: Degradation of adsorbed PFOA and adsorbent regeneration - Jiaqin Deng; Ying Fang; Changlan Hou; Yanru Zhang; Meifang Li; Jianing Han; WanXuan Du; Chunfang Tang; Xinjiang Hu (Journal of Environmental Chemical Engineering, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Effect of modified atmosphere packaging assisted cold plasma on performance of edible soybean protein isolate films - Qi Li; Ai Zhi; Xueming He; Fei Shen; Yong Fang; Qiuhui Hu; Xingquan Liu (Food Bioscience, 2023)

In vitro gastrointestinal digestion of thermally reversible and irreversible fish gelatin induced by microbial transglutaminase - Xiao-Mei Sha; Ting Fang; Jia-Hui Zhang; Sheng Shu; Wen-Li Jiang; Zi-Zi Hu; Zong-Cai Tu (Food Hydrocolloids, 2023)

Bio-functionalization of metakaolin for better performance of metakaolin mortars - Yonghui Wang; Hu Fang; Peiyuan Chen; Chunning Pei; Jin Li; Xin Shen (Applied Clay Science, 2023)

Poly-adenine-mediated tetrahedral DNA nanostructure with multiple target-recognition sites for ultrasensitive and rapid electrochemical detection of Aflatoxin B1 - Kaixuan Wang; Nuanfei Zhu; Yumo Li; Hu Zhang; Beibei Wu; Jian Cui; Jun Tang; Zhugen Yang; Fang Zhu; Zhen Zhang (Analytica Chimica Acta, 2023)

Implicit finite difference wave equation forward modeling based on partial fraction expansion - Jian-yong Song; Hong Cao; Ming-hui Lu; Zhi-fang Yang; Xin-hai Hu; Hong-bing Li; Xin-fei Yan (Applied Geophysics, 2023)

Efficient removal of per- and polyfluoroalkyl substances from biochar composites: Cyclic adsorption and spent regenerant degradation - Jiaqin Deng; Jianing Han; Changlan Hou; Yanru Zhang; Ying Fang; WanXuan Du; Meifang Li; Yuan Yuan; Chunfang Tang; Xinjiang Hu (Chemosphere, 2023)

Effects of four amendments on cadmium and arsenic immobilization and their exposure risks from pakchoi consumption - Zhe Wang; Yiping Zhang; Shiyong Sun; Jinzhao Hu; Wanming Zhang; Hui Liu; Huanjuan He; Jingqiu Huang; Fang Wu; Ying Zhou; Fengyu Huang; Li Chen (Chemosphere, 2023)

Magnetic Fe3O4/bamboo-based activated carbon/UiO-66 composite as an environmentally friendly and effective adsorbent for removal of Bisphenol A - Yao Zhang; Xinyu Hu; Hongbin Wang; Jiaxiong Li; Shuju Fang; Guizhen Li (Chemosphere, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

Long-term residue retention affects seedcotton yield by regulating distribution of photosynthetic carbon, boll capacity of the root system and soil quality - Li Zha; Wen Jin; Guowen Fang; Jingyu Guo; Zhitao Liu; Wei Hu; Zhiguo Zhou; Yali Meng (Field Crops Research, 2023)

Plant-inspired modification strategy for the large-scale, versatile preparation of cellulose-based products with highly effective and durable UV-protective, antimicrobial, and antiviral performance - Songnan Hu; Yuehu Li; Fang Peng; Jinfen Ou; Lei Guo; Yian Chen; Yun Li; Fengxia Yue; Haisong Qi (Chemical Engineering Journal, 2023)

Electroacupuncture Inhibits Pain Memory and Related Anxiety-Like Behaviors by Blockading the GABAB Receptor Function in the Midcingulate Cortex - Xiaoyu Li; Yichen Zhu; Haiju Sun; Zui Shen; Jing Sun; Siqi Xiao; Xiaofen He; Boyu Liu; Yifang Wang; Yuxin Hu; Boyi Liu; Yi Liang; et al. (Molecular Neurobiology, 2023)
Pain memory is commonly considered an underlying cause of chronic pain and is also responsible for a range of anxiety. Electroacupuncture (EA) has been shown to ameliorate pain memories and exert anti-anxiety effects. Previous research has indicated that GABAergic neurons and/or GABA receptors (GABARs) in the midcingulate cortex (MCC) have potential associations with chronic pain and anxiety. However, there is no known empirical research that has specifically studied the effects of EA on the GABAergic system in the MCC. Here, we used cross-injection of carrageenan to establish the pain memory rats model. Immunofluorescence were used to detect the excitability of GABAergic neurons within MCC. Von Frey filament, elevated zero maze, and open field tests were used to measure mechanical allodynia and anxiety-like behaviors, combined with chemogenetic and pharmacologic technologies. Finally, this study provides evidence that pain memories contribute to generalized negative emotions and that downregulating the activity of GABAergic neurons within MCC could block pain memories and reverse anxiety emotion. Specifically, GABA B R is involved in pain memory and related anxiety-like behaviors. Activation of GABAergic neurons in the MCC did not reverse the effects of EA on pain memories and related anxiety-like behaviors, whereas these effects could be reversed by a GABA B R agonist. These findings highlight the functional significance of GABA B R in the EA-mediated attenuation of pain memories and related anxiety-like behaviors in rats.

Influences of arbuscular mycorrhizal fungi on crop growth and potentially toxic element accumulation in contaminated soils: A meta-analysis - Li Chen; Fayuan Wang; Zhiqin Zhang; Herong Chao; Haoran He; Weifang Hu; Yi Zeng; Chengjiao Duan; Ji Liu; Linchuan Fang (Critical Reviews in Environmental Science and Technology, 2023)

The impact of multiple metals exposure on the risk of developing proliferative diabetic retinopathy in Anhui, China: a case–control study - Yan-Qing Li; Si-Tian Zhang; Nai-Yu Ke; Yan-Cheng Fang; Wen-Lei Hu; Guo-Ao Li; Fen Huang; Yan-Feng Zhou (Environmental Science and Pollution Research, 2023)

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Elemental sulfur redox bioconversion for selective recovery of phosphorus from Fe/Al-bound phosphate-rich anaerobically digested sludge: Sulfur oxidation or sulfur reduction? - Qinghong Sui; Lanlan Liu; Lingyu Hu; Yujun Zhou; Jiansheng Li; Lixiang Zhou; Di Fang (Water Research, 2023)

Defects identification and location of underground space for ground penetrating radar based on deep learning - Haobang Hu; Hongyuan Fang; Niannian Wang; Duo Ma; Jiaxiu Dong; Bin Li; Danyang Di; Hongbiao Zheng; Jiang Wu (Tunnelling and Underground Space Technology, 2023)

Lithospheric velocity structure of South China Sea basin from ocean bottom seismometer ambient noise tomography - Liqun Cheng; Yinxia Fang; Xiongwei Niu; Tingzi Li; Chongzhi Dong; Yanghui Zhao; Hao Hu; Fansheng Kong; Pingchuan Tan; Aiguo Ruan; Shaoping Lu; Jianke Fan; et al. (Tectonophysics, 2023)

Nine pairs of undescribed enantiomers from the resin of Styrax tonkinensis (Pierre) Craib ex Hart with anti-inflammatory activity - Qun Li; Hong-Bin Fang; Bin-Yuan Hu; Yong-Ming Yan; Ya-Bin Jiao; Gan-Peng Li; Yong-Xian Cheng (Phytochemistry, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Preparation and characterization of inclusion complex of Myristica fragrans Houtt. (nutmeg) essential oil with 2-hydroxypropyl-β-cyclodextrin - Xiaohui Xi; Jialing Huang; Shengyang Zhang; Qian Lu; Zhengfeng Fang; Cheng Li; Qing Zhang; Yuntao Liu; Hong Chen; Aiping Liu; Shuxiang Liu; Caixia Wang; et al. (Food Chemistry, 2023)

The crosstalk between M1 macrophage polarization and energy metabolism disorder contributes to polystyrene nanoplastics-triggered testicular inflammation - Siwen Li; Lemei Liu; Gang Luo; Yu Yuan; Die Hu; Fang Xiao (Food and Chemical Toxicology, 2023)

RIPF-Unet for regional landslides detection: a novel deep learning model boosted by reversed image pyramid features - Bangjie Fu; Yange Li; Zheng Han; Zhenxiong Fang; Ningsheng Chen; Guisheng Hu; Weidong Wang (Natural Hazards, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

Co-exposure to iron, copper, zinc, selenium and titanium is associated with the prevention of gastric precancerous lesions - Tingting Wang; Fang Xu; Xiao Lin; Yaning Lv; Xiaohui Zhang; Wenli Cheng; Li Wang; Min Wang; Meng Zhang; Tao Xia; Shiqing Qian; Min Tang; et al. (BioMetals, 2023)

Combining hybrid nanoflowers with hybridization chain reaction for highly sensitive detection of SARS-CoV-2 nucleocapsid protein - Wen Yin; Ji Hu; Fang Chen; Li Zhu; Yingxin Ma; Nuo Wang; Hongping Wei; Hang Yang; Shan-Ho Chou; Jin He (Analytica Chimica Acta, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

MLDet: Towards efficient and accurate deep learning method for Marine Litter Detection - Dongliang Ma; Jine Wei; Ye Li; Fang Zhao; Xi Chen; Yuchao Hu; Shanshan Yu; Tianhao He; Ruihe Jin; Zhaozhao Li; Min Liu (Ocean & Coastal Management, 2023)

Spatiotemporal characteristics of Chinese metro-led underground space development: A multiscale analysis driven by big data - Yun-Hao Dong; Fang-Le Peng; Hu Li; Yan-Qing Men (Tunnelling and Underground Space Technology, 2023)

Factors impacting the behavior of phytoremediation in pesticide-contaminated environment: A meta-analysis - Fang Jia; Yue Li; Qian-nan Hu; Lan Zhang; Lian-gang Mao; Li-zhen Zhu; Hong-yun Jiang; Xin-gang Liu; Yan Sun (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Ambient NO2 hinders neutrophil extracellular trap formation in rats: Assessment of the role of neutrophil autophagy - Shuzi Ye; Yu Ma; Siwen Li; Sijia Luo; Lai Wei; Die Hu; Fang Xiao (Journal of Hazardous Materials, 2023)

Reforestation substantially changed the soil antibiotic resistome and its relationships with metal resistance genes, mobile genetic elements, and pathogens - Song Zhang; Ting Li; Jinming Hu; Kexin Li; Dong Liu; Haixia Li; Fang Wang; Danhong Chen; Zejin Zhang; Qiuping Fan; Xiaoyong Cui; Rongxiao Che (Journal of Environmental Management, 2023)

Targeting transportation of curcumin by soybean lipophilic protein nano emulsion: Improving its bioaccessibility and regulating intestinal microorganisms in mice - Zhen Zeng; Siqi Deng; Yang Liu; Cheng Li; Zhengfeng Fang; Bin Hu; Hong Chen; Caixia Wang; Saiyan Chen; Wenjuan Wu; Yuntao Liu (Food Hydrocolloids, 2023)

Alteration of the migration trajectory of antibiotic resistance genes by microplastics in a leachate activated sludge system - Hongyuan Liu; Hong Li; Libo Qiu; Qiaona Xie; Yingying Lu; Binhui Chen; Hua Wang; Yuyang Long; Lifang Hu; Chengran Fang (Environmental Pollution, 2023)

Establishment of TRV-mediated Gene Silencing and Application for Elucidating Functions of Anthocyanidin Reductase Gene HcANR in Kenaf (Hibiscus cannabinus L.) - Xin Yang; Hu Li; Sylvain Niyitanga; Lilan Zhang; Xingen Li; Jianmin Qi; Jiantang Xu; Aifen Tao; Pingping Fang; Liwu Zhang (Tropical Plant Biology, 2023)

Systematic analyzing a five- miRNA panel and its diagnostic value of plasma expression in colorectal cancer - Si-Qi Li; Li-Ye Xie; Zheng-Min Cai; Hao-Tang Wei; Ming-Zhi Xie; Bang-Li Hu; Shu-Fang Ning (Molecular Biology Reports, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

PKMYT1: A Potential Target for CCNE1 Amplificated Colorectal Tumors - Yong Fang; Xuhui Zhang; Yuyang Guo; Yi Dong; Wenfei Liu; Xihua Hu; Xuxin Li; Daifeng Gao (Cell Biochemistry and Biophysics, 2023)

Quantifying the effects of urban development intensity on the surface urban heat island across building climate zones - Tianxing He; Rui Zhou; Qun Ma; Chunlin Li; Dan Liu; Xuening Fang; Yina Hu; Jun Gao (Applied Geography, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Reciprocal effects of NOM and solution electrolyte ions on aggregation of ferrihydrite nanoparticles - Zhixiong Li; Yandi Hu; Yufan Chen; Shiyu Fang; Yuyan Liu; Wei Tang; Jiawei Chen (Chemosphere, 2023)

Understanding spontaneous biodiversity in informal urban green spaces: A local-landscape filtering framework with a test on wall plants - Xinyu Miao; Yuhan Pan; Hanxu Chen; Ming-Juan Zhang; Wensi Hu; Yuxiang Li; Ruoyu Wu; Peiyao Wang; Shubo Fang; Kechang Niu; Chi Xu; Shuqing N. Teng (Urban Forestry & Urban Greening, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

Emission factors of ozone-depleting chloromethanes during production processes based on field measurements surrounding a typical chloromethane plant in China - Bowei Li; Xingchen Zhao; Xinhe Li; Xiaoyi Hu; Liting Hu; Di Chen; Minde An; Yang Yang; Rui Feng; Liya Guo; Pengnan Jiang; Bo Yao; et al. (Journal of Cleaner Production, 2023)

Aflatoxins degradation and quality evaluation in naturally contaminated rice by dielectric barrier discharge cold plasma - Ai Zhi; Shanshan Shi; Qi Li; Fei Shen; Xueming He; Yong Fang; Qiuhui Hu; Xuesong Jiang (Innovative Food Science & Emerging Technologies, 2023)

Molecular insights into ions permeation and destruction behavior in methane hydrate driven by electrostatic fields - Jie Chen; Zhengcai Zhang; Yongchao Hao; Daniel Porfirio Luis Jiménez; Jiafang Xu; Nengyou Wu; Fulong Ning; Bin Fang; Jun Zhang; Jianye Sun; Xiluo Hao; Qingguo Meng; et al. (Fuel, 2023)

Influence of interfacial properties/structure on oxygen diffusion in oil-in-water emulsions - Yanlei Li; Fangfang Chen; Zhiming Gao; Wei Xiang; Yuehan Wu; Bing Hu; Xuewen Ni; Katsuyoshi Nishinari; Yapeng Fang (Food Research International, 2023)

Effect of different concentrations of gellan gum with/without 0.50% basil essential oil on the physicochemical properties of gellan gum-rice bran oil coating emulsions and their application in egg preservation - Dongmei Pan; Yakai Li; Yue Hu; Rui Li; Xun Gao; Xiaokang Fan; Hongmei Fang; Qiang Du; Cunliu Zhou (Food Chemistry, 2023)

Comparative analysis of the interaction between alpha-lactalbumin and two edible azo colorants equipped with different sulfonyl group numbers - Mohan Li; Dian Zhou; Di Wu; Xia Hu; Jie Hu; Fang Geng; Lei Cheng (Food Chemistry, 2023)

Combined effect of salinity and hypoxia on digestive enzymes and intestinal microbiota in the oyster Crassostrea hongkongensis - Zhe Xie; Yuting Li; Kai Xiong; Zhihan Tu; Khor Waiho; Chuangye Yang; Yuewen Deng; Saishuai Li; James K.H. Fang; Menghong Hu; Sam Dupont; Youji Wang (Environmental Pollution, 2023)

Synthesis of nonthermal plasma-irradiated polyvalent manganese (hydro)oxide functionalized nanosilica for intensifying geopolymerized solidification/stabilization of thallium-contaminated soil and mechanism exploration - Tao Huang; Dongping Song; Qi Fang; Chaojun Yang; Di Wu; Shouze Li; Yinglan Luo; Yujie Yan; Zhengfeng Hu (Chemical Engineering Journal, 2023)

Cellulose sulfate lithium as a conductive binder for LiFePO4 cathode with long cycle life - Xu Su; Han Fang; Hao Yang; Fangfang Zou; Gang Li; Lian Wang; Hongxin Liao; Wei Guan; Xuebu Hu (Carbohydrate Polymers, 2023)

Improvement of duplex-specific nuclease salt tolerance by fusing DNA-binding domain of DNase from an extremely halotolerant bacterium Thioalkalivibrio sp. K90mix - Wenhao Hu; Jin Wang; Juan Li; Mengxia Yang; Zhixing Li; Xuning Zhang; Fang Wu; Yaqi Zhang; Zhidan Luo; Henghao Xu (Extremophiles, 2023)

A rapid and effective method for obtaining ardicrenin from Ardisia crenata Sims var. bicolor plants - Zhen Lin; Xiuling Yang; Lin Li; Chunyan Ma; Lingjuan Kong; Huancheng Li; Shican Xiong; Haiyan Zhong; Shangrao Pu; Fang Liang; Ju Hu (Brazilian Journal of Botany, 2023)

Interaction between four galactans with different structural characteristics and gut microbiota - Song Li; Jielun Hu; Haoyingye Yao; Fang Geng; Shaoping Nie (Critical Reviews in Food Science and Nutrition, 2023)

Mechanism of antibiotic resistance development in an activated sludge system under tetracycline pressure - Hong Li; Hongyuan Liu; Libo Qiu; Qiaona Xie; Binhui Chen; Hua Wang; Yuyang Long; Lifang Hu; Chengran Fang (Environmental Science and Pollution Research, 2023)

Down-regulated Smyd1 participated in the inhibition of myoblast differentiation induced by cigarette smoke extract - Fang Li; Mengting Xu; Jianing Miao; Nengyin Hu; Ying Wang; Lili Wang (Toxicology Letters, 2023)

Banks, emissions, and environmental impacts of China's ozone depletion substances and hydrofluorocarbon substitutes during 1980–2020 - Jing Wu; Shan Ding; Xuekun Fang; Fuli Bai; Tong Li; Jing Wang; Dayu Zhang; Tengfei Ma; Liying Yi; Jianxin Hu (Science of The Total Environment, 2023)

Dietary exposure to nTiO2 reduces byssus performance of mussels under ocean warming - Saishuai Li; Hui Chen; Chunhua Liu; Inna M. Sokolova; Yuchuan Chen; Fujing Deng; Zhe Xie; Li'ang Li; Wei Liu; James Kar-Hei Fang; Daohui Lin; Menghong Hu; et al. (Science of The Total Environment, 2023)

Biogeographic distribution, ecotype partitioning and controlling factors of Chloroflexi in the sediments of six hadal trenches of the Pacific Ocean - Jiaxin Wu; Li Wang; Jiangtao Du; Yuheng Liu; Lin Hu; Hui Wei; Jiasong Fang; Rulong Liu (Science of The Total Environment, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Potassium isotope fractionation during granite differentiation and implications for crustal K isotope heterogeneity - Zi-Yi Ding; Shan-Ke Liu; Ben-Xun Su; Wen-Jun Li; Yang Bai; Qi-Qi Pan; Fang-Yang Hu; Kwan-Nang Pang (Lithos, 2023)

Sources, bioaccumulation, and toxicity mechanisms of cadmium in Chlamys farreri - Huan Liu; Xiuhui Tian; Lisheng Jiang; Dianfeng Han; Shunxin Hu; Yanmei Cui; Fang Jiang; Yongchun Liu; Yingjiang Xu; Huanjun Li (Journal of Hazardous Materials, 2023)

A robust and ultra-high-surface hydrogen-bonded organic framework promoting high-efficiency solid phase microextraction of multiple persistent organic pollutants from beverage and tea - Yalan Hu; Youyou Li; Yueru Shi; Yixin Kuang; Suxin Zhou; Yuan Peng; Yuefan Liu; Luyi Chen; Ningbo Zhou; Juan Zheng; Fang Zhu; Gangfeng Ouyang (Food Chemistry, 2023)

Enhancement of the chemical stability of nanoemulsions loaded with curcumin by unsaturated mannuronate oligosaccharide - Decheng Bi; Meiting Li; Lijun Yao; Nanting Zhu; Weishan Fang; Wushuang Guo; Yan Wu; Hong Xu; Zhangli Hu; Xu Xu (Food Chemistry, 2023)

Fe and Mo dual-site single-atom catalysts for high-efficiency wide-pH hydrogen evolution and alkaline overall water splitting - Wenhui Fang; Ying Wu; Shixian Xin; Ye Hu; Jiaqi Dang; Min Li; Bozhen Chen; Hong Zhao; Zengxi Li (Chemical Engineering Journal, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

The thermodynamics of enhanced dope stability of cellulose solution in NaOH solution by urea - Yu Chen; Yoshiharu Nishiyama; Ang Lu; Yan Fang; Ziqiang Shao; Tao Hu; Dongdong Ye; Haisong Qi; Xiaodong Li; Jakob Wohlert; Pan Chen (Carbohydrate Polymers, 2023)

Rif1 Regulates Self-Renewal and Impedes Mesendodermal Differentiation of Mouse Embryonic Stem Cells - Cheng Liu; Peng Yu; Zongna Ren; Fang Yao; Li Wang; Guang Hu; Pishun Li; Quanyi Zhao (Stem Cell Reviews and Reports, 2023)
Background RAP1 interacting factor 1 ( Rif1 ) is highly expressed in mice embryos and mouse embryonic stem cells (mESCs). It plays critical roles in telomere length homeostasis, DNA damage, DNA replication timing and ERV silencing. However, whether Rif1 regulates early differentiation of mESC is still unclear. Methods In this study, we generated a Rif1 conditional knockout mouse embryonic stem (ES) cell line based on Cre-loxP system. Western blot, flow cytometry, quantitative real-time polymerase chain reaction (qRT-PCR), RNA high-throughput sequencing (RNA-Seq), chromatin immunoprecipitation followed high-throughput sequencing (ChIP-Seq), chromatin immunoprecipitation quantitative PCR (ChIP-qPCR), immunofluorescence, and immunoprecipitation were employed for phenotype and molecular mechanism assessment. Results Rif1 plays important roles in self-renewal and pluripotency of mESCs and loss of Rif1 promotes mESC differentiation toward the mesendodermal germ layers. We further show that Rif1 interacts with histone H3K27 methyltransferase EZH2, a subunit of PRC2, and regulates the expression of developmental genes by directly binding to their promoters. Rif1 deficiency reduces the occupancy of EZH2 and H3K27me3 on mesendodermal gene promoters and activates ERK1/2 activities. Conclusion Rif1 is a key factor in regulating the pluripotency, self-renewal, and lineage specification of mESCs. Our research provides new insights into the key roles of Rif1 in connecting epigenetic regulations and signaling pathways for cell fate determination and lineage specification of mESCs. Graphical abstract

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Real-time perception of rock–machine interaction information in TBM tunnelling using muck image analysis - Wei-Qiang Xie; Xiao-Ping Zhang; Xiao-Li Liu; Chen-Yu Xu; Xin-Fang Li; Dan-Qing Song; Qing Ma; Nan Hu (Tunnelling and Underground Space Technology, 2023)

Selective extraction of gold from strong acid E-waste leachate through H+-triggered cascade reaction of thiolated β-cyclodextrin - Difan Fang; Feihu Bi; Liming Yang; Wenbin Hu; Zan Hua; Hanchen Wei; Changli Chen; Yunyun Tu; Penghui Shao; Min Li; Xubiao Luo; Guang Yang (Resources, Conservation and Recycling, 2023)

Isolation and characterization of a gas-producing and acid-resistant bacterium from spoiled vinegar - Xingjie Wang; Kaidi Hu; Fang Liu; Juan Mou; Jinghui Lai; Mengmei Zhang; Song Wang; Qin Li; Jianlong Li; Aiping Liu; Xiaolin Ao; Li He; et al. (International Journal of Food Microbiology, 2023)

An upconversion nanoplatform based multi-effective theatment for Parkinson’s disease - Binbin Hu; Huaqiang Fang; Zhixin Huang; Wenjing Huang; Li Huang; Huijie Liu; Fanzhen Lv; Wei Huang; Xiaolei Wang (Chemical Engineering Journal, 2023)

Insight into the biomass pyrolysis volatiles reaction with an iron-based oxygen carrier in a two-stage fixed-bed reactor - Donghai Hu; Guoqiang Cao; Meijie Du; Jiejie Huang; Jiantao Zhao; Chunyu Li; Yitian Fang (Chemical Engineering Journal, 2023)

Tribological behavior at electronic scales for an oil-soluble ionic liquid with extremely low effective addition and highly load bearing capacity - Hongling Fang; Yi Li; Hua Li; Songwei Zhang; Qi Ding; Wei Yu; Litian Hu (Chemical Engineering Journal, 2023)

Impacts of ammonia stress on different Pacific whiteleg shrimp Litopenaeus vannamei families and the underlying adaptive mechanisms - Difei Tong; Zhihang Zhu; Jiayan Wu; Fang Li; Jiawei Shen; Jiaqi Cao; Yusong Tang; Guangxu Liu; Lihua Hu; Wei Shi (Aquatic Toxicology, 2023)

Shifting of the first-order root foraging strategies of Chinese fir (Cunninghamia lanceolata) under varied environmental conditions - Yingchun Liao; Houbao Fan; Xiaohua Wei; Huimin Wang; Fangfan Shen; Liang Hu; Yanyan Li; Huanying Fang; Rongzhen Huang (Trees, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Climate and soil management factors control spatio-temporal variation of soil nutrients and soil organic matter in the farmland of Jiangxi Province in South China - Bifeng Hu; Modian Xie; Hongyi Li; Rebin He; Yue Zhou; Yefeng Jiang; Wenjun Ji; Jie Peng; Fang Xia; Zongzheng Liang; Wanming Deng; Junjie Wang; et al. (Journal of Soils and Sediments, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Assessing stroke rehabilitation degree based on quantitative EEG index and nonlinear parameters - Yuxia Hu; Yufei Wang; Rui Zhang; Yubo Hu; Mingzhu Fang; Zhe Li; Li Shi; Yankun Zhang; Zhong Zhang; Jinfeng Gao; Lipeng Zhang (Cognitive Neurodynamics, 2023)

LINC00536 Promotes Breast Cancer Progression by Regulating ROCK1 via Sponging of miR-214-5p - Caixia Hu; Xiufen Zhang; Kai Fang; Zijian Guo; Lihua Li (Biochemical Genetics, 2023)

Ecological drivers and potential functions of viral communities in flooded arsenic-contaminated paddy soils - Ruichuan Gao; Bin Ma; Min Hu; Liping Fang; Guanhong Chen; Wenqiang Zhang; Yiling Wang; Xinwei Song; Fangbai Li (Science of The Total Environment, 2023)

Simultaneous profiling of dust aerosol mass concentration and optical properties with polarized high-spectral-resolution lidar - Da Xiao; Nanchao Wang; Sijie Chen; Lingyun Wu; Detlef Müller; Igor Veselovskii; Chengcai Li; Eduardo Landulfo; Venkataraman Sivakumar; Jing Li; Huizheng Che; Jing Fang; et al. (Science of The Total Environment, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Experimental testing to determine stability thresholds for partially submerged vehicles at different flow orientations - Xiaozhe Hu; Junqi Li; Wenhai Wang; Xing Fang (Journal of Hydrology, 2023)

Effects of co-fermentation on the release of ferulic acid and the rheological properties of whole wheat dough - Wen Li; Xinyang Sun; Yifei Du; Anxiang Su; Yong Fang; Qiuhui Hu; Fei Pei (Journal of Cereal Science, 2023)

A novel gdmH-related gene, ghl, involved in environmental stress tolerance and vancomycin susceptibility in milk-derived Staphylococcus aureus - Hao Pei; Jun Wang; Chengfeng Zhu; Hui Wang; Mengcheng Fang; Fang Shu; Hongli Wang; Yutong Hu; Bingbing Li; Ting Xue (Food Research International, 2023)

Preparation, characterization and safety evaluation of Ligusticum chuanxiong essential oils liposomes for treatment of cerebral ischemia-reperfusion injury - Yu Long; Shuang Yu; Dan Li; Ai Shi; Yin Ma; Jie Deng; Xiao-qiu Li; Jing Wen; Yuan-yuan Wu; Yue Hu; Xiao-fang He; Nan Li; et al. (Food and Chemical Toxicology, 2023)

Combining Bone Collagen Material with hUC-MSCs for Applicationto Spina Bifida in a Rabbit Model - Hu Wang; Xue-Cheng Sun; Jian-Hui Li; Li-Qiang Yin; Yu-Fang Yan; Xu Ma; Hong-Fei Xia (Stem Cell Reviews and Reports, 2023)

Exogenous methyl jasmonate and cytokinin antagonistically regulate lignin biosynthesis by mediating CsHCT expression in Camellia sinensis - Chun-Fang Liu; Ni Yang; Rui-Min Teng; Jing-Wen Li; Yi Chen; Zhi-Hang Hu; Tong Li; Jing Zhuang (Protoplasma, 2023)

Clay mineral distribution characteristics of surface sediments in the South Mid-Atlantic Ridge - Qiannan Hu; Chuanshun Li; Baoju Yang; Xisheng Fang; Huahua Lü; Xuefa Shi; Jihua Liu (Journal of Oceanology and Limnology, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

Assessing the effects of short-term traffic restriction policies on traffic-related air pollutants - Xiao-Rui Fang; Xing-Hang Zhu; Xing-Zhou Li; Zhong-Ren Peng; Hu Qingyao; Hong-Di He; AJ Yuan Chen; Huang Cheng (Science of The Total Environment, 2023)

Structural variation (SV)-based pan-genome and GWAS reveal the impacts of SVs on the speciation and diversification of allotetraploid cottons - Shangkun Jin; Zegang Han; Yan Hu; Zhanfeng Si; Fan Dai; Lu He; Yu Cheng; Yiqian Li; Ting Zhao; Lei Fang; Tianzhen Zhang (Molecular Plant, 2023)

Genomic insights into the genetic basis of cotton breeding in China - Yiqian Li; Zhanfeng Si; Guoping Wang; Zhuolin Shi; Jinwen Chen; Guoan Qi; Shangkun Jin; Zegang Han; Wenhao Gao; Yue Tian; Yun Mao; Lei Fang; et al. (Molecular Plant, 2023)

Microplastics may increase the environmental risks of Cd via promoting Cd uptake by plants: A meta-analysis - Fengyu Huang; Jinzhao Hu; Li Chen; Zhe Wang; Shiyong Sun; Wanming Zhang; Hu Jiang; Ying Luo; Lei Wang; Yi Zeng; Linchuan Fang (Journal of Hazardous Materials, 2023)

Complementary use of generalized logistic mixture model and distributed activation energy model in exploring kinetic mechanisms of wheat straw and torrefied rice husk pyrolysis - Jianfeng Zou; Hangli Hu; Yingkai Li; Hessam Jahangiri; Fang He; Xingguang Zhang; Md Maksudur Rahman; Junmeng Cai (Journal of Cleaner Production, 2023)

Simultaneous oxidation and absorption of nitric oxide and sulfur dioxide by peroxymonosulfate activated by bimetallic metal-organic frameworks - Zhaoxin Wan; Xiude Hu; Chengbo Li; Jiawei Zhang; Qi Wang; Long Fang; Linlin Zhang; Qingjie Guo; Deshuai Sun (Journal of Environmental Chemical Engineering, 2023)

High dissolved oxygen exacerbates ammonia toxicity with sex-dependent manner in zebrafish - Sheng-Xiang Sun; Chun-Ting Hu; Fang Qiao; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

High bioethanol titer and yield from phosphoric acid plus hydrogen peroxide pretreated paper mulberry wood through optimization of simultaneous saccharification and fermentation - Pleasure Chisom Ajayo; Qing Wang; Mei Huang; Li Zhao; Dong Tian; Jinsong He; Dexin Fang; Jinguang Hu; Fei Shen (Bioresource Technology, 2023)

New insights into photochemical initial concentrations of VOCs and their source implications - Bowei Li; Shaocai Yu; Min Shao; Xinhe Li; Steven Sai Hang Ho; Xiaoyi Hu; Hongli Wang; Rui Feng; Xuekun Fang (Atmospheric Environment, 2023)

Comparison and Investigation of Exosomes from Human Amniotic Fluid Stem Cells and Human Breast Milk in Alleviating Neonatal Necrotizing Enterocolitis - Xiaohan Hu; Rui Zhang; Hansi Liang; Jingnan An; Yuan Yang; Jie Huo; Zhenjiang Chen; Wei Quan; Lu Jiang; Cancan Li; Jian Li; Fang Li; et al. (Stem Cell Reviews and Reports, 2023)
In view of the devastating impact of neonatal necrotizing enterocolitis (NEC) on newborns, the research on its intervention is particularly important. Although exosomes from human amniotic fluid stem cells (AFSC) and human breast milk (HBM) can protect against NEC, their mechanisms remain unclear. Here, we intend to compare the intervention effects of two types of exosomes on NEC mouse model and reveal their respective regulatory mechanisms. In general, both AFSC-derived exosomes (AFSC-exos) and HBM-derived exosomes (HBM- exos) can alleviate NEC- associated intestinal injury, significantly reduce NEC score, and reduce systemic and ileal inflammation and NEC related brain injury during experimental NEC. However, the mode and mechanism of action of the two sources of exosomes were not identical. In vivo, the number of ileal crypts was more significantly restored after HBM-exos intervention than AFSC-exos, and in vitro, HBM-exos preferentially inhibited the inflammatory response of intestinal epithelial cells (IECs), whereas AFSC-exos preferentially regulated the migration of IECs. Mechanistically, GO and KEGG analyses revealed the different therapeutic mechanisms of AFSC-exos and HBM-exos in NEC. Taken together, our results illustrate that AFSC-exos and HBM-exos reduce the severity of experimental NEC and intestinal damage through different mechanisms, supporting the potential of cell-free or breast milk free exosome therapy for NEC. Graphical Abstract

Feeding Strategies and Trophic Niche Divergence of Three Groups of Dosidicus gigas off Peru: Based on Stable Carbon and Nitrogen Isotopes and Morphology of Feeding Apparatuses - Zhenfang Zhao; Guanyu Hu; Zhou Fang; Jinhui Li; Bilin Liu; Xinjun Chen (Marine Biotechnology, 2023)

Spatial autocorrelation and spatial heterogeneity of underground parking space development in Chinese megacities based on multisource open data - Yun-Hao Dong; Fang-Le Peng; Hu Li; Yan-Qing Men (Applied Geography, 2023)

A molecularly imprinted fluorescence sensor for sensitive detection of tetracycline using nitrogen-doped carbon dots-embedded zinc-based metal-organic frameworks as signal-amplifying tags - Jinni Zhang; Yan Li; Longhao Teng; Yichuan Cao; Xuelian Hu; Guozhen Fang; Shuo Wang (Analytica Chimica Acta, 2023)

Cationic surfactants influencing the enhancement of energy efficiency for perfluorooctanoic acid (PFOA) removal in the electrocoagulation-flotation (ECF) system - Yueh-Feng Li; Ting Fang; Yu-Chi Lee; Yu-Jung Liu; Ching-Yao Hu; Shang-Lien Lo (Chemosphere, 2023)

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Analysis of differential proteins between non-capacitated and capacitated boar sperm and verification of the effect of phosphofructokinase on capacitation - Feng Ni; Ge Chenling; Huang Fang; Li Xun; Wang Xiaoye; Tang Yinsheng; Huang Mingguang; Hu Chuanhuo (Theriogenology, 2023)

Characteristics and source apportionment of some halocarbons in Hangzhou, eastern China during 2021 - Xinhe Li; Bowei Li; Yang Yang; Liting Hu; Di Chen; Xiaoyi Hu; Rui Feng; Xuekun Fang (Science of The Total Environment, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Immobilization effect of heavy metals in biochar via the copyrolysis of sewage sludge and apple branches - Fang-Zhou Jiang; Hong-Chao Hao; Zi-Ying Hu; Shuo Chen; Zi-Yan Li (Journal of Environmental Management, 2023)

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Manipulating the severe shoot topping delays the harvest date and modifies the flavor composition of Cabernet Sauvignon wines in a semi-arid climate - Hao-Cheng Lu; Li Hu; Yao Liu; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Effect of different cooking methods on the nutrient, and subsequent bioaccessibility and biological activities in Boletus auripes - Xuejiao Li; Linman Yu; Yushan Xie; Cheng Li; Zhengfeng Fang; Bin Hu; Caixia Wang; Saiyan Chen; Wenjuan Wu; Xiaolin Li; Zhen Zeng; Yuntao Liu (Food Chemistry, 2023)

Molecular dynamics simulation of the interaction of food proteins with small molecules - Xia Hu; Zhen Zeng; Jing Zhang; Di Wu; Hui Li; Fang Geng (Food Chemistry, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Volatomics of ‘Cabernet Sauvignon’ grapes and wines under the fan training system revealed the nexus of microclimate and volatile compounds - Meng-Bo Tian; Yao Liu; Hao-Cheng Lu; Li Hu; Yu Wang; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Soil sample sizes for DNA extraction substantially affect the examination of microbial diversity and co-occurrence patterns but not abundance - Ting Li; Song Zhang; Jinming Hu; Haiyan Hou; Kexin Li; Qiuping Fan; Fang Wang; Linfeng Li; Xiaoyong Cui; Dong Liu; Rongxiao Che (Soil Biology and Biochemistry, 2023)

Observational evidence for the non-suppression effect of atmospheric chemical modification on the ice nucleation activity of East Asian dust - Jingchuan Chen; Zhijun Wu; Xiangxinyue Meng; Cuiqi Zhang; Jie Chen; Yanting Qiu; Li Chen; Xin Fang; Yuanyuan Wang; Yinxiao Zhang; Shiyi Chen; Jian Gao; et al. (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Metabolomics and proteomics reveal the toxicological mechanisms of florfenicol stress on wheat (Triticum aestivum L.) seedlings - Hanmei Chen; Jiaojun Jin; Shuhao Hu; Luoqin Shen; Ping Zhang; Zhiheng Li; Zhiguo Fang; Huijun Liu (Journal of Hazardous Materials, 2023)

Formation and application of edible oleogels prepared by dispersing soy fiber particles in oil phase - Yanlei Li; Chao Zhang; Bing Hu; Zhiming Gao; Yuehan Wu; Qianchun Deng; Katsuyoshi Nishinari; Yapeng Fang (Food Research International, 2023)

Investigation of the Quinone-quinone and Quinone-catechol products using 13C labeling, UPLC-Q-TOF/MS and UPLC-Q-Exactive Orbitrap/MS - Yaqian Geng; Zijing Xu; Yiran Yu; Jinbo Yao; Wei Li; Fang Chen; Xiaosong Hu; Junfu Ji; Lingjun Ma (Food Research International, 2023)

Modification of soy protein isolate using dielectric barrier discharge cold plasma assisted by modified atmosphere packaging - Qi Li; Fei Shen; Xueming He; Changrui Xing; Wenjing Yan; Yong Fang; Qiuhui Hu (Food Chemistry, 2023)

The effects of cooperative fermentation by yeast and lactic acid bacteria on the dough rheology, retention and stabilization of gas cells in a whole wheat flour dough system – A review - Xinyang Sun; Simiao Wu; Wen Li; Filiz Koksel; Yifei Du; Lei Sun; Yong Fang; Qiuhui Hu; Fei Pei (Food Hydrocolloids, 2023)

Pesticide exposure and forage shortage in rice cropping system prevents honey bee colony establishment - Feng Liu; Ge Zhang; Chuanlian Zhang; Weiliang Zhou; Xijian Xu; Qinyi Shou; Fang Yuan; Qian Li; Huijun Huang; Jinghua Hu; Wujun Jiang; Jiamin Qin; et al. (Environmental Research, 2023)

Preparation of XCu@TiO2 adsorbent for high-efficient PH3 removal in anaerobic environment and evaluation of desulfurization activity of deactivated adsorbent - Lijuan Jia; Xuejin Yang; Kaiqiang Hu; Jiayu Feng; Fang Wang; Kai Li; Xin Sun; Fei Wang; Ping Ning (Chemical Engineering Journal, 2023)

Synergy of yolk-shelled structure and tunable oxygen defect over CdS/CdCO3-CoS2: Wide band-gap semiconductors assist in efficient visible-light-driven H2 production and CO2 reduction - Siyi Zhang; Shiwen Du; Yumin Wang; Ziwu Han; Xu Li; Guojun Li; Qing Hu; Hu Xu; Chunqing He; Pengfei Fang (Chemical Engineering Journal, 2023)

Improving the hydrogen evolution reaction activity of molybdenum-based heterojunction nanocluster capsules via electronic modulation by erbium–nitrogen–phosphorus ternary doping - Fang Tan; Yingtang Zhou; Hua Zhang; Pengliang Sun; Hongyi Li; Xijun Liu; Thomas Wågberg; Guangzhi Hu (Chemical Engineering Journal, 2023)

Dual-responsive targeted atherosclerosis therapy through a multi-effective nanoplatform with anti-inflammatory, lipid-regulating and autophagy - Huaqiang Fang; Li Huang; Fanzhen Lv; Binbin Hu; Huijie Liu; Zhixin Huang; Yue Sun; Weimin Zhou; Xiaolei Wang (Chemical Engineering Journal, 2023)

Bioactive hydrogel encapsulated dual-gene engineered nucleus pulposus stem cells towards intervertebral disc tissue repair - Yuchen Ye; Panpan Xu; Cai Li; Shichang Jin; Jie Hu; Yuekun Fang; Kun Zhu; Gang Xu; Zhongbing Han; Zhili Zhang; Nan Wu; Pan Jiang; et al. (Chemical Engineering Journal, 2023)

Efficient electrochemical CO2 reduction to CO by metal and nitrogen co-doped carbon catalysts derived from pharmaceutical wastes adsorbed on commercial carbon nanotubes - Yang Gang; Boyang Li; Siyuan Fang; John Pellessier; Lingzhe Fang; Fuping Pan; Zichen Du; Yun Hang Hu; Tao Li; Guofeng Wang; Ying Li (Chemical Engineering Journal, 2023)

Calcification of cell membranes: From ions to minerals - Xiao Gao; Jie Li; Kaiming Hu; Yanyang Zhao; Yu Han; Fang Liu; Maurice E. Tucker; Zuozhen Han (Chemical Geology, 2023)

Genome-Wide Analysis of AMT Gene Family and its Response to Mycorrhizal Symbiosis in Maize - Yunjian Xu; Fang Liu; Shamsur Rehman; Hao Dong; Qunxing Hu; Zhaolin Tu; Xiaoyu Li (Journal of Plant Growth Regulation, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Hearing of Otof-deficient mice restored by trans-splicing of N- and C-terminal otoferlin - Honghai Tang; Hui Wang; Shengyi Wang; Shao Wei Hu; Jun Lv; Mengzhao Xun; Kaiyu Gao; Fang Wang; Yuxin Chen; Daqi Wang; Wuqing Wang; Huawei Li; et al. (Human Genetics, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

A loop‐mediated isothermal amplification‐based microfluidic chip for triplex detection of shrimp pathogens - Keshun Hu; Ye Li; Feng Wang; Jianying Liu; Yuanyuan Li; Qian Zhao; Xiaoye Zheng; Ningyu Zhu; Xiaoping Yu; Shaohua Fang; Jun Huang (Journal of Fish Diseases, 2023)
Decapod iridescent virus 1 (DIV1), White spot syndrome virus (WSSV), and Enterocytozoon hepatopenaei (EHP) pose serious threats to the shrimp farming. To date, early detection remains an important way to control the occurrence and diffusion of these pathogens. Here, we developed for the first time, a loop‐mediated isothermal amplification (LAMP)‐based microfluidic chip detection system, which could detect DIV1, WSSV, and EHP simultaneously. The limits of detection (LoD) of the system were 10 copies/reaction for EHP and DIV1, and 10 2 copies/reaction for WSSV. The entire detection procedure could be completed rapidly in 40 min at 63°C with 100% specificity and had no cross‐reaction with other common shrimp pathogens. This newly established method was further validated using 94 Penaeus vannamei clinical samples, which were comparable to a typical qPCR assay and revealed good stability and reproducibility. These results illustrate that this LAMP microfluidic chip detection system allows rapid triplex pathogen analysis and could satisfy the demands of the field and routine diagnoses in aquaculture.

Performance of anaerobic digestion of phenol using exogenous hydrogen and granular activated carbon and analysis of microbial community - Yongcun Li; Chunhua He; Fang Dong; Shoujun Yuan; Zhenhu Hu; Wei Wang (Environmental Science and Pollution Research, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Composition of dissolved organic matter (DOM) in wastewater treatment plants influent affects the efficiency of carbon and nitrogen removal - Ling Wen; Fang Yang; Xuan Li; Siwan Liu; Yuye Lin; En Hu; Li Gao; Ming Li (Science of The Total Environment, 2023)

In vitro simulated digestion of and microbial characteristics in colonic fermentation of polysaccharides from four varieties of Tibetan tea - Yaowen Tan; Meiwen Li; Keyang Kong; Yushan Xie; Zhen Zeng; Zhengfeng Fang; Cheng Li; Bin Hu; Xinjie Hu; Caixia Wang; Saiyan Chen; Wenjuan Wu; et al. (Food Research International, 2023)

Maternal exposure to ambient PM2.5 perturbs the metabolic homeostasis of maternal serum and placenta in mice - Shimin Tao; Mingjun Yang; Bin Pan; Yuzhu Wang; Fang Tian; Dongyang Han; Wenpu Shao; Wenhui Yang; Yuanting Xie; Xinyi Fang; Minjie Xia; Jingying Hu; et al. (Environmental Research, 2023)

Screening of structural and functional alterations in duckweed (Lemna minor) induced by per- and polyfluoroalkyl substances (PFASs) with FTIR spectroscopy - Ying-Lin Wu; Qian Xiong; Ben Wang; You-Sheng Liu; Pei-Liang Zhou; Li-Xin Hu; Fang Liu; Guang-Guo Ying (Environmental Pollution, 2023)

High performance carbon dioxide electroreduction in ionic liquids with in situ shell-isolated nanoparticle-enhanced Raman spectroscopy - Ye Hu; Zhongdong Gan; Shixian Xin; Wenhui Fang; Min Li; Yanlei Wang; Wei Cui; Hong Zhao; Zengxi Li; Xiangping Zhang (Chemical Engineering Journal, 2023)

Combining Bone Collagen Matrix with hUC-MSCs for Application to Alveolar Process Cleft in a Rabbit Model - Xue-Cheng Sun; Hu Wang; Dan Zhang; Jian-Hui Li; Li-Qiang Yin; Yu-Fang Yan; Xu Ma; Hong-Fei Xia (Stem Cell Reviews and Reports, 2023)

Will the Historic Southeasterly Wind over the Equatorial Pacific in March 2022 Trigger a Third-year La Niña Event? - Xianghui Fang; Fei Zheng; Kexin Li; Zeng-Zhen Hu; Hongli Ren; Jie Wu; Xingrong Chen; Weiren Lan; Yuan Yuan; Licheng Feng; Qifa Cai; Jiang Zhu (Advances in Atmospheric Sciences, 2023)

Transcriptomes of Different Tissues for Expression Characteristics Analysis of MYB gene Family in Kenaf (Hibiscus cannabinus L.) - Hu Li; Xin Yang; Sylvain Niyitanga; Qinyao He; Siyuan Chen; Jiantang Xu; Jianmin Qi; Aifen Tao; Pingping Fang; Liwu Zhang (Tropical Plant Biology, 2022)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Trade-offs between grain yields and ecological efficiencies in a wheat–maize cropping system using optimized tillage and fertilization management on the North China Plain - Daijing Zhang; Yuxin Guo; Zhiyao Fan; Xiao Hu; Xinru Hao; Ling Fang; Chunxi Li (Environmental Science and Pollution Research, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Two new physalins from Physalis alkekengi L. var. franchetii (Mast.) Makino - Jia-Min Sun; Ji-Xiang He; Min Huang; Hui-Xin Hu; Lin-Tao Xu; Kai-Li Fang; Xiao-Ning Wang; Tao Shen (Natural Product Research, 2022)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Exotic fishes that are phylogenetically close but functionally distant to native fishes are more likely to establish - Meng Xu; Shao‐peng Li; Jaimie T. A. Dick; Dangen Gu; Miao Fang; Yexin Yang; Yinchang Hu; Xidong Mu (Global Change Biology, 2022)
Since Darwin's time, degree of ecological similarity between exotic and native species has been assumed to affect the establishment success or failure of exotic species. However, a direct test of the effect of exotic–native similarity on establishment of exotics is scarce because of the difficulty in recognizing failures of species to establish in the field. Here, using a database on the establishment success and failure of exotic fish species introduced into 673 freshwater lakes, we evaluate the effect of similarity on the establishment of exotic fishes by combining phylogenetic and functional information. We illustrate that, relative to other biotic and abiotic factors, exotic–native phylogenetic and functional similarities were the most important correlates of exotic fish establishment. While phylogenetic similarity between exotic and resident fish species promoted successful establishment, functional similarity led to failure of exotics to become established. Those exotic species phylogenetically close to, but functionally distant from, native fishes were most likely to establish successfully. Our findings provide a perspective to reconcile Darwin's naturalization conundrum and suggest that, while phylogenetic relatedness allows exotic fish species to pre‐adapt better to novel environments, they need to possess distinct functional traits to reduce competition with resident native fish species.

Polycyclic aromatic hydrocarbons exposure was associated with microRNA differential expression and neurotransmitter changes: a cross-sectional study in coal miners - Fang Wang; Teng Jia; Yu Wang; Haiyuan Hu; Yuying Wang; Li Chang; Xiaojun Shen; Gaisheng Liu (Environmental Science and Pollution Research, 2022)

Transgenic expression of rice OsPHR2 increases phosphorus uptake and yield in wheat - Yan Li; Yuhui Fang; Chaojun Peng; Xia Hua; Yu Zhang; Xueli Qi; Zhengling Li; Yumin Wang; Lin Hu; Weigang Xu (Protoplasma, 2022)

Optimal Design of the Seepage Control for Xianglushan Diversion Tunnel Under High External Water Pressure - Zhen-jie Zhang; Chun-pin Zeng; Hu Li; Yang Gao; Liang Gong; Yu-xing Li; Hai-fang Liang; En-zhong Zhang (Geotechnical and Geological Engineering, 2022)

Complete mitochondrial genomes of Thyreophagus entomophagus and Acarus siro (Sarcoptiformes: Astigmatina) provide insight into mitogenome features, evolution, and phylogeny among Acaroidea mites - Yu Fang; Mingzhong Sun; Ying Fang; Zetao Zuo; Luyao Liu; Lingmiao Chu; Lan Ding; Caixiao Hu; Feiyan Li; Renrui Han; Xingquan Xia; Shulin Zhou; et al. (Experimental and Applied Acarology, 2022)

Key factors affecting carbon prices from a time-varying perspective - Ming-Fang LI; Hui HU; Lu-Tao ZHAO (Environmental Science and Pollution Research, 2022)

Oral fate and stabilization technologies of lactoferrin: a systematic review - Yun-shan Wei; Kun Feng; Shu-fang Li; Teng-gen Hu; Robert J. Linhardt; Min-hua Zong; Hong Wu (Critical Reviews in Food Science and Nutrition, 2022)

Investigation of an Uncommon Artifact during Reducing Capillary Electrophoresis-Sodium Dodecyl Sulfate Analysis of a Monoclonal Antibody with Dynamic Light Scattering and Reversed Phase High-Performance Liquid Chromatography - Han Gao; Si-Tao Wang; Feng Hu; Bin-Bin Shen; Min-Fei Sun; Haibin Wang; Lei Li; Wei-Jie Fang (Pharmaceutical Research, 2022)

P2X7/P2X4 Receptors Mediate Proliferation and Migration of Retinal Microglia in Experimental Glaucoma in Mice - Meng-Xi Xu; Guo-Li Zhao; Xin Hu; Han Zhou; Shu-Ying Li; Fang Li; Yanying Miao; Bo Lei; Zhongfeng Wang (Neuroscience Bulletin, 2022)

Reliable reference genes for qPCR normalization in females of the mirid predator, Cyrtorhinus lividipennis (Hemiptera: Miridae) - Kui Hu; Ke Chen; Baobao Fu; Jianqi Liu; Yan Li; Qinjian Pan; Fang Liu (Biologia, 2022)

Molecular Cloning of Heat Shock Protein 60 (SpHSP60) from Schizothorax prenanti and the Gene Expressions of Four SpHSPs during Lipopolysaccharide (LPS) Infection - Jianlu Zhang; Jiqin Huang; Cheng Fang; Wanchun Li; Hu Zhao; Fei Kong; Han Zhang; Hongxing Zhang; Qijun Wang (Fishes, 2022)
Heat shock proteins (HSPs) play a key role in anti-stress and immune processes and are associated with autoimmune diseases. In order to explore the immunological role of HSPs from Schizothorax prenanti (S. prenanti), SpHSP60 was cloned for the first time in this study, and the gene expressions of SpHSP27, SpHSP60, SpHSP70 and SpHSP90 in the hepatopancreas, head kidney, hindgut and spleen were analyzed by quantitative real-time PCR (qPCR) after treatment with lipopolysaccharide (LPS). The open reading frame of the SpHSP60 gene (GenBank accession number ON245159) is 1728 bp. It encodes a protein of 575 amino acids. Its C-terminus is a highly conserved and repeated glycine sequence, which is an important cofactor in ATP binding. Compared with the control group, most of the SpHSPs were significantly upregulated in the tissues examined at 12 or 24 h after LPS challenge. The most abundant expression of SpHSP70 was found in the head kidney at 24 h after LPS injection, followed by SpHSP27 in the spleen at 24 h; both of these SpHSPs displayed strong expression under the LPS stresses, about 20–70 fold more than that of SpHSP60 and SpHSP90. The temporal expression patterns of the four SpHSP genes were different in the four tissues examined. Taken together, the results suggest that SpHSP27, SpHSP60, SpHSP70 and SpHSP90 participate in innate immunity stimulated by LPS, and the response intensity of the SpHSPs was organ-specific, indicating they could provide early warning information against bacterial infection. The findings in our study will contribute to better understanding the biological processes and important roles of SpHSPs involved in defending against pathogenic bacterial challenge.

High Fish Stocking Density Weakens the Effects of Rice-Fish Co-culture on Water Eutrophication and Greenhouse Gas Emissions - Yi Hu; Tong Yang; Yaobin Liu; Fengbo Li; Chunchun Xu; Fuping Fang; Jinfei Feng (Water, Air, & Soil Pollution, 2022)

Distinct assembly mechanisms of microbial sub-communities with different rarity along the Nu River - Song Zhang; Kexin Li; Jinming Hu; Fang Wang; Danhong Chen; Zejin Zhang; Ting Li; Linfeng Li; Juan Tao; Dong Liu; Rongxiao Che (Journal of Soils and Sediments, 2022)

Molecular mechanisms and differences in lynch syndrome developing into colorectal cancer and endometrial cancer based on gene expression, methylation, and mutation analysis - Hongfeng Li; Liwei Sun; Yan Zhuang; Caijuan Tian; Fang Yan; Zhenzhen Zhang; Yuanjing Hu; Pengfei Liu (Cancer Causes & Control, 2022)
Purpose The aim of this study was to screen biomarkers specific to Lynch syndrome (LS) with colorectal cancer (CRC) or endometrial cancer (EC) to explore the mechanisms by which LS develops into CRC and EC and their differences. Methods Differentially expressed or differentially methylated genes and differential mutations were identified in 10 LS, 50 CRC, and 50 EC patients from TCGA, and genes overlapping between LS and CRC or EC (named SGs-LCs and SGs-LEs, respectively) were identified. Afterward, we annotated the enriched GO terms and pathways and constructed a protein–protein interaction (PPI) network. Finally, samples from 10 clinical cases with MSI-H/MSS CRC and EC were collected to verify the mutations and their correlations with five LS pathogenic genes in the SGs-LCs and SGs-LEs. Results A total of 494 SGs-LCs and 104 SGs-LEs were identified and enriched in 106 and 14 GO terms, respectively. There were great differences in the gene count and enriched terms between SGs-LCs and SGs-LEs. In the PPI network, SST , GCG , SNAP25 , and NPY had the highest degree of connection among the SGs-LCs, and KIF20A and NUF2 had the highest degree of connection among the SGs-LE. In the SGs-LCs and SGs-LEs, the genes whose expression levels affected the survival of LS, CRC or EC patients were quite different. Conclusions COL11A1 was found to be mutated in MSS CRC patients, similar to the mutations of MSH6 . SST , GCG , SNAP25 , and NPY may be biomarkers for the development of LS into CRC, and KIF20A and NUF2 may be markers of LS developing into EC.

Abnormal functional connectivity of the salience network in insomnia - Yongxin Cheng; Ting Xue; Fang Dong; Yiting Hu; Mi Zhou; Xiaojian Li; Ruoyan Huang; Xiaoqi Lu; Kai Yuan; Dahua Yu (Brain Imaging and Behavior, 2022)

Cancerous Inhibitor of Protein Phosphatase 2A (CIP2A): Could It Be a Promising Biomarker and Therapeutic Target in Parkinson’s Disease? - Sijia Yin; Chao Han; Yun Xia; Fang Wan; Junjie Hu; Liang Kou; Yadi Sun; Jiawei Wu; Yunna Li; Qiulu Zhou; Nian Xiong; Jinsha Huang; et al. (Molecular Neurobiology, 2022)
Parkinson’s disease (PD) is an incurable neurodegenerative disease characterized by aggregation of pathological alpha-synuclein (α-syn) and loss of dopaminergic neuron in the substantia nigra. Inhibition of phosphorylation of the α-syn has been shown to mediate alleviation of PD-related pathology. Protein phosphatase 2A (PP2A), an important serine/threonine phosphatase, plays an essential role in catalyzing dephosphorylation of the α-syn. Here, we identified and validated cancerous inhibitor of PP2A (CIP2A), as a potential diagnostic biomarker for PD. Our data showed that plasma CIP2A concentrations in PD patients were significantly lower compared to age- and sex-matched controls, 1.721 (1.435–2.428) ng/ml vs 3.051(2.36–5.475) ng/ml, p < 0.0001. The area under the curve of the plasma CIP2A in distinguishing PD from the age- and sex-matched controls was 0.776. In addition, we evaluated the role of CIP2A in PD-related pathogenesis in PD cellular and MPTP-induced mouse model. The results demonstrated that CIP2A is upregulated in PD cellular and MPTP-induced mouse models. Besides, suppression of the CIP2A expression alleviates rotenone induced aggregation of the α-syn as well as phosphorylation of the α-syn in SH-SY5Y cells, which is associated with increased PP2A activity. Taken together, our data demonstrated that CIP2A plays an essential role in the mechanisms related to PD development and might be a novel PD biomarker.

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

SYL3-k increases style length and yield of F1 seeds via enhancement of endogenous GA4 content in Oryza sativa L. pistils - Xiaojing Dang; Yuanqing Zhang; Yulong Li; Siqi Chen; Erbao Liu; Bingjie Fang; Qiangming Liu; Dong She; Zhiyao Dong; Zhilan Fan; Dalu Li; Hui Wang; et al. (Theoretical and Applied Genetics, 2022)
Key message SYL3-k allele increases the outcrossing rate of male sterile line and the yield of hybrid F 1 seeds via enhancement of endogenous GA 4 content in Oryza sativa L. pistils. The change in style length might be an adaptation of rice cultivation from south to north in the northern hemisphere. Abstract The style length (SYL) in rice is one of the major factors influencing the stigma exertion, which affects the outcross rate of male sterile line and the yield of hybrid F 1 seeds. However, the biological mechanisms underlying SYL elongation remain elusive. Here, we report a map-based cloning and characterisation of the allele qSYL3-k . The qSYL3-k allele encodes a MADS-box family transcription factor, and it is expressed in various rice organs. The qSYL3-k allele increases SYL via the elongation of cell length in the style, which is associated with a higher GA 4 content in the pistil. The expression level of OsGA3ox2 in pistils with qSYL3-k alleles is significantly higher than that in pistils with qSYL3-n allele on the same genome background of Nipponbare. The yield of F 1 seeds harvested from plants with 7001S SYL3−k alleles was 16% higher than that from plants with 7001S SYL3−n allele. The sequence data at the qSYL3 locus in 136 accessions showed that alleles containing the haplotypes qSYL3 AA , qSYL3 AG , and qSYL3 GA increased SYL, whereas those containing the haplotype qSYL3 GG decreased it. The frequency of the haplotype qSYL3 GG increases gradually from the south to north in the northern hemisphere. These findings will facilitate improvement in SYL and yield of F 1 seeds henceforward.

Enhanced removal of aqueous chromium(VI) by KOH-activated soybean straw-based carbon - Xiaohong Guo; Weiwei Hu; Zheng Gu; Jiali Li; Zongfan Xie; Caixia Fang; Haisheng Tao (Water, Air, & Soil Pollution, 2021)

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Higenamine mitigates interleukin-1β-induced human nucleus pulposus cell apoptosis by ROS-mediated PI3K/Akt signaling - Xiaojuan Zhu; Shichao Liu; Zhijiao Cao; Lei Yang; Fang Lu; Yulan Li; Lili Hu; Xiaoliang Bai (Molecular and Cellular Biochemistry, 2021)

Higher ammonium-to-nitrate ratio shapes distinct soil nitrifying community and favors the growth of Moso bamboo in contrast to broadleaf tree species - Xiaoyan Hu; Xingmeng Wang; Touqeer Abbas; Tao Fang; Danni Miao; Yongfu Li; Scott X. Chang; Yongchun Li (Biology and Fertility of Soils, 2021)

Implantation of Bone Marrow Mesenchymal Stem Cells into Small Intestinal Submucosa Improves Bile Duct Injury in Rabbits - Ying Li; Piao Wang; Xiao-dong Hu; Jing-da Zeng; Cheng Fang; Yu Gan; Fang-yi Peng; Xiao-li Yang; De Luo; Bo Li; Song Su (Tissue Engineering and Regenerative Medicine, 2021)

Genipin Attenuates Tau Phosphorylation and Aβ Levels in Cellular Models of Alzheimer’s Disease - Meiting Li; Nan Cai; Liang Gu; Lijun Yao; Decheng Bi; Weishan Fang; Zhijian Lin; Yan Wu; Hong Xu; Hui Li; Zhangli Hu; Xu Xu (Molecular Neurobiology, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

A Case Study of Whistle Detection and Localization for Humpback Dolphins in Taiwan - Ching-Tang Hung; Wei-Yen Chu; Wei-Lun Li; Yen-Hsiang Huang; Wei-Chun Hu; Chi-Fang Chen (Journal of Marine Science and Engineering, 2021)
In recent years, Taiwan’s government has focused on policies regarding offshore wind farming near the Indo-Pacific humpback dolphin habitat, where marine mammal observation is a critical consideration. The present research developed an algorithm called National Taiwan University Passive Acoustic Monitoring (NTU_PAM) to assist marine mammal observers (MMOs). The algorithm performs whistle detection processing and whistle localization. Whistle detection processing is based on image processing and whistle feature extraction; whistle localization is based on the time difference of arrival (TDOA) method. To test the whistle detection performance, we used the same data to compare NTU_PAM and the widely used software PAMGuard. To test whistle localization, we designed a real field experiment where a sound source projected simulated whistles, which were then recorded by several hydrophone stations. The data were analyzed to locate the moving path of the source. The results show that localization accuracy was higher when the sound source position was in the detection region composed of hydrophone stations. This paper provides a method for MMOs to conveniently observe the migration path and population dynamics of cetaceans without ecological disturbance.

Functionally divergent growth, biomass allocation and root distribution of two xerophytic species in response to varying soil rock fragment content - Hui Hu; Fang Lan Li; M. Luke McCormack; Long Huang; Wei Kai Bao (Plant and Soil, 2021)

Petroleum contamination significantly changes soil microbial communities in three oilfield locations in Delta State, Nigeria - Macdonald Ogorm Mafiana; Xiao-Hu Kang; Yan Leng; Li-Fang He; Shi-Weng Li (Environmental Science and Pollution Research, 2021)

Carbon and nitrogen budget in fish-polychaete integrated aquaculture system - Fawen Hu; Ming Sun; Jinghui Fang; Guodong Wang; Li Li; Fengxiang Gao; Yuxia Jian; Xue Wang; Guangbin Liu; Yan Zou; Wen Guo (Journal of Oceanology and Limnology, 2021)

Recent progress in induced pluripotent stem cell-derived 3D cultures for cardiac regeneration - Kai-Li Wang; Qi Xue; Xun-Hong Xu; Fang Hu; Hong Shao (Cell and Tissue Research, 2021)

An active-passive fusion strategy and accuracy evaluation for shallow water bathymetry based on ICESat-2 ATLAS laser point cloud and satellite remote sensing imagery - Bincai Cao; Yong Fang; Li Gao; Haiyan Hu; Zhengzhi Jiang; Bijiao Sun; Lele Lou (International Journal of Remote Sensing, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Restraint of Bagging on Fruit Skin Coloration in on-Tree Kiwifruit (Actinidia arguta) - Yukuo Li; Xiujuan Qi; Wen Cui; Miaomiao Lin; Chengkui Qiao; Yunpeng Zhong; Jinbao Fang; Chungen Hu (Journal of Plant Growth Regulation, 2021)

Identification of QTLs associated with the anaerobic germination potential using a set of Oryza nivara introgression lines - Licheng Liu; Xiaoxiang Li; Sanxiong Liu; Jun Min; Wenqiang Liu; Xiaowu Pan; Baohua Fang; Min Hu; Zhongqi Liu; Yongchao Li; Haiqing Zhang (Genes & Genomics, 2021)

Ochratoxin A induces nephrotoxicity in vitro and in vivo via pyroptosis - Hu Li; Xinru Mao; Kai Liu; Jiahao Sun; Benrui Li; Rahmani Mohammad Malyar; Dandan Liu; Cuiling Pan; Fang Gan; Yunhuan Liu; Kehe Huang; Xingxiang Chen (Archives of Toxicology, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Effects of fenvalerate concentrations and its chiral isomers on bacterial community structure in the sediment environment of aquaculture ponds - Chao Song; Jingwei Zhang; Xi Chen; Gengdong Hu; Limin Fan; Guang Yang; Tian Li; Liping Qiu; Jiazhang Chen; Longxiang Fang (Environmental Science and Pollution Research, 2021)

Long-term Outcomes and Risk Factors Related to Hydrocephalus After Intracerebral Hemorrhage - Rong Hu; Chao Zhang; Jiesheng Xia; Hongfei Ge; Jun Zhong; Xuanyu Fang; Yongjie Zou; Chuan Lan; Lan Li; Hua Feng (Translational Stroke Research, 2021)

Hypoglycemic mechanism of polysaccharide from Cyclocarya paliurus leaves in type 2 diabetic rats by gut microbiota and host metabolism alteration - Qiqiong Li; Jielun Hu; Qixing Nie; Xiao Chang; Qingying Fang; Junhua Xie; Haishan Li; Shaoping Nie (Science China Life Sciences, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

The bioaerosols emitted from toilet and wastewater treatment plant: a literature review - Mengmeng Lou; Shuai Liu; Chunjie Gu; Huimin Hu; Zhengkun Tang; Yaopeng Zhang; Chenye Xu; Fang Li (Environmental Science and Pollution Research, 2021)

Cryptococcal Meningitis: A Rare Complication in HIV-Negative Patients with Nephrotic Syndrome in A Chinese Teaching Hospital - Dongying Hu; Qilong Zhang; Weiwei Jiang; Amir Arastehfar; Macit Ilkit; Wenjie Fang; Hang Li; Xianzhen Chen; Lei Zhang; Xiaojing Li; Weihua Pan; Wanqing Liao (Mycopathologia, 2020)

Vertical fine-root distributions in five subalpine forest types shifts with soil properties across environmental gradients - Fang Lan Li; M. Luke McCormack; Xin Liu; Hui Hu; De Feng Feng; Wei Kai Bao (Plant and Soil, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

Experimental and theoretical study of mechanical properties of root-soil interface for slope protection - Li-jun Su; Bing-li Hu; Qi-jun Xie; Fang-wei Yu; Chong-lei Zhang (Journal of Mountain Science, 2020)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Aging exacerbates impairments of cerebral blood flow autoregulation and cognition in diabetic rats - Shaoxun Wang; Wenshan Lv; Huawei Zhang; Yedan Liu; Longyang Li; Joshua R. Jefferson; Ya Guo; Man Li; Wenjun Gao; Xing Fang; Ian A. Paul; Grazyna Rajkowska; et al. (GeroScience, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Different experiences of two PRRT2-associated self-limited familial infantile epilepsy - Qianlei Zhao; Zhenwei Liu; Ying Hu; Shiyu Fang; Feixia Zheng; Xiucui Li; Feng Li; Zhongdong Lin (Acta Neurologica Belgica, 2020)
To analyze the clinical characteristics and PRRT2 gene mutation of self-limited familial infantile epilepsy and evaluate the treatment responses of different antiepileptic drugs in self-limited familial infantile epilepsy. We reviewed the clinical feature and genetic mutation results and treatment responses of two sibling sisters. They were detected with the PRRT2 gene mutation through Sanger sequencing. Elder sister was treated with oxcarbazepine oral suspension, while younger sister was treated with levetiracetam oral solution. The two sibling sisters exhibited PRRT2 heterozygous mutation inherited from their mother in c.649dupC p.(Arg217fs). Oxcarbazepine oral suspension had an immediate effect on the elder sister who was treated with it. However, levetiracetam oral solution had no effect on younger sister even though the dose was increased, but she got seizure-free after turning to oxcarbazepine oral suspension. Oxcarbazepine, which plays the mechanism of the sodium channel blockers, has a more significant effect than levetiracetam, which has no mechanism of the sodium channel blockers in self-limited familial infantile epilepsy. The PRRT2 gene of infantile epileptic patients with a family history of infantile convulsions or paroxysmal kinesigenic dyskinesia(PKD) could be detected by sanger sequencing and a biomarker to select antiepileptic drugs which play the mechanism of the sodium channel blockers could be utilized.

Sub‐seasonal prediction of rainfall over the South China Sea and its surrounding areas during spring–summer transitional season - Qingquan Li; Juanhuai Wang; Song Yang; Fang Wang; Jie Wu; Yamin Hu (International Journal of Climatology, 2020)
The sub‐seasonal characteristics and prediction of rainfall over the South China Sea and surrounding areas during spring–summer transitional season (April–May–June) are investigated using a full set of hindcasts generated by the Dynamic Extended Range Forecast operational system version 2.0 (DERF2.0) of Beijing Climate Center, China Meteorological Administration. The onset and development of Asian summer monsoon and the seasonal migration of rain belt over East Asia can be well depicted by the model hindcasts at various leads. However, there exist considerable differences between model results and observations, and model biases depend not only on the lead time, but also on the stage of monsoon evolution. In general, forecast skill drops with increasing lead time but rises again after lead time becomes longer than 30 days, possibly associated with the effect of slowly‐varying forcing or atmospheric variability. An abrupt turning point of bias development appears around mid‐May when bias growths of wind and precipitation exhibit significant changes over the northwestern Pacific and South Asia, especially over the Bay of Bengal and the South China Sea. This abrupt bias change is reasonably captured by the first two modes of multivariate empirical orthogonal function analysis, which reveals several important features associated with the bias change. This analysis may provide useful information for further improving model performance in sub‐seasonal rainfall prediction.

Increased litter input significantly changed the total and active microbial communities in degraded grassland soils - Rongxiao Che; Dong Liu; Jinling Qin; Fang Wang; Weijin Wang; Zhihong Xu; Linfeng Li; Jinming Hu; Iman Tahmasbian; Xiaoyong Cui (Journal of Soils and Sediments, 2020)

Methionine Sulfoxide Reductases Are Related to Arsenic Trioxide-Induced Oxidative Stress in Mouse Liver - Gaolong Zhong; Fang Wan; Hao Yan; Zhijun Ning; Congcong Wang; Ying Li; Jiaqiang Pan; Zhaoxin Tang; Zengming Yang; Riming Huang; Lianmei Hu (Biological Trace Element Research, 2020)

Determination of cadmium in rice bran oils by ICP-MS with rapid ultrasound-assisted acid leaching extraction - Zhiying Shao; Mei Xue; Qin Liu; Peng Li; Yong Fang; Qiuhui Hu (Journal of Consumer Protection and Food Safety, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

High-carbohydrate diet promotes the adaptation to acute hypoxia in zebrafish - Qiang Ma; Chun-Ting Hu; Junjiayu Yue; Yuan Luo; Fang Qiao; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2020)

Expression profiles of three crustin-like genes in Litopenaeus vannamei under Vibrio harveyi infection - Mao-Cang Yan; Yao-Hua Wang; De-Wei Ji; Fang Li; Li-Hua Hu; Min Zhang (Aquaculture International, 2020)

Dopamine D2 Receptor-Mediated Modulation of Rat Retinal Ganglion Cell Excitability - Ning Yin; Yu-Long Yang; Shuo Cheng; Hong-Ning Wang; Xin Hu; Yanying Miao; Fang Li; Zhongfeng Wang (Neuroscience Bulletin, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Impact of Maternal Selenium Supplementation from Late Gestation and Lactation on Piglet Immune Function - Ning-ya Li; Zhi-jian Sun; Abdur Rahman Ansari; Lei Cui; Ya-fang Hu; Zi-wei Li; Mickael Briens; Lei Kai; Lv-hui Sun; Niel A. Karrow; Hua-zhen Liu (Biological Trace Element Research, 2020)

Phylogeography and population dynamics of an endemic oak (Quercus fabri Hance) in subtropical China revealed by molecular data and ecological niche modeling - Xiao-Dan Chen; Jia Yang; Li Feng; Tao Zhou; Hao Zhang; Hui-Min Li; Guo-Qing Bai; Xu Meng; Zhong-Hu Li; Gui-Fang Zhao (Tree Genetics & Genomes, 2020)

Genetic dissection of yield-related traits via genome-wide association analysis across multiple environments in wild soybean (Glycine soja Sieb. and Zucc.) - Dezhou Hu; Huairen Zhang; Qing Du; Zhenbin Hu; Zhongyi Yang; Xiao Li; Jiao Wang; Fang Huang; Deyue Yu; Hui Wang; Guizhen Kan (Planta, 2020)

Ketamine Alleviates Fear Generalization Through GluN2B-BDNF Signaling in Mice - Muhammad Asim; Bo Hao; Yu-Han Yang; Bu-Fang Fan; Li Xue; Yan-Wei Shi; Xiao-Guang Wang; Hu Zhao (Neuroscience Bulletin, 2020)

miR-142a-3p promotes the proliferation of porcine hemagglutinating encephalomyelitis virus by targeting Rab3a - Peng Fan; Jiyu Guan; Wenqi He; Xiaoling Lv; Shiyu Hu; Yungang Lan; Kui Zhao; Feng Gao; Fang Li; Gencheng Fan; Hongbin He; Zi Li (Archives of Virology, 2020)

The application of the ‘Gene-deletor’ technology in banana - Chun-hua Hu; Qiao-song Yang; Xiu-hong Shao; Tao Dong; Fang-cheng Bi; Chun-yu Li; Gui-ming Deng; Yi Li; Gan-jun Yi; Tong-xin Dou (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Banana ( Musa spp.) is an important tropical crop. Banana industry is under biotic and abiotic stresses such as Fusarium wilt, typhoon, cold stress. Genetic engineering offers a powerful strategy to create germplasm of banana with enhanced resistance. The safety of genetically modified organisms has become a bottleneck restricting the popularization and application of genetically modified technology. In this study, a candidate promoter, LEAFY (LFY) for expression and flower initiation in Arabidopsis , was cloned and constructed to ‘Gene-deletor’ vector. Histochemical β-glucuronidase (GUS) staining results showed that the ‘Gene-deletor’ vector driven by LFY promoter could lead to 88.5% excision efficiency from Arabidopsis seeds based on more than 200 T 3 progeny examined per event. GUS staining was found to be partially negative in transgenic bananas, however, polymerase chain reaction could still detect the presence of large fragments of the vector. These results suggest that although LFY promoter could not completely drive the ‘Gene-deletor’ vector to achieve the effect of complete elimination of exogenous gene in bananas, its efficiency of eliminating exogenous gene laid a theoretical foundation for cloning banana fruit-specific promoters, that is, ‘non-transgenic’ GM bananas.

A simple method of depressing numerical dissipation effects during wave simulation within the Euler model - Zhe Hu; Xiaoying Zhang; Weicheng Cui; Fang Wang; Xiaowen Li; Yan Li (Acta Oceanologica Sinica, 2020)

Origin of Pumice in Sediments from the Middle Okinawa Trough: Constraints from Whole-Rock Geochemical Compositions and Sr-Nd-Pb Isotopes - Xue Fang; Zhigang Zeng; Siyi Hu; Xiaohui Li; Zuxing Chen; Shuai Chen; Bowen Zhu (Journal of Marine Science and Engineering, 2019)
Frequent volcanic activity has occurred in the Okinawa Trough (OT) during the late Quaternary, which attracted much attention to the origin of volcanic rocks. Pumice collected from the seafloor has been extensively investigated, whereas few studies paid attention to the pumice in the sediment. The geochemical compositions of pumice preserved in sediments generally provide insight into past volcanic activity and regional magmatism. Here, we present major and trace element compositions and Sr-Nd-Pb isotope data, together with the established age framework for pumice samples recovered from sediment core S9 in the middle OT (MOT) to investigate their possible formation. Compositionally, the S9 pumice samples are dacite and are characterized by relatively higher Sr (87Sr/86Sr = 0.70480–0.70502) and Pb (206Pb/204Pb = 18.321-18.436, 207Pb/204Pb = 15.622–15.624, and 208Pb/204Pb = 38.52–38.63) and lower Nd (143Nd/144Nd = 0.51272–0.51274) isotope compositions than basalts from the MOT. The geochemical compositions of pumice clasts from different layers of core S9 display no temporal variation trends and vary within narrow ranges. On the basis of the geochemical characteristics of S9 pumice samples, we infer that the parent magma of these samples might generate from hybrid magma through an extensive fractional crystallization process. The Indian Ocean MORB-type mantle was first metasomatized by the subducted Philippine Sea sediments to form the primitive magma; then, followed by assimilation of a small amount of lower crustal component occurred in the lower crust. The long-term magmatism and relatively consistent isotopic compositions indicate that a magma chamber might have existed in the lower crust of the MOT between 11.22 and 12.96 cal. ka BP.

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

The mechanism of damage in the midgut of Bombyx mori after chlorantraniliprole exposure - Jiahuan Hu; Mengxue Li; Zhengting Lu; Tingting Mao; Jian Chen; Hui Wang; Jianwei Qu; Yilong Fang; Xiaoyu Cheng; Jinxin Li; Fanchi Li; Bing Li (Ecotoxicology, 2019)

Soil organic carbon components in inner Mongolian shrub-encroached grasslands - Luhong Zhou; Haihua Shen; Yunping Xu; He Li; Leiyi Chen; Yinghui Wang; Pujin Zhang; Xia Zhao; Taoyu Liu; Huifeng Hu; Jingyun Fang (Plant and Soil, 2019)

Behavioural, physiological and molecular changes in alloparental caregivers may be responsible for selection response for female reproductive investment in honey bees - Fan Wu; Chuan Ma; Bin Han; Lifeng Meng; Han Hu; Yu Fang; Mao Feng; Xufeng Zhang; Olav Rueppell; Jianke Li (Molecular Ecology, 2019)
Reproductive investment is a central life history variable that influences all aspects of life. Hormones coordinate reproduction in multicellular organisms, but the mechanisms controlling the collective reproductive investment of social insects are largely unexplored. One important aspect of honey bee ( Apis mellifera ) reproductive investment consists of raising female‐destined larvae into new queens by alloparental care of nurse bees in form of royal jelly provisioning. Artificial selection for commercial royal jelly production over 40 years has increased this reproductive investment by an order of magnitude. In a cross‐fostering experiment, we establish that this shift in social phenotype is caused by nurse bees. We find no evidence for changes in larval signalling. Instead, the antennae of the nurse bees of the selected stock are more responsive to brood pheromones than control bees. Correspondingly, the selected royal jelly bee nurses are more attracted to brood pheromones than unselected control nurses. Comparative proteomics of the antennae from the selected and unselected stocks indicate putative molecular mechanisms, primarily changes in chemosensation and energy metabolism. We report expression differences of several candidate genes that correlate with the differences in reproductive investment. The functional relevance of these genes is supported by demonstrating that the corresponding proteins can competitively bind one previously described and one newly discovered brood pheromone. Thus, we suggest several chemosensory genes, most prominently OBP16 and CSP4, as candidate mechanisms controlling queen rearing, a key reproductive investment, in honey bees. These findings reveal novel aspects of pheromonal communication in honey bees and explain how sensory changes affect communication and lead to a drastic shift in colony‐level resource allocation to sexual reproduction. Thus, pheromonal and hormonal communication may play similar roles for reproductive investment in superorganisms and multicellular organisms, respectively.

Identification of favorable alleles for rice seedling anoxic tolerance using natural and bi-parental populations - Xiaojing Dang; Yanhui Li; Yuanqing Zhang; Jie Ji; Dalu Li; Xiaoxiao Hu; Shangshang Zhu; Zhiyao Dong; Erbao Liu; Hui Wang; Bingjie Fang; Delin Hong (Euphytica, 2019)

The Molecular Mechanisms of Protective Role of Se on the G0/G1 Phase Arrest Caused by AFB1 in Broiler’s Thymocytes - Ke Guan; Hang Li; Zhicai Zuo; Fengyuan Wang; Ping Hu; Xi Peng; Jing Fang; Hengmin Cui; Gang Shu; Ping Ouyang (Biological Trace Element Research, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Tolerance of two apple rootstocks to short-term salt stress: focus on chlorophyll degradation, photosynthesis, hormone and leaf ultrastructures - Yan-fang Zhu; Yu-xia Wu; Ya Hu; Xu-mei Jia; Tong Zhao; Li Cheng; Yan-xiu Wang (Acta Physiologiae Plantarum, 2019)

Coinfection of a lingual lesion with bovine papular stomatitis virus and bovine papillomavirus - Wei Zhu; Takeshi Haga; Dongfang Yuan; Ken-ichi Watanabe; James K. Chambers; Nannan Gao; Kazuyuki Uchida; Shushan Fan; Fang Li; Mingcai Yang; Junzo Norimine; Shilin Hu; et al. (Archives of Virology, 2019)

Diltiazem used as a tacrolimus-sparing agent for treatment of pediatric patients with refractory nephrotic syndrome: a case report and retrospective analysis - Jie-Yu Sun; Ya-Hui Hu; Hong-Li Guo; Xia Jing; Ze-Jun Xu; Fang Sun; Hui-Lei Guo; Xuan-Sheng Ding; Feng Chen; Jing Xu (European Journal of Clinical Pharmacology, 2019)

Natural variation of ZmHKT1 affects root morphology in maize at the seedling stage - Pengcheng Li; Ting Pan; Houmiao Wang; Jie Wei; Minjun Chen; Xiaohong Hu; Yu Zhao; Xiaoyi Yang; Shuangyi Yin; Yang Xu; Huimin Fang; Jun Liu; et al. (Planta, 2019)

Quaternary phosphonium cationic ionic liquid/porous metal–organic framework as an efficient catalytic system for cycloaddition of carbon dioxide into cyclic carbonates - Yu Lin Hu; Rui Li Zhang; Dong Fang (Environmental Chemistry Letters, 2019)

Targeting the gut microbiota by dietary nutrients: A new avenue for human health - Daotong Li; Pan Wang; Pengpu Wang; Xiaosong Hu; Fang Chen (Critical Reviews in Food Science and Nutrition, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Transcriptome analysis in Malus halliana roots in response to iron deficiency reveals insight into sugar regulation - Ya Hu; Yan-fang Zhu; Ai-xia Guo; Xu-mei Jia; Li Cheng; Tong Zhao; Yan-xiu Wang (Molecular Genetics and Genomics, 2018)

Complete plastid genome of Bupleurum boissieuanum, an endemic herb plant in western China - Ying Wu; Tian-Ze Zhang; Dai-Yu Qiu; Qiang Chai; Wei-Bing Fan; Zhong-Hu Li; Min-Feng Fang (Conservation Genetics Resources, 2018)

The Protective Role of Selenium in AFB1-Induced Tissue Damage and Cell Cycle Arrest in Chicken’s Bursa of Fabricius - Ping Hu; Zhicai Zuo; Fengyuan Wang; Xi Peng; Ke Guan; Hang Li; Jing Fang; Hengmin Cui; Gang Su; Ping Ouyang; Yi Zhou (Biological Trace Element Research, 2018)

Method for real-time self-calibrating GLONASS code inter-frequency bias and improvements on single point positioning - Liang Chen; Min Li; Zhigang Hu; Chenghe Fang; Changjiang Geng; Qile Zhao; Chuang Shi (GPS Solutions, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Regulation of Thermostable Direct Hemolysin and Biofilm Formation of Vibrio parahaemolyticus by Quorum-Sensing Genes luxM and luxS - Muhan Guo; Zhijia Fang; Lijun Sun; Dongfang Sun; Yaling Wang; Can Li; Rundong Wang; Yang Liu; Hanqiao Hu; Ying Liu; Defeng Xu; Ravi Gooneratne (Current Microbiology, 2018)

Pyrite textures and compositions from the Zhuangzi Au deposit, southeastern North China Craton: implication for ore-forming processes - Xing-Hui Li; Hong-Rui Fan; Kui-Feng Yang; Pete Hollings; Xuan Liu; Fang-Fang Hu; Ya-Chun Cai (Contributions to Mineralogy and Petrology, 2018)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

MiR-519d-3p suppresses breast cancer cell growth and motility via targeting LIM domain kinase 1 - Dengfeng Li; Hongming Song; Tianqi Wu; Dan Xie; Jiashu Hu; Junyong Zhao; Qiang Shen; Lin Fang (Molecular and Cellular Biochemistry, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Semi-automatic geometric correction of airborne hyperspectral push-broom images using ground control points and linear features - Hao Fang; Binlin Hu; Zhongjiang Yu; Huoxi Xu; Chuan He; Aihua Li; Yinnian Liu (International Journal of Remote Sensing, 2018)

Effects of autophagy on acid-sensing ion channel 1a-mediated apoptosis in rat articular chondrocytes - Ya-Ya Xie; Yue Li; Ren-peng Zhou; Bei-Bei Dai; Yue-jiao Qian; Xiao-shan Wu; Jin-fang Ge; Wei Hu; Fei-hu Chen (Molecular and Cellular Biochemistry, 2018)

Impact of International Collaborative Training Programs on Medical Students’ Research Ability - Remila Rezhake; Shang-Ying Hu; Yu-Qian Zhao; Li Zhang; Xue-Lian Zhao; Ayling Z. Dominguez; You-Lin Qiao; Cai-Hong Zhou; Fang-Hui Zhao (Journal of Cancer Education, 2018)

A large lung gene expression study identifying IL1B as a novel player in airway inflammation in COPD airway epithelial cells - Gao Yi; Min Liang; Ming Li; Xiangming Fang; Jifang Liu; Yuxiong Lai; Jitao Chen; Wenxia Yao; Xiao Feng; La Hu; Chunyi Lin; Xinke Zhou; et al. (Inflammation Research, 2018)

Characterization of brown carbon constituents of benzene secondary organic aerosol aged with ammonia - Mingqiang Huang; Jun Xu; Shunyou Cai; Xingqiang Liu; Weixiong Zhao; Changjin Hu; Xuejun Gu; Li Fang; Weijun Zhang (Journal of Atmospheric Chemistry, 2018)

Synaptic Dysfunction in Alzheimer’s Disease: Aβ, Tau, and Epigenetic Alterations - Ke Li; Qing Wei; Fang-Fang Liu; Fan Hu; Ao-ji Xie; Ling-Qiang Zhu; Dan Liu (Molecular Neurobiology, 2018)

Isolation and structure elucidation of a new compound from the fungus Aspergillus flavipes PJ03-11 - Fang Liu; Gang Chen; Li-hua Zhang; Bing Liu; Shaofei Chen; Huiming Hua; Jiao Bai; Hai-feng Wang; Yue-Hu Pei (Natural Product Research, 2018)

ccaA and FBP/SBPase Derived From Cyanobacteria Improved Photosynthetic Capacity in Rice - Han Y. Gong; Yang Li; Gen Fang; Dao H. Hu; Zhao H. Wang; Guang H. Yu; Yang S. Li (Plant Molecular Biology Reporter, 2017)

MXR7 facilitates liver cancer metastasis via epithelial-mesenchymal transition - Guishuai Lv; Yexiong Tan; Hongwei Lv; Tian Fang; Changzheng Wang; Ting Li; Yanting Yu; Congli Hu; Wen Wen; Hongyang Wang; Wen Yang (Science China Life Sciences, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Changes in Histopathology, Enzyme Activities, and the Expression of Relevant Genes in Zebrafish (Danio rerio) Following Long-Term Exposure to Environmental Levels of Thallium - Li-Ping Hou; Yang Yang; Hu Shu; Guang-Guo Ying; Jian-Liang Zhao; Yi-Bing Chen; Yong-Heng Chen; Gui-Zhen Fang; Xin Li; Ji-Sheng Liu (Bulletin of Environmental Contamination and Toxicology, 2017)

Hydroxy-Al and cell-surface negativity are responsible for the enhanced sensitivity of Rhodotorula taiwanensis to aluminum by increased medium pH - Xue Qiang Zhao; Xue Min Bao; Chao Wang; Zuo Yi Xiao; Zhen Min Hu; Chun Li Zheng; Ren Fang Shen (Archives of Microbiology, 2017)

Occurrence and genetic diversity analysis of apple stem pitting virus isolated from apples in China - Guo-Jun Hu; Ya-Feng Dong; Zun-Ping Zhang; Xu-Dong Fan; Fang Ren; Zhengnan Li (Archives of Virology, 2017)

Efficacy and safety of escitalopram in treatment of severe depression in Chinese population - Tianmei Si; Gang Wang; Fude Yang; Yiru Fang; Maosheng Fang; Jijun Li; Jicheng Dong; Xinhua Shen; Jianmin Zhuo; Qing Rui; Jinan Wang; Hu Cuili (Metabolic Brain Disease, 2017)

A Brillouin scattering study of hydrous basaltic glasses: the effect of H2O on their elastic behavior and implications for the densities of basaltic melts - Lei Wu; De-Bin Yang; Jun-Xiu Liu; Bo Hu; Hong-Sen Xie; Fang-Fei Li; Yang Yu; Wen-Liang Xu; Chun-Xiao Gao (Physics and Chemistry of Minerals, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Effect of potential role of p53 on embryo development arrest induced by H2O2 in mouse - De-Bao Hu; Zhong-Shu Li; Ihsan Ali; Li-Jie Xu; Nan-Zhu Fang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Differentiating Patients with Parkinson’s Disease from Normal Controls Using Gray Matter in the Cerebellum - Ling-Li Zeng; Liang Xie; Hui Shen; Zhiguo Luo; Peng Fang; Yanan Hou; Beisha Tang; Tao Wu; Dewen Hu (The Cerebellum, 2017)

A New Perspective for Parkinson’s Disease: Circadian Rhythm - Siyue Li; Yali Wang; Fen Wang; Li-Fang Hu; Chun-Feng Liu (Neuroscience Bulletin, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

Complete nucleotide sequence of a new variant of grapevine fanleaf virus from northeastern China - Jun Zhou; Xudong Fan; Yafeng Dong; Zunping Zhang; Fang Ren; Guojun Hu; Zhengnan Li (Archives of Virology, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Erratum to: Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene - Na Qin; Weigang Xu; Lin Hu; Yan Li; Huiwei Wang; Xueli Qi; Yuhui Fang; Xia Hua (Protoplasma, 2016)

Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene - Na Qin; Weigang Xu; Lin Hu; Yan Li; Huiwei Wang; Xueli Qi; Yuhui Fang; Xia Hua (Protoplasma, 2016)

Urban expansion in China and its effect on cultivated land before and after initiating “Reform and Open Policy” - ZengXiang Zhang; QingKe Wen; Fang Liu; XiaoLi Zhao; Bin Liu; JinYong Xu; Ling Yi; ShunGuang Hu; Xiao Wang; LiJun Zuo; Na Li; MinMin Li; et al. (Science China Earth Sciences, 2016)

Urban expansion in China and its spatial-temporal differences over the past four decades - Fang Liu; Zengxiang Zhang; Lifeng Shi; Xiaoli Zhao; Jinyong Xu; Ling Yi; Bin Liu; Qingke Wen; Shunguang Hu; Xiao Wang; Lijun Zuo; Na Li; et al. (Journal of Geographical Sciences, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Dehydration-responsive features of Atrichum undulatum - Ruoyang Hu; Lihong Xiao; Fang Bao; Xuedong Li; Yikun He (Journal of Plant Research, 2016)

Mass spectrometric study of aged benzene secondary organic aerosol in the presence of dry ammonium sulfate - Mingqiang Huang; Jiahui Zhang; Shunyou Cai; Yingmin Liao; Weixiong Zhao; Changjin Hu; Xuejun Gu; Li Fang; Weijun Zhang (Journal of Atmospheric Chemistry, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Effect Comparison of Both Iron Chelators on Outcomes, Iron Deposit, and Iron Transporters After Intracerebral Hemorrhage in Rats - Gaiqing Wang; Weimin Hu; Qingping Tang; Li Wang; Xin-gang Sun; Yanli Chen; Yongfeng Yin; Fang Xue; Zhitang Sun (Molecular Neurobiology, 2016)

Identification of a divergent variant of grapevine berry inner necrosis virus in grapevines showing chlorotic mottling and ring spot symptoms - Xudong Fan; Ni Hong; Zunping Zhang; Zuokun Yang; Fang Ren; Guojun Hu; Zhengnan Li; Jun Zhou; Yafeng Dong; Guoping Wang (Archives of Virology, 2016)

De novo assembly and characterization of the leaf, bud, and fruit transcriptome from the vulnerable tree Juglans mandshurica for the development of 20 new microsatellite markers using Illumina sequencing - Zhuang Hu; Tian Zhang; Xiao-Xiao Gao; Yang Wang; Qiang Zhang; Hui-Juan Zhou; Gui-Fang Zhao; Ma-Li Wang; Keith E. Woeste; Peng Zhao (Molecular Genetics and Genomics, 2016)

Extraction of basic trends of urban expansion in China over past 40 years from satellite images - Qingke Wen; Zengxiang Zhang; Lifeng Shi; Xiaoli Zhao; Fang Liu; Jinyong Xu; Ling Yi; Bin Liu; Xiao Wang; Lijun Zuo; Shunguang Hu; Na Li; et al. (Chinese Geographical Science, 2016)

Phytosterol content and the campesterol:sitosterol ratio influence cotton fiber development: role of phytosterols in cell elongation - Shasha Deng; Ting Wei; Kunling Tan; Mingyu Hu; Fang Li; Yunlan Zhai; Shue Ye; Yuehua Xiao; Lei Hou; Yan Pei; Ming Luo (Science China Life Sciences, 2016)

Variation of molybdenum isotopes in molybdenite from porphyry and vein Mo deposits in the Gangdese metallogenic belt, Tibetan plateau and its implications - Yong Wang; Lian Zhou; Shan Gao; Jian-Wei Li; Zhi-Fang Hu; Lu Yang; Zhao-Chu Hu (Mineralium Deposita, 2016)

Effects of rosiglitazone on proliferation and differentiation of duck preadipocytes - Fang Ding; Jiamin Qiu; Qingqing Li; Jiwei Hu; Chenling Song; Chunchun Han; Hua He; Jiwen Wang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Olfactory Deprivation Hastens Alzheimer-Like Pathologies in a Human Tau-Overexpressed Mouse Model via Activation of cdk5 - Ke Li; Fang-Fang Liu; Chun-Xue He; He-Zhou Huang; Ao-Ji Xie; Fan Hu; Dan Liu; Jian-Zhi Wang; Ling-Qiang Zhu (Molecular Neurobiology, 2016)

Location- and Subunit-Specific NMDA Receptors Determine the Developmental Sevoflurane Neurotoxicity Through ERK1/2 Signaling - Wen-Yuan Wang; Li-Jie Jia; Yan Luo; Hong-Hai Zhang; Fang Cai; Hui Mao; Wei-Cai Xu; Jun-Biao Fang; Zhi-You Peng; Zheng-Wen Ma; Yan-Hong Chen; Juan Zhang; et al. (Molecular Neurobiology, 2016)

First survey of parasitic helminths of goats along the Han River in Hubei Province, China - Xin Yang; Robin B. Gasser; Rui Fang; Jinrong Zeng; Kaixiang Zhu; Mingwei Qi; Zongze Zhang; Li Tan; Weiqiang Lei; Yanqin Zhou; Junlong Zhao; Min Hu (Acta Parasitologica, 2016)
Diseases caused by parasitic helminths cause considerable production and economic losses in livestock worldwide. Understanding the epidemiology of these parasites has important implications for controlling them. The main purpose of the present study was to estimate the prevalence of key parasitic helminths in goats along the Han River in Zhanggang, Hubei Province (from January to December 2014). We used faecal flotation and sedimentation techniques as well as PCR-based DNA sequencing to detect and identify helminths. Results showed that the prevalence of helminths was high throughout the year, particularly for gastrointestinal nematodes. These first findings provide useful baseline information for goat helminths in Zhanggang, and a starting point for the implementation of control programs. With an increased expansion of the goat industry in China, the findings also emphasise the need to undertake prevalence surveys in other regions of China where extensive farming practices are used.

New compound with DNA Topo I inhibitory activity purified from Penicillium oxalicum HSY05 - Bing Liu; Hai-Feng Wang; Li-Hua Zhang; Fang Liu; Feng-Jun He; Jiao Bai; Hui-Ming Hua; Gang Chen; Yue-Hu Pei (Natural Product Research, 2015)

Ectopic expression a tomato KNOX Gene Tkn4 affects the formation and the differentiation of meristems and vasculature - Fang Yan; Guojian Hu; Zhenxin Ren; Wei Deng; Zhengguo Li (Plant Molecular Biology, 2015)

A Successful Attempt to Obtain the Linear Dependence Between One-Photon and Two-Photon Spectral Properties and Hammett Parameters of Various Aromatic Substituents in New π-Extended Asymmetric Organic Chromophores - Nvdan Hu; Yulong Gong; Xinchao Wang; Yao Lu; Guangyue Peng; Long Yang; Shengtao Zhang; Ziping Luo; Hongru Li; Fang Gao (Journal of Fluorescence, 2015)

Nontuberculous mycobacterial osteomyelitis - Sheng Bi; Fei-Shu Hu; Hai-Ying Yu; Kai-Jin Xu; Bei-Wen Zheng; Zhong-Kang Ji; Jun-Jie Li; Mei Deng; Hai-Yang Hu; Ji-Fang Sheng (Infectious Diseases, 2015)

Geochemistry characteristics of the Low Permian sedimentary rocks from central uplift zone, Qiangtang Basin, Tibet: insights into source-area weathering, provenance, recycling, and tectonic setting - Junjie Hu; Qi Li; Nianqiao Fang; Jingyi Yang; Dongsheng Ge (Arabian Journal of Geosciences, 2015)

Classification of estuaries in China based on eutrophication susceptibility to nutrient load - JunLong Li; BingHui Zheng; Yong Liu; Zhen Wu; Fang Liu; JunBo Shao; XuPeng Hu (Science China Earth Sciences, 2015)

Distribution of Yeast Isolates from Invasive Infections and Their In Vitro Susceptibility to Antifungal Agents: Evidence from 299 Cases in a 3-Year (2010 to 2012) Surveillance Study - Wei Li; Yu-an Hu; Fang-qiu Li; Li-ning Shi; Hai-feng Shao; Mei Huang; Ying Wang; Dan-dan Han; Hong Liao; Chun-fang Ma; Guo-yong Zhang (Mycopathologia, 2015)

JcCBF2 gene from Jatropha curcas improves freezing tolerance of Arabidopsis thaliana during the early stage of stress - Linghui Wang; Jihai Gao; Xiaobo Qin; Xiaodong Shi; Lin Luo; Guozhen Zhang; Hongwu Yu; Chenyang Li; Minchao Hu; Qifan Liu; Ying Xu; Fang Chen (Molecular Biology Reports, 2015)

Remote-sensing observations of Typhoon Soulik (2013) forced upwelling and sediment transport enhancement in the northern Taiwan Strait - Yunhai Li; Xiaohui Xu; Xijie Yin; Jianyong Fang; Wenye Hu; Jian Chen (International Journal of Remote Sensing, 2015)

Sulfide oxidation and nitrate reduction for potential mitigation of H2S in landfills - Yuan Fang; Yao Du; Huan Feng; Li-Fang Hu; Dong-Sheng Shen; Yu-Yang Long (Biodegradation, 2015)

Bayesian model averaging for benchmark dose estimation - Susan J. Simmons; Cuixian Chen; Xiaosong Li; Yishi Wang; Walter W. Piegorsch; Qijun Fang; Bonnie Hu; G. Eddie Dunn (Environmental and Ecological Statistics, 2015)

Productivity responses of desert vegetation to precipitation patterns across a rainfall gradient - Fang Li; Wenzhi Zhao; Hu Liu (Journal of Plant Research, 2015)

Enhanced soil washing process for the remediation of PBDEs/Pb/Cd-contaminated electronic waste site with carboxymethyl chitosan in a sunflower oil–water solvent system and microbial augmentation - Mao Ye; Mingming Sun; Jinzhong Wan; Guodong Fang; Huixin Li; Feng Hu; Xin Jiang; Fredrick Orori Kengara (Environmental Science and Pollution Research, 2015)

Effects of added polyacrylamide on changes in water states during the composting of kitchen waste - Yu-Qiang Yang; Zhuo-Xian Chen; Xue-Qing Zhang; Li-Fang Hu; Dong-Sheng Shen; Yu-Yang Long (Environmental Science and Pollution Research, 2015)

In vitro simulation of in vivo pharmacokinetic model with intravenous administration via flow rate modulation - Yuan-cheng Chen; Wang Liang; Jia-li Hu; Gao-li He; Xiao-jie Wu; Xiao-fang Liu; Jing Zhang; Xue-qian Hu (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Terrestrial input and nutrient change reflected by sediment records of the Changjiang River Estuary in recent 80 years - Junlong Li; Binghui Zheng; Xupeng Hu; Yiming Wang; Ye Ding; Fang Liu (Acta Oceanologica Sinica, 2015)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Molecular characterization of the hippeastrum chlorotic ringspot virus L segment and its protein - Ye Xu; Shi-gao Lou; Qiu-fang Li; Qing Hu; Li-peng Sun; Zheng-yue Li; Yong-zhong Li; Ya-ting Liu (Archives of Virology, 2014)

Chemical analysis of aged benzene secondary organic aerosol using aerosol laser time-of-flight mass spectrometer - Mingqiang Huang; Yuehong Lin; Xianying Huang; Xingqiang Liu; Changjin Hu; Xuejun Gu; Weixiong Zhao; Li Fang; Weijun Zhang (Journal of Atmospheric Chemistry, 2014)

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

Effect of LeERF1 and LeERF2 overexpression in the response to salinity of young tomato (Solanumlycopersicum cv. Micro-Tom) seedlings - Nan Hu; Ning Tang; Fang Yan; Mondher Bouzayen; Zhengguo Li (Acta Physiologiae Plantarum, 2014)

Role and Mechanism of Microglial Activation in Iron-Induced Selective and Progressive Dopaminergic Neurodegeneration - Wei Zhang; Zhao-fen Yan; Jun-hua Gao; Li Sun; Xi-yan Huang; Zhuo Liu; Shu-yang Yu; Chen-Jie Cao; Li-jun Zuo; Ze-Jie Chen; Yang Hu; Fang Wang; et al. (Molecular Neurobiology, 2014)

Isolation and characterization of microsatellite loci from Gasterophilus pecorum (Diptera: Gasterophilidae) - Fang Cheng; Jianmei Yang; Dong Zhang; Defu Hu; Hongjun Chu; Jie Cao; Feng Jiang; Lan Bu; Kai Li (Conservation Genetics Resources, 2014)

Identifying novel salt-tolerant genes from Dunaliella salina using a Haematococcus pluvialis expression system - Wen-fang Gong; Li-na Zhao; Bin Hu; Xi-wen Chen; Feng Zhang; Zheng-mao Zhu; De-fu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Influence of hydrophilic amino acids and GC-content on expression of recombinant proteins used in vaccines against foot-and-mouth disease virus in Escherichia coli - Hongfei Wei; Mingli Fang; Min Wan; Hua Wang; Peiyin Zhang; Xiaoping Hu; XiuLi Wu; Ming Yang; Yongsheng Zhang; Lei Zhou; Chengfeng Jiao; Li Hua; et al. (Biotechnology Letters, 2014)

Variability of atlantic meridional overturning circulation in FGOALS-g2 - Wenyu Huang; Bin Wang; Lijuan Li; Li Dong; Pengfei Lin; Yongqiang Yu; Tianjun Zhou; Li Liu; Shiming Xu; Kun Xia; Ye Pu; Lu Wang; et al. (Advances in Atmospheric Sciences, 2014)

The role of sucrose-metabolizing enzymes in pear fruit that differ in sucrose accumulation - Hu Ping Zhang; Ju You Wu; Gai Hua Qin; Gai Fang Yao; Kai Jie Qi; Li Fen Wang; Shao Ling Zhang (Acta Physiologiae Plantarum, 2014)

Identification and characterization of the pig ABIN-1 gene and investigation of its association with reproduction traits - MEIXIA FANG; HONGLI DU; YONGSHENG HU; XIAONING ZHOU; HONGJIA OUYANG; WEI ZHANG; XINZHENG JIA; JUAN LI; YAJUN WANG; QINGHUA NIE; XIQUAN ZHANG (Journal of Genetics, 2013)

Gardiquimod inhibits the expression of calcium-induced differentiation markers in HaCaT cells - Bo Jia; Xin Luo; Feng-Wei Cheng; Lei Li; Dao-Jun Hu; Fang Wang; Sheng-Quan Zhang (Molecular Biology Reports, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Spatio-temporal changes in biomass carbon sinks in China’s forests from 1977 to 2008 - ZhaoDi Guo; HuiFeng Hu; Pin Li; NuYun Li; JingYun Fang (Science China Life Sciences, 2013)

Effects of inorganic seed aerosols on the growth and chemical composition of secondary organic aerosol formed from OH-initiated oxidation of toluene - Mingqiang Huang; Liqing Hao; Xuejun Gu; Changjin Hu; Weixiong Zhao; Zhenya Wang; Li Fang; Weijun Zhang (Journal of Atmospheric Chemistry, 2013)

Combinational biosynthesis of phycocyanobilin using genetically-engineered Escherichia coli - Baosheng Ge; Yan Li; Haixiang Sun; Shuai Zhang; Peijie Hu; Song Qin; Fang Huang (Biotechnology Letters, 2013)

An L-Type Calcium Channel Agonist, Bay K8644, Extends the Window of Intervention Against Ischemic Neuronal Injury - Hong-hai Hu; Shu-ji Li; Pu Wang; Hua-cheng Yan; Xiong Cao; Feng-qin Hou; Ying-ying Fang; Xin-hong Zhu; Tian-ming Gao (Molecular Neurobiology, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

The cloning, characterization, and expression profiling of the LRP8 gene in duck (Anas platyrhynchos) - Shenqiang Hu; Hehe Liu; Zhixiong Pan; Fang Ding; Jie Kou; Liang Li; Jiwen Wang (Molecular and Cellular Biochemistry, 2012)

Microdissection and Microcloning of Chromosome 5 in Gossypium arboreum - Peng Renhai; Liu Fang; Hu Xiao; Wang Chunying; Li Shaohui; Zhang Xiangdi; Wang Yuhong; Wang Kunbo (Plant Molecular Biology Reporter, 2012)

Association between estrogen receptor alpha c.454-397T>C and c.454-351A>G and ischemic stroke risk: a systematic review and meta-analysis - Bing-Hu Li; Li-Li Zhang; Yan-Wei Yin; Yan Pi; Lu Guo; Qing-Wu Yang; Chang-Yue Gao; Chuan-Qin Fang; Jing-Zhou Wang; Jing Xiang; Jing-Cheng Li (Molecular Biology Reports, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Carbon storage and vertical distribution in three shrubland communities in Gurbantünggüt Desert, Uygur Autonomous Region of Xinjiang, Northwest China - Yanming Gong; Yukun Hu; Fei Fang; Yanyan Liu; Kaihui Li; Guangming Zhang (Chinese Geographical Science, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Gibberellic Acid-Insensitive mRNA Transport in Pyrus - Wen-Na Zhang; Lei Gong; Chao Ma; Hai-Yan Xu; Jian-Fang Hu; Takeo Harada; Tian-Zhong Li (Plant Molecular Biology Reporter, 2012)

Improving the discrimination capability of bioaerosols using a dual-channel ultraviolet aerodynamic particle sizer spectrometer - Xiao-Ling Ma; Wei-Xiong Zhao; Jia-Qiang Zhao; Na Li; Hai-Yang Zheng; Li Fang; Fei-Hu Chen; Wei-Jun Zhang (Aerobiologia, 2012)

Determination of the specific interaction between palmatine and bovine serum albumin - Yu Ou-Yang; Xiao-Ling Li; Hong Wang; Min Fang; Yan-Jun Hu (Molecular Biology Reports, 2012)

Association between paraoxonase 2 Ser311Cys polymorphism and ischemic stroke risk: a meta-analysis involving 5,008 subjects - Bing-Hu Li; Li-Li Zhang; Yan-Wei Yin; Yan Pi; Qing-Wu Yang; Chang-Yue Gao; Chuan-Qin Fang; Jing-Zhou Wang; Jing-Cheng Li (Molecular Biology Reports, 2012)

Gene/protein expression level, immunolocalization and binding characteristics of fatty acid binding protein from Clonorchis sinensis (CsFABP) - Lisi Huang; Yue Hu; Yan Huang; Hang Fang; Ran Li; Dong Hu; Wenfang Li; Xuerong Li; Chi Liang; Xinbing Yu (Molecular and Cellular Biochemistry, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Molecular Cloning, Sequence Analysis, and Expression of the Polygalacturonase-inhibiting Protein (PGIP) Gene in Mulberry - Dongqing Hu; Ruiqiang Dai; Yuhua Wang; Yinghua Zhang; Zhaoyue Liu; Rongjun Fang; Weiguo Zhao; Long Li; Qiang Lin; Liu Li (Plant Molecular Biology Reporter, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Identification and characterization of SHORTENED UPPERMOST INTERNODE 1, a gene negatively regulating uppermost internode elongation in rice - Li Zhu; Jiang Hu; Keming Zhu; Yunxia Fang; Zhenyu Gao; Yinghong He; Guangheng Zhang; Longbiao Guo; Dali Zeng; Guojun Dong; Meixian Yan; Jian Liu; et al. (Plant Molecular Biology, 2011)

Microstructures and Photocatalytic Properties of Fe3+/Ce3+ Codoped Nanocrystalline TiO2 Films - Yan-zhen Qu; Ming-ming Yao; Fang Li; Xiao-hu Sun (Water, Air, & Soil Pollution, 2011)

Expression pattern of enzymes related to juvenile hormone metabolism in the silkworm, Bombyx mori L. - Yang Hua-jun; Zhou Fang; Sabhat Awquib; Firdose Ahmad Malik; Bhaskar Roy; Li Xing-hua; Hu Jia-biao; Sun Chun-guang; Yan-shan Niu; Miao Yun-gen (Molecular Biology Reports, 2011)

The genetic profiling of preferentially expressed genes in murine splenic CD8α+ dendritic cells - Tao Li; Wu-Ying Li; Hui-Ling Bai; Hong-Bing Ma; Hu Zhang; Jiang-Mu Zhu; Xiao-Hong Li; Hong-Ying Huang; Yuan-Fang Ma; Xin-Ying Ji (Immunologic Research, 2011)

Expression of Trichoderma viride endoglucanase III in the larvae of silkworm, Bombyx mori L. and characteristic analysis of the recombinant protein - Xing-hua Li; Peng Zhang; Mei-xian Wang; Fang Zhou; Firdose Ahmad Malik; Hua-jun Yang; Roy Bhaskar; Jia-biao Hu; Chun-guang Sun; Yun-gen Miao (Molecular Biology Reports, 2011)

Fluorofenidone attenuates renal interstitial fibrosis in the rat model of obstructive nephropathy - Bing-xin Li; Yi-ting Tang; Wei Wang; Yan-yun Xie; Na-sui Wang; Qiong-jing Yuan; Fang-fang Zhang; Zhang-zhe Peng; Gao-yun Hu; Li-jian Tao (Molecular and Cellular Biochemistry, 2011)

PPARγ Agonist Suppresses TLR4 Expression and TNF-α Production in LPS Stimulated Monocyte Leukemia Cells - Chun-Zhi Wang; Yong Zhang; Xu-Dong Li; Yuan Hu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang; Pei-Qing Liu; Jia-Jun Liu (Cell Biochemistry and Biophysics, 2011)

Screening of Plant Species for Phytoremediation of Uranium, Thorium, Barium, Nickel, Strontium and Lead Contaminated Soils from a Uranium Mill Tailings Repository in South China - Guang-yue Li; Nan Hu; De-xin Ding; Ji-fang Zheng; Yu-long Liu; Yong-dong Wang; Xiao-qin Nie (Bulletin of Environmental Contamination and Toxicology, 2011)

Weight-reducing effect of Acer truncatum Bunge may be related to the inhibition of fatty acid synthase - Wen-Hua Zhao; Li-Fang Gao; Wen Gao; Yong-Sheng Yuan; Chun-Chun Gao; Li-Ge Cao; Zi-Zheng Hu; Jian-Qiang Guo; Ying-Xia Zhang (Natural Product Research, 2011)

Synthesis and Spectroscopy of Novel Branched Fluorescent Dyes Containing Benzophenone Parts and the Possibility as Fluorescence Probes - Fang Gao; Lanying Niu; Nvdan Hu; Jianchao Wang; Hongru Li; Shengtao Zhang (Journal of Fluorescence, 2011)

Cloning and expression of a cellulase gene in the silkworm, Bombyx mori by improved Bac-to-Bac/BmNPV baculovirus expression system - Xing-hua Li; Dan Wang; Fang Zhou; Hua-jun Yang; Roy Bhaskar; Jia-biao Hu; Chun-guang Sun; Yun-gen Miao (Molecular Biology Reports, 2010)

PI3K-dependent host cell actin rearrangements are required for Cronobacter sakazakii invasion of human brain microvascular endothelial cells - Qiang Li; Wei-Dong Zhao; Ke Zhang; Wen-Gang Fang; Ying Hu; Shao-Hui Wu; Yu-Hua Chen (Medical Microbiology and Immunology, 2010)

Construction and Preliminary Analysis of a Deep-Sea Sediment Metagenomic Fosmid Library from Qiongdongnan Basin, South China Sea - Yongfei Hu; Chengzhang Fu; Yeshi Yin; Gong Cheng; Fang Lei; Xi Yang; Jing Li; Elizabeth Jane Ashforth; Lixin Zhang; Baoli Zhu (Marine Biotechnology, 2010)

Bio-immobilization of Cu and Zn in recirculated bioreactor landfill - Yu-Yang Long; Li-Fang Hu; Jing Wang; Cheng-Ran Fang; Ruo He; Dong-Sheng Shen (Environmental Science and Pollution Research, 2010)

A New Hazardous Solid Waste Detoxication Method: Semi-solid Fenton Process (SSFP) - Li-Fang Hu; Yu-Yang Long; Hua-Jun Feng; Jun Yao; Cheng-Ran Fang; Dong-Sheng Shen (Water, Air, & Soil Pollution, 2010)

Identification and characterization of NARROW AND ROLLED LEAF 1, a novel gene regulating leaf morphology and plant architecture in rice - Jiang Hu; Li Zhu; Dali Zeng; Zhenyu Gao; Longbiao Guo; Yunxia Fang; Guangheng Zhang; Guojun Dong; Meixian Yan; Jian Liu; Qian Qian (Plant Molecular Biology, 2010)

Genetic characterization of E2 gene of classical swine fever virus by restriction fragment length polymorphism and phylogenetic analysis - Ning Chen; Dejiang Li; Xuemei Yuan; Xiaoliang Li; Hongxia Hu; Binglin Zhu; Xiaoyuan Wan; Weihuan Fang (Virus Genes, 2010)

Development of real-time and nested RT-PCR to detect astrovirus and one-year survey of astrovirus in Jiangmen City, China - Ying-chun Dai; Qiao-hua Xu; Xian-bo Wu; Gui-fang Hu; Ya-li Tang; Jian-dong Li; Qing Chen; Jun Nie (Archives of Virology, 2010)

Synthesis, Spectroscopy and Photochemistry of Novel Branched Fluorescent Nitro-Stilbene Derivatives with Benzopheonone Groups - Fang Gao; Jian Liu; Huayong Peng; Nvdan Hu; Hongru Li; Shengtao Zhang (Journal of Fluorescence, 2010)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Metal Pollution in Huayuan River in Hunan Province in China by Manganese Sulphate Waste Residue - Nan Hu; Ji-Fang Zheng; De-Xin Ding; Jun Liu; Lu-Qing Yang; Jie Yin; Guang-Yue Li; Yong-Dong Wang; Yu-Long Liu (Bulletin of Environmental Contamination and Toxicology, 2009)

Evolution of resistance to different classes of fungicides in Botrytis cinerea from greenhouse vegetables in eastern China - Chuan-qing Zhang; Jia-li Hu; Fang-ling Wei; Guo-nian Zhu (Phytoparasitica, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Effects of the Yangtze River source of drinking water on metabolites of Mus musculus - Yan Zhang; Dayong Zhao; Bing Wu; Fang Hu; Jie Kong; Xuxiang Zhang; Mei Li; Yibin Cui; Shupei Cheng (Ecotoxicology, 2009)

A new screening method based on yeast-expressed human dipeptidyl peptidase IV and discovery of novel inhibitors - Chen-Xi Hu; Hui Huang; Li Zhang; You Huang; Zhu-Fang Shen; Ke-Di Cheng; Guan-Hua Du; Ping Zhu (Biotechnology Letters, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

Synthesis, Spectroscopy and Photochemistry of Nitro-Azobenzene Dyes Bearing Benzophenone Parts - Fang Gao; Jianchao Wang; XiaoJiao Liu; Long Yang; Nvdan Hu; Ting Xie; Hongru Li; Shengtao Zhang (Journal of Fluorescence, 2009)

A Novel Camptothecin Derivative Incorporated in Nano-Carrier Induced Distinguished Improvement in Solubility, Stability and Anti-tumor Activity Both In Vitro and In Vivo - Min Han; Cai-Xia He; Qiu-Li Fang; Xiao-Chun Yang; Yuan-Yuan Diao; Dong-Hang Xu; Qiao-Jun He; Yong-Zhou Hu; Wen-Quan Liang; Bo Yang; Jian-Qing Gao (Pharmaceutical Research, 2009)

Vertical Transmission of Chlamydia trachomatis in Chongqing China - Jialin Yu; Shixiao Wu; Fang Li; Linyan Hu (Current Microbiology, 2009)

Porcine reproductive and respiratory syndrome viruses predominant in southeastern China from 2004 to 2007 were from a common source and underwent further divergence - Hongxia Hu; Xiaoliang Li; Zhanfeng Zhang; Jiangbing Shuai; Ning Chen; Guangqing Liu; Weihuan Fang (Archives of Virology, 2009)

Synthesis, Crystal, Absorption and Fluorescence Spectroscopy of Nitro-Stilbene Derivatives with Benzophenones - Fang Gao; Ting Xie; Zhibin Cheng; Nvdan Hu; Long Yang; Yun Gong; Shengtao Zhang; Hongru Li (Journal of Fluorescence, 2008)

Study of antioxidant activities of sulfated polysaccharides from Laminaria japonica - Xue Zhao; Chang-Hu Xue; Ba-Fang Li (Journal of Applied Phycology, 2008)

Cyclooxygenase-2 mediates the delayed cardioprotection induced by hydrogen sulfide preconditioning in isolated rat cardiomyocytes - Li-Fang Hu; Ting-Ting Pan; Kay Li Neo; Qian Chen Yong; Jin-Song Bian (Pflügers Archiv - European Journal of Physiology, 2008)

BcLTP, a novel lipid transfer protein in Brassica chinensis, may secrete and combine extracellular CaM - Chunming Wang; Wanqin Xie; Fang Chi; Wenquan Hu; Guohong Mao; Daye Sun; Cuifeng Li; Ying Sun (Plant Cell Reports, 2007)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

A rapid and accurate 3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide colorimetric assay for quantification of bacteriocins with nisin as an example - Fang Wang; Li-ting Cao; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2007)

Site-Directed Mutagenesis of Aeromonas hydrophila Enoyl Coenzyme A Hydratase Enhancing 3-Hydroxyhexanoate Fractions of Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) - Fengqing Hu; Yan Cao; Fang Xiao; Jin Zhang; Hui Li (Current Microbiology, 2007)

Study on Metsulfuron-Methyl Degradation in Simulated Wheat (Triticum Asetivum L.) Rhizospheric Soil with Penicillium sp. Inoculation - Yong Hua He; Dong Sheng Shen; Li Fang Hu; Yin Mei Zhu (Water, Air, & Soil Pollution, 2007)

Coherency matrix-based proper orthogonal decomposition with application to wind field simulation - Liang Hu; Li Li; Jian Fan; Qinhan Fang (Earthquake Engineering and Engineering Vibration, 2006)

Chloroplast Transformation in Oilseed Rape - Bing-Kai Hou; Yi-Hua Zhou; Li-Hong Wan; Zhong-Lin Zhang; Gui-Fang Shen; Zheng-Hua Chen; Zan-Min Hu (Transgenic Research, 2003)

Relative brightness index and it’s climatic significance from lacustrine sediment of napahai lake, northwestern yunnan plateau, china - Yong Yin; Nian-qiao Fang; Chao-yong Hu; Hao-gang Nie; Zun-li Qing (Chinese Geographical Science, 2002)

Chemical characters and antioxidative properties of sulfated polysaccharides from Laminaria japonica - Chang-Hu Xue; Yu Fang; Hong Lin; Lei Chen; Zhao-Jie Li; Deng Deng; Chong-Xiao Lu (Journal of Applied Phycology, 2001)

Estimation of soil organic carbon reservoir in China - Wang Shao-qiang; Zhou Cheng-hu; Li Ke-rang; Zhu Song-li; Huang Fang-hong (Journal of Geographical Sciences, 2001)

An integrated genetic map of Populus deltoides based on amplified fragment length polymorphisms - R. L. Wu; Y. F. Han; J. J. Hu; J. J. Fang; L. Li; M. L. Li; Z. -B. Zeng (Theoretical and Applied Genetics, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effect of total alkaloid ofPeganum harmala L. in the treatment of experimental haemosporidian infections in cattle - Bingtang Fan; Jilan Liang; Jucheng Men; Fang Gao; Guangling Li; Sixi Zhao; Tingjun Hu; Ping Dang; Ling Zhang (Tropical Animal Health and Production, 1997)